What determines trophic niche breadth? A global analysis of freshwater fishes using isospaces - Friedrich Wolfgang Keppeler; Tommaso Giarrizzo; Carmen G. Montaña; Alphonse Adite; Şenol Akın; Ronaldo Angelini; Caroline C. Arantes; Evanilde Benedito; Thethela Bokhutlo; Rana El-Sabaawi; Alexandre Garcia; Ivan Gonzalez-Bergonzoni; et al. (Reviews in Fish Biology and Fisheries, 2026)

Integrating lineage-specific and universal genomic probes illuminates phylogenetic relationships and molecular evolution in Sauvagesieae (Ochnaceae) - Sandra Reinales; Félix Forest; Alexandre R. Zuntini; Domingos Cardoso; Gustavo A. Ballen; Dairon Cárdenas; José R. Pirani (Molecular Phylogenetics and Evolution, 2026)

Unveiling neglected ecosystem services in semi-arid agricultural landscapes of the Brazilian Caatinga - Igor C.A. Araruna; André B. Reis; Alyce P. Alexandre; Marília B. Lion; Carolina N. Liberal; Helder F.P. Araujo; Bráulio A. Santos (Agriculture, Ecosystems & Environment, 2026)

When empirical data challenge entrenched interpretations: Revisiting the “hyaenid metanarrative” at Fuente Nueva 3 archaeological site (Orce, Granada, Spain) - José Yravedra; Lloyd A. Courtenay; Mario Gutiérrez-Rodríguez; Juan Francisco Reinoso-Gordo; Juha Saarinen; Natalia Égüez; Carmen Luzón; Juan José Rodríguez-Alba; Stefania Titton; Eva Montilla-Jiménez; José Cámara-Donoso; Darío Herranz-Rodrigo; et al. (Quaternary Science Reviews, 2026)

Far from the coast: organohalogen bioaccumulation in spinner dolphins from the Southwestern Atlantic - Caroline A.C. Corrêa; Bárbara M.R. Manhães; Nara Oliveira-Ferreira; Elitieri B. Santos-Neto; Eduardo R. Secchi; Juliana C. Di Tullio; Rodrigo C. Genoves; Haydée A. Cunha; Tatiana L. Bisi; Alexandre F. Azevedo; José Lailson-Brito (Marine Pollution Bulletin, 2026)

Terrestrial formation of calcium sulfate and carbonate assemblages in Atacama CO chondrites: Implications for Martian evaporitic environments - Gabriel A. Pinto; Vinciane Debaille; Jolantha Eschrig; Alexandre Corgne; Kevin Soto; Thierry Leduc; Sophie Decree; Steven Goderis (Icarus, 2026)

Mycorrhizal inoculum–mediated modulation of maize–rhizosphere interactions under pesticide stress - Anna Manukyan; Alexandre Pedrinho; Panagiotis A. Karas; Christos Papadopoulos; Athanasia Katsoula; Sotirios Vasileiadis; Dimitrios G. Karpouzas; Kalliope K. Papadopoulou (European Journal of Soil Biology, 2026)

Replaceable laser-textured copper foils and Cu–TiO2 composite foils for sustained suppression of microbial contamination on ICU high-touch surfaces - Alexandre M. Emelyanenko; Andrey V. Buglak; Kirill A. Emelyanenko; Edward A. Domblides; Gleb A. Putsman; Daniil V. Filin; Lusine R. Avetisyan; Marina Y. Chernukha; Sergei K. Zyryanov; Ludmila B. Boinovich (Chemical Engineering Journal, 2026)

The Asian Green Mussel Perna viridis in the Canal do Itajurú, Brazil: Establishment in a Hypersalinity-Influenced Coastal Channel - Bruno Pereira Masi; Márcio A. Siqueira; Alexandre R. da Silva; Júlio C. Monteiro; Alexandre D. Kassuga; Luciana Altvater; Luciana V. R. Messano; Ricardo Coutinho (Thalassas: An International Journal of Marine Sciences, 2026)
The Asian green mussel, Perna viridis , is a globally successful invasive bivalve first recorded in the South Atlantic in 2018. Here, we report and characterize the establishment of P. viridis in the Canal do Itajurú, a coastal channel connecting the hypersaline Araruama Lagoon to the Atlantic Ocean in Rio de Janeiro, Brazil. We assessed its spatial distribution, substrate association, and morphometric variation to evaluate local establishment and potential ecological and management implications. Perna viridis was recorded along nearly the entire channel and was strongly associated with artificial substrates, including vessels, ropes, buoys, bridge structures, and concrete rubble. Morphometric variation indicated larger individuals on more stable artificial structures, suggesting that these habitats may favor population development. Although the Canal do Itajurú is part of a hypersaline lagoon system and is subject to elevated and variable salinity, salinity was not measured during the biological survey; therefore, this occurrence should be interpreted as evidence of establishment in a hypersalinity-influenced coastal channel. The concentration of mussels on artificial substrates in economically important areas underscores the role of recreational vessels and maritime infrastructure as vectors and settlement habitats. These findings highlight the need for continuous monitoring, public awareness, and antifouling strategies to reduce further dispersal and establishment in vulnerable coastal ecosystems.

Effects of soybean oil and rumen-protected lipid sources on milk production and fatty acid profile in lactating ewes - Adrielly Lais A. da Silva; Matheus Sousa de P. Carlis; Paulo César.G. Dias Junior; Isabela J. dos Santos; Rhaíssa G. de Assis; Jamile H. Comelli; Daniel M. Polizel; Janaina S. Biava; Bruno I. Cappellozza; Alexandre V. Pires; Evandro M. Ferreira (Animal Feed Science and Technology, 2026)

Mitigating overload conditions in vibrating screens through fuzzy-controlled feed rate regulation - Alexandre G. Fonseca; Robson A. Duarte; Kaike S. Albuquerque; Thomás Pinto; Thiago A.M. Euzébio (Minerals Engineering, 2026)

Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Increasing body size unlocks gelatinous planktivory in a key coral reef fish species - James Gahan; David R. Bellwood; Renato A. Morais; Leo Nankervis; Isabelle Ng; Alexandre C. Siqueira; Cecilia Villacorta-Rath; Sterling B. Tebbett (Coral Reefs, 2026)
Coral reefs depend on the assimilation of off-reef nutrients, particularly from zooplankton, to fuel on-reef productivity. Planktivorous reef fishes thus play a critical role in sustaining a key ecosystem function as the major consumers of plankton. The importance of gelatinous zooplankton to the nutritional ecology of larger-bodied planktivorous fishes is becoming increasingly apparent. Yet, the extent to which feeding on gelatinous plankton within these taxa is a product of ontogeny has not yet been addressed. It has been hypothesised that Caesio cuning , a key planktivorous species that contributes substantially to reef fish biomass on Australia’s Great Barrier Reef, undergoes an ontogenetic diet shift from predominantly non-gelatinous prey as juveniles to a diet composed mainly of gelatinous zooplankton as adults. We examine high-taxonomic resolution DNA metabarcoding of gut contents, with morphometric analyses, to investigate whether changing body size and habitat are linked with a purported dietary transition in C. cuning . We reveal clear evidence of a shift towards increased feeding on gelatinous plankton with increasing body size in C. cuning . Across the sampled habitats, small- and large-sized individuals occupied distinct dietary spaces. The increase in size and ontogenetic dietary shift in C. cuning was also correlated with a transition towards morphological traits associated with feeding and movement in the water column. These results emphasise the importance of gelatinous zooplankton in shaping the distribution, feeding ecology, and productivity of C. cuning on coral reefs and underscore the close connection between large body size and exploitation of gelatinous plankton by reef fishes.

Integrating score-based diffusion models with machine learning-enhanced localization for advanced data assimilation in geological carbon storage - Gabriel Serrão Seabra; Nikolaj T. Mücke; Vinicius Luiz Santos Silva; Alexandre A. Emerick; Denis Voskov; Femke C. Vossepoel (Computational Geosciences, 2026)
Accurate characterization of subsurface heterogeneity is important for the safe and effective implementation of geological carbon storage (GCS) projects. This paper explores how machine learning methods can enhance data assimilation for GCS with a framework that integrates score-based diffusion models with machine learning-enhanced localization in channelized reservoirs during CO $$_2$$ 2 injection. We employ a machine learning-enhanced localization framework that uses large ensembles ( $$N_s = 5000$$ N s = 5000 ) with permeabilities generated by the diffusion model and states computed by simple ML algorithms to improve covariance estimation for the Ensemble Smoother with Multiple Data Assimilation (ESMDA). We apply ML algorithms to a prior ensemble of channelized permeability fields, generated with the geostatistical model FLUVSIM. Our approach is applied on a CO $$_2$$ 2 injection scenario simulated using the Delft Advanced Research Terra Simulator (DARTS). Our ML-based localization maintains significantly more ensemble variance than when localization is not applied, while achieving comparable data-matching quality. This framework has practical implications for GCS projects, helping improve the reliability of uncertainty quantification for risk assessment.

Atmospheric fate of ketolimonene part 2: Highly oxygenated molecules (HOMs) and secondary organic aerosol (SOA) formation from NO3-initiated oxidation - Sandy Solaiman; Prasanna Kumar Bej; Cécile Coeur; Nicolas Houzel; Hayley Furnell; Emma Galloway; Fabrice Cazier; Amir Ben Brik; Mixtli Campos-Pineda; Estelle Roth; Albert A. Ruth; John C. Wenger; et al. (Journal of Environmental Sciences, 2026)

Assessment of Eucalyptus seedlings grown in biodegradable containers and their growth in clonal plantations - Vitor S. Brito; Emanuela F. Gama-Rodrigues; José L. M. Gonçalves; Alexandre V. Ferraz; José C. A. Júnior (New Forests, 2026)

Geographic patterns of Darwinian shortfall and implications for fish conservation in the Tocantins-Araguaia River basin - Laura Barreto de Paula-Souza; Murilo Sversut Dias; Gabriel Nakamura; Guilherme Rogie Gonçalves Tavares; Fabrício Barreto Teresa; Geiziane Tessarolo; Fernanda A. S. Cassemiro; José Alexandre Felizola Diniz-Filho (Hydrobiologia, 2026)
To understand biodiversity patterns at distinct geographic scales, it is important to consider the impacts of lack of knowledge (shortfalls) on such patterns. Our aim here is to evaluate the spatial patterns in the lack of phylogenetic knowledge (i.e., Darwinian shortfall) among fish species in the Tocantins-Araguaia River Basin and to correlate it with key conservation metrics and patterns, including the difference between protected and non-protected areas. We used linear models to test these relationships, considering the spatial structure of the basin. We highlight a high level of Darwinian shortfall for the basin, where 35% of the evolutionary history is unknown, which is more pronounced in the Tocantins drainage. Also, we found that endemism, phylogenetic diversity, rarity, and species richness are predictors of the shortfall. This study underscores a critical knowledge shortfall in the Tocantins-Araguaia River basin, a region of national and global significance due to its remarkable biodiversity. The positive correlations found between the Darwinian shortfall with endemism, phylogenetic diversity, and rarity imply that the basin's distinctive evolutionary history remains underappreciated. Consequently, we highlight key regions within the basin that are imperative for future aquatic research.

Soil contamination assessment of a 19th-century abandoned Sb–Au mine in northern Portugal - Giulia Resta; Patrícia Santos; Marcus Monteiro; Rui Melo; Morgana Carvalho; Ana Carvalho; Alexandre Lima; Eric Font; José A. Ribeiro; Manuel Azenha; Thierry Adatte; Deolinda Flores (Environmental Geochemistry and Health, 2026)
Abandoned mines are among the main sources of long-term soil contamination, often leaving behind persistent concentrations of potentially toxic elements (PTE) that pose environmental and health risks. Ribeiro da Serra Sb–Au mine, in Portugal, active from 1858 to 1890, has left a significant environmental legacy. This study mapped the spatial distribution of mine processing residues, elemental characterisation distinguishing between anthropogenic and natural enrichment by determining soil sample concentrations of PTE, Hg mobility, and Total Organic Carbon (TOC) quantification. Multivariate analysis, spatial interpolation and comparison with Enrichment Factor were employed with the aim of understanding the distributions and sources of PTEs in the soils. Mercury is still present at the site, revealing high mobile (18.72 mg kg −1 ) and semi-mobile (3.58 mg kg −1 ) concentrations accumulated in waste piles, a remnant of Au amalgamation processes. High Hg concentrations (20.75 mg kg −1 ) pose significant environmental risks, even after more than a century, such as bioaccumulation potential and soil toxicity. Also, there are high concentrations of Pb (449.03 mg kg −1 ) in the waste piles from the Sb processing. This study highlights the critical importance of interpreting natural enrichment values of elements of Hg (EF = 267) and Pb (EF = 18) to discern pollution pathways resulting from mining and processing activities. Interpretation of natural enrichment values leads to a more accurate evaluation of environmental contamination and its sources. The Enrichment Factor shows that Sb (EF = 133) and Hg (EF = 267) are the elements that present extremely high enrichment (EF > 40).

Brazil’s science–policy effort to monitor native vegetation restoration - André L. Giles; Marina G. Freitas; Ana L. V. Espada; Pedro Constantino; Bruno S. Francisco; Silvia B. Rodrigues; Alexandre B. Sampaio; Isis F. de Freitas; Gabriela C. S. Bueno; Raquel C. A. Lacerda; R. Edson; Kirsten Silvius; et al. (Ambio, 2026)
In its early years, the UN Decade on Ecosystem Restoration has mobilized unprecedented global commitments. Yet, measuring restoration success remains contested, particularly in megadiverse countries where the absence of standardized indicators and assessment protocols often leads to subjective decisions by environmental agencies. Here, we present a core set of leading indicators developed through a pioneering Brazil-led science–policy collaboration between environmental agencies and research institutions. The indicators capture early vegetation recovery within four years and whether restoration trajectories are sustained or at risk of reversal. The initiative also establishes a framework that bridges science and policy to deliver practical monitoring tools. It offers a model for other megadiverse countries with complex governance, showing how simple, standardized indicators can translate restoration pledges into measurable results for the UN Decade.

The Franciscana ( Pontoporia blainvillei ) in the Northern Limit of the FMA II : Strandings and Habitat Use in I lha G rande B ay - Alexandre F. Azevedo; Rafael R. Carvalho; Karina S. Pereira; Lis Bittencourt; Elitieri B. Santos‐Neto; Lara V. Pereira; Beatriz A. Santos; Gian Berardinelli; Haydée A. Cunha; Tatiana L. Bisi; José Lailson‐Brito (Marine Mammal Science, 2026)
The presence of the franciscana ( Pontoporia blainvillei ) at the northern limit of the FMA II was investigated using a range of methods, including monitoring of strandings, boat surveys, and passive acoustic monitoring (PAM). Franciscana strandings were recorded within the distributional gap between Macaé (22°55′ S) and Ilha Grande (23°09′ S), suggesting that the northern boundary of the FMA II may extend as far as Jaconé (22°56′ S; 42°38′ W). Furthermore, habitat use in Ilha Grande Bay was investigated through a combination of boat surveys and PAM efforts. Our findings support the idea that the species use Ilha Grande Bay year‐round, both day and night, and this bay might be the primary habitat of P. blainvillei in the FMA II section of the Rio de Janeiro coast. In Ilha Grande Bay, the franciscana is widely distributed over an area of more than 300 km 2 , along isobaths between 8 and 30 m. There were multiple detection events at the same PAM station during the day, indicating that the species was present at different times of day at the same location. Average group size was 7.7 (±6.7). While P. blainvillei occupies a large area of the bay, further investigation is needed into its use of shallower waters and the deeper, central portion of the bay, as well as the presence of areas with higher individual densities.

Climate Predicts Tree Dispersal Strategies Across Brazil's Ecosystems - Fernanda C. Souza; Vinícius Andrade Maia; Renata Françoso; Matheus Coutinho Freitas de Oliveira; Ana Beatriz Ligo; Bruno X. Pinho; Jesús Aguirre‐Gutiérrez; Martin Sullivan; Larissa Rocha‐Santos; Laura de Brito Évora; Leonardo de Sousa Miranda; María Natalia Umaña; et al. (Global Ecology and Biogeography, 2026)
Aim We investigate the distribution of dispersal modes — endozoochory (via animal ingestion), synzoochory (via animal seed accumulation) and anemochory (via wind)—and seed mass of woody plants across Brazilian ecosystems, testing whether their relative abundance in local plant communities could be predicted by climate, edaphic factors and dispersal agents (e.g., the main vectors moving seeds). We expected climate to be the main predictor of dispersal strategy abundance. Location Brazilian ecosystems (Amazon, Atlantic Forest, Cerrado and Caatinga). Time Period 2004–2020. Major Taxa Studied Woody angiosperms, trees and shrubs. Methods We assigned seed mass to 1984 species and dispersal mode to 2203 species within 300 old‐growth and non‐flooded plots. We employed Random Forest regressions to assess the influence of water availability, temperature seasonality, soil fertility, wind and frugivorous primates on the community‐weighted means of seed mass and dispersal modes. We mapped predictions and estimated the area of applicability to identify regions where predictions were reliable. Results Climate was the main factor predicting tree dispersal strategies, followed by dispersal agents or soil properties. Endozoochory was prevalent in wetter regions with high water availability and greater diurnal temperature range. Anemochory was more common in drier regions with low water availability, stronger winds and greater diurnal temperature range, whereas synzoochory was more abundant in areas with low temperature seasonality. Heavier seeds were more prevalent in regions with less seasonal temperatures, smaller diurnal temperature ranges and weaker winds. Main Conclusions Climate is a key predictor of the distribution and prevalence of plants with contrasting dispersal modes and seed masses. We thus expect functional responses to environmental change associated with shifts in the relative abundance of dispersal strategies, with implications for ecosystem services. Our results also highlight the critical role of plot‐based datasets in improving our understanding of how environmental factors influence seed dispersal strategies across tropical ecosystems.

Sea state estimation from full-scale FPSO motions using neural networks: Assessment based on in-service records and metocean reanalysis - Gustavo A. Bisinotto; João V. Sparano; Alexandre N. Simos; Fabio G. Cozman; Marcos D. Ferreira; Eduardo A. Tannuri (Ocean Engineering, 2026)

Potential of guava pulps treated by ohmic heating as a delivery vehicle for probiotic bacteria: stability, functional properties, and in vitro digestibility - Newton C. Santos; Raphael L.J. Almeida; Virgínia M. de A. Silva; Thalis L.B. de Lima; Ronildo P. de Sousa Júnior; Victor H. de A. Ribeiro; Yaroslávia F. Paiva; Francislaine S. dos Santos; Deyzi S. Gouveia; Rennan P. de Gusmão; Alexandre J. de M. Queiroz; Josivanda P. Gomes; et al. (International Journal of Food Microbiology, 2026)

A novel framework for temporal data transformation in environmental risk assessment: Addressing data variability and gaps in monitoring - Tiago H. Marum; Ronney R. Agra; Ramoel Serafini; Alexandre Maximiano; Fábio Lofrano; Fernando A. Kurokawa (Environmental Impact Assessment Review, 2026)

Correction: Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Intergroup Encounters Among Wild White-Faced Capuchins (Cebus imitator) at a Densely Populated Field Site: Insights into Frequency, Intensity, and Participation - Sarah A. Kovalaskas; Agostina Colosimo; Vasco Alexandre Martins; Juan Carlos Ordoñez; Elena Morera Saborío; Jacinta C. Beehner; Thore J. Bergman; Marcela E. Benítez (International Journal of Primatology, 2026)
Intergroup encounters (IGEs) are a major feature of social life for group-living primates, influencing access to resources, reproductive opportunities, and territory. We examined IGE frequency, intensity, and participation in a high-density population of wild white-faced capuchin monkeys ( Cebus imitator ) at the Capuchinos de Taboga research project in Guanacaste, Costa Rica, using 4 years of data on three capuchin groups (4,984 observation hours, 218 IGEs). The IGE rates at Taboga (0.044/hr) were two to four times higher than those at nearby lower-density sites and did not vary with rainfall or temperature. More than half of IGEs involved high-intensity aggression (chases or contact aggression). Ordinal logistic models showed that the number of focal group participants was a consistent predictor of escalation, with each additional participant increasing the odds of higher intensity by 1.4 times, while ecological variables had little explanatory value. Participation was more likely for older individuals, males, alphas, and when individuals were closer to the center of core use areas; males participated more than females at distances further from the center of core use areas. Females participated in 44% of IGEs, with lactating females less likely to participate than cycling or pregnant females. Our findings suggest that high population density and overlapping ranges drive frequent and aggressive IGEs at Taboga and that escalation is shaped primarily by social rather than ecological factors. These results highlight the importance of social processes in territorial defense and underscore their role in shaping intergroup conflict in areas of high population density.

Modeling longitudinal changes of maximal short-term power outputs in young volleyball players: a Bayesian analysis - Humberto M. Carvalho; André L. A. Soares; Alexandre M. Oliveira; Luciano G. Galvão; Fábio C. Karasiak; Felipe G. Mendes; Rui Resende; Carlos E. Gonçalves (German Journal of Exercise and Sport Research, 2026)

Yield stability and multi-trait selection for agronomic and food quality traits in white guinea yam (Dioscorea rotundata) across multiple locations in Benin Republic - Esperance D. Codjia; Myriame Dansi; Jeannette Gbemissola Fakorede; Asrat Asfaw; Paterne A. Agre; Igor O. Yelome; Yêyinou Laura Estelle Loko; Abel Amegan; Honorine Ogou; Alexandre Dansi (Euphytica, 2026)

PAHs in Sediments from Amazon Mangrove and Oyster Farming Areas: Sources, Ecological Risks and Potential Toxicity - Cibelle C. L. Brandão; Thaís R. Sousa; James T. Lee; Júlia A. Ferreira-Griz; Dioniso S. Sampaio; Alexandre M. C. Carmo; Eliete Zanardi-Lamardo; Silvia K. Kawakami (Bulletin of Environmental Contamination and Toxicology, 2026)
Sixteen polycyclic aromatic hydrocarbons (PAHs) were examined in mangrove sediments from three Amazonian municipalities, known for port operation, fish market (Curuçá), oyster production (Augusto Corrêa) and tourism (Salinópolis). ∑PAH concentrations (4.55–1303 ng g −1 dry sediment; mean: 246 ± 644) indicated low to moderate contamination, in the order: Curuçá ≫ Salinópolis > Augusto Corrêa, with the maxima near natural oyster banks (Curuçá) and lowest in the oyster farming area (Augusto Corrêa). Contamination sources and apportionment were investigated using diagnostic ratios and multivariate analysis, estimating 30% from fossil fuel combustion, 59% from biomass/coal burning and 11% from petrogenic and natural sources. Carcinogenic benzo[a]pyrene-equivalent toxicity was below threshold guidelines, but dibenzo[a,h]anthracene exceeded ecological risks and integrative indices in Curuçá and Salinópolis samples. A potential PAH transfer risk from suspended sediments to oyster may occur. Our results contribute to the local socioeconomic basis with environmental quality dataset and baseline PAHs in mangrove areas.

Projected Impacts of Climate Change on Interactions Between Plants and Avian Frugivores Across the Americas - Alexandre J. C. Rabeau; Alex L. Pigot; Joseph A. Tobias; Matthias Schleuning (Global Ecology and Biogeography, 2026)
Aim Frugivorous birds provide crucial seed‐dispersal functions in terrestrial ecosystems. However, the impact of climate change on plant–avian frugivore interactions remains unclear due to past methodological limitations. In this study, we address this by mapping these interactions across the Americas and projecting shifts in interaction diversity under future climate scenarios. Location North, South, and Central America. Time Period Present (1980–2010) and future (2070–2100). Major Taxa Studied Frugivorous birds and fleshy‐fruited plants. Methods Using a trait‐matching framework, we estimated interaction probabilities between frugivorous birds ( n = 539 species) and fleshy‐fruited plants ( n = 3280 species) at the ecoregion level. To estimate climate impacts, we modeled how interaction probabilities will change under future scenarios based on the overlap between avian climate niches and ecoregion climates. From these probabilities, we calculated plant–frugivore interaction diversity as the effective number of avian partners for a given plant species in an ecoregion. We then used simulations to examine how avian dietary flexibility and dispersal may buffer future diversity of plant–frugivore interactions. Results Under future climate scenarios, our models projected a decline in interaction diversity across most ecoregions, especially in tropical and subtropical biomes. Simulations indicated that interaction rewiring through dietary flexibility and dispersal could partially mitigate losses of interaction diversity, particularly in tropical forests. Main Conclusions Our results suggest that the diversity of plant–frugivore interactions in the Americas will decline in response to climate change, potentially undermining the stability of seed‐dispersal functions. We also show that the resilience of this function depends on the capacity of frugivorous birds to modify their geographic ranges or dietary preferences. However, the extent to which avian dispersal and adaptation will regulate future species interactions remains unknown, highlighting the importance of maintaining high plant–frugivore interaction diversity in current assemblages to buffer ecosystems against future climatic changes, especially in the tropics.

Environmental risk assessment following Brazilian mining dam collapse: A diffusion approach - Leticia A. Bertoldo; Barbara Kroetz; Cecilia S. dos Reis; Emilli Frachini; Angelita Ribeiro; Alexandre Urbano; Taufik Abrão; Maria Josefa Santos (Chemosphere, 2026)

Environmental gradients shape fish assemblages across estuarine-coastal ecosystems on the eastern Brazilian coast - Rafael L. Oliveira; Germano Henrique Costa Barrilli; Mauricio Hostim-Silva; Ronaldo R. Oliveira-Filho; Helen A. Pichler; André P. Cattani; Ryan Andrades; Ciro C. Vilar; Ana C. Martins; Valéria M. Lemos; Alexandre M. Garcia; Henry L. Spach; et al. (Marine Environmental Research, 2026)

Atmospheric fate of ketolimonene part 1: temperature-dependent kinetics and gas-phase products from NO3-initiated oxidation - Sandy Solaiman; Prasanna Kumar Bej; Cécile Coeur; Nicolas Houzel; Hayley Furnell; Emma Galloway; Amir Ben Brik; Mixtli Campos-Pineda; Estelle Roth; Albert A. Ruth; John C. Wenger; Alexandre Tomas; et al. (Journal of Environmental Sciences, 2026)

Effects of Channel Characteristics on Wastewater Chemical Transformation in Rivers - Robert A. Newbould; D. Mark Powell; Juliet Hodges; Alexandre Teixeira; Michael J. Whelan (Water, Air, & Soil Pollution, 2026)
Microbially-mediated transformations are important for removing wastewater chemicals in rivers. In-stream degradation rates are likely to be affected by channel morphology and size because these factors determine the extent of chemical contact between the water column and the microbial community in fixed biofilms, where most microbially-mediated processes are expected to take place. We hypothesize that transformation rate constants are inversely proportional to hydraulic radius ( R : the ratio of channel cross-sectional area to wetted perimeter). Microbial transformations are also predicted to be controlled systematically by bed sediment characteristics. This will be a function of sediment surface area per unit volume (for biofilm colonisation) and hyporheic exchange. Here, we test the above hypotheses in controlled 14-day laboratory experiments, by monitoring nitrification and biodegradation in stirred tanks with three different water depths and three different sediment sizes (sand, gravel and cobbles). Transformation rate constants were inversely proportional to depth, supporting the notion that channel morphology represents a significant system-specific control. Rate constants for nitrification were highest in the gravel treatments and lowest in sand. This suggests that intermediate grain sizes simultaneously allow good biofilm colonisation and solute exchange between sediment and the water column. There was, however, little difference in biodegradation rate constants between different sediment sizes. This study highlights the need to consider geomorphology in models of chemical exposure.

Creating Engineered NAC Flaps Using in Vivo Revascularization: A Proof-Of-Concept Study - Yanis Berkane; Alperen Abaci; Bradley W. Ellis; Loïc van Dieren; Edvin Hendi; Haizam Oubari; Nicolas Bertheuil; Ruben Oganesyan; Curtis L. Cetrulo; Michelle E. McCarthy; Mark A. Randolph; Alexandre G. Lellouch; et al. (Stem Cell Reviews and Reports, 2026)

Synergistic effects from combining foliar and soil inoculation of plant growth promoting microbes: enhanced sugarcane physiology and rhizosphere modulation via organic acid exudation and nitrogen - cycling - Mariley Fonseca; João William Bossolani; Luis Fernando Merloti; Márcio F. A. Leite; Alexandre Pedrinho; Fernando Dini Andreote; Carlos Alexandre Costa Crusciol (Biology and Fertility of Soils, 2026)
Sugarcane ( Saccharum officinarum L.) is a strategic crop for the energy sector, but its intensive cultivation requires sustainable management practices. Plant growth-promoting bacteria (PGPB) such as Azospirillum brasilense and Nitrospirillum amazonense are known for their ability to fix atmospheric nitrogen and stimulate growth in grasses. This study evaluated the effects of inoculation with A. brasilense ( Ab ) and N. amazonense ( Na ), applied individually or in combination ( Ab + Na ), on sugarcane physiology, nitrogen use efficiency, root exudation, and rhizospheric microbial communities. The experiment was conducted under controlled greenhouse conditions with four treatments: Control (no inoculation), Ab , Na , and Ab + Na . The Ab + Na treatment promoted the highest photosynthetic rate, carboxylation efficiency, and water use efficiency. These physiological responses were associated with greater nitrogen accumulation in roots, rhizomes, and leaves, as well as increased total biomass and 15 N fertilizer recovery. Nitrogen losses were significantly reduced in Ab and Ab + Na treatments. At the molecular level, rhizosphere soil analysis showed a reduced abundance of microbial functional genes related to nitrification and denitrification ( amoA , nirK , and nosZ ) in inoculated treatments, indicating a lower potential for nitrogen losses. However, gene abundances were higher in the Ab + Na than in the individual inoculations, likely due to greater organic acid exudation stimulating soil organic matter mineralization. Only Ab and Ab + Na increased nifH abundance, indicating enhanced biological nitrogen fixation, predominantly associated with A. brasilense . The Ab + Na treatment also led to a distinct rhizospheric microbial profile and promoted more uniform microbial community structure. These findings suggest that combining microbial inoculants improve plant nitrogen efficiency and modify rhizosphere functioning through coordinated physiological and microbial mechanisms. Foliar inoculation with compatible PGPB offers a promising strategy for sustainable sugarcane intensification.

Taxonomic uncertainty: causes, consequences, and metrics - Leila Meyer; Richard J. Ladle; Rafaela J. Trad; Annelise Frazão; Lívia Frateles; Thainá Lessa; Rafael B. Pinto; Tiago M.S. Freitas; Geiziane Tessarolo; Jhonny J.M. Guedes; Rodrigo A. Castro-Souza; Herison Medeiros; et al. (Trends in Ecology & Evolution, 2026)

Wind conditions do not consistently affect large-scale movement decisions of large savanna herbivores - Sara Gomez; Melinda Boyers; Alexandre Caron; Daniel Cornelis; Henjo de Knegt; Michel de Garine-Wichatitsky; Jasper A. J. Eikelboom; J. Werner Kilian; Norman Owen-Smith; Thomas Prin; Adrian M. Shrader; Jared A. Stabach; et al. (Oecologia, 2026)

Enigmatic granite–gneiss domes within the Balkan fold-and-thrust belt, Bulgaria: Tracers of Gondwana–Baltica proximity and large-scale terrane displacement during the waning stages of the Cadomian orogeny? - Jiří Žák; Martin Svojtka; Ianko Gerdjikov; Lukáš Ackerman; Václav Kachlík; Jiří Sláma; Dian A. Vangelov; Alexandre Kounov; R.Damian Nance; J.Brendan Murphy; Jitka Míková (Gondwana Research, 2026)

Orange (Citrus sinensis) essential oil as feed additive for sheep: nutrient intake and apparent digestibility, nitrogen balance, and rumen fermentation characteristics - Paulo César G. Dias Junior; Ana Carolina S. Vicente; Isabela J. dos Santos; Letícia C. B. Soares; Adrielly L. A. da Silva; Rhaissa G. de Assis; Jamile Haddad Comelli; Daniel M. Polizel; Janaina S. Biava; Diogo F. A. Costa; Alexandre V. Pires; Evandro M. Ferreira (Tropical Animal Health and Production, 2026)

Quantitative morphology supports the synonymy of Dasyprocta ruatanica O. Thomas, 1901 under D. punctata J. E. Gray, 1842 (Rodentia: Dasyproctidae) - Manfredo A. Turcios-Casco; Pablo Teta; Nicolás Reyes-Amaya; Celeste M. López; Don E. Wilson; Alexandre Schiavetti (Journal of Mammalian Evolution, 2026)
The taxonomic status of Dasyprocta ruatanica Thomas, 1901, described as an endemic species from Roatán Island, Honduras, has remained controversial. Its diagnosis relied primarily on smaller body size and darker pelage compared to D. punctata Gray, 1842; traits later accepted by several authors. However, these characters are known to vary in insular mammals, where dwarfism and darker colorations are common ecological responses. Our morphometric analyses, based on multivariate approaches, demonstrate extensive overlap between D. ruatanica and D. punctata , with no statistically significant divergence in overall cranial and mandibular shape. Nonetheless, Roatán individuals show consistent reduction in size relative to both continental and other insular populations, confirming a strong pattern of island dwarfism. These results indicate that D. ruatanica does not warrant species-level recognition but rather represents a morphologically distinct insular lineage. Based on our findings, we propose treating D. ruatanica under the trinomial name of Dasyprocta punctata ruatanica . This reclassification maintains taxonomic stability while acknowledging its unique evolutionary trajectory. From a conservation perspective, the Roatán population remains highly vulnerable due to its restricted range, habitat loss, hunting, and possible introgression from introduced D. punctata . Effective management should prioritize habitat preservation, and invasive species control underscoring the need for tailored management to protect this insular lineage.

Removal of Bisphenol A, Bisphenol S, and Estrogenic Activity from Real Wastewater Using a Multi-stage IFAS System - Amanda F. do Amaral; Alexandre S. A. da Silva; Deivisson L. Cunha; Priscila M. de O. M. Cunha; Rodrigo Coutinho; Marcia Marques (Bulletin of Environmental Contamination and Toxicology, 2026)
This study evaluated the removal of bisphenol A (BPA), bisphenol S (BPS), and estrogenic activity from real municipal wastewater using a pilot-scale multi-stage integrated fixed-film activated sludge (MS-IFAS) system. The configuration comprised five sequential reactors (Anaerobic, Anoxic-1, Aerobic under IFAS, Anoxic-2, and Re-aeration) providing distinct redox conditions. Influent concentrations averaged 112.6 ± 49.5 µg L −1 for BPA and 6.6 ± 3.0 µg L −1 for BPS. Overall removal efficiencies reached 99.8 ± 0.1% and 97.7 ± 1.0%, respectively, despite influent variability. The aerobic IFAS reactor was the main contributor to contaminant degradation, maintaining performance even after a > 90% biomass loss. Estrogenicity, assessed by the Yeast Estrogen Screen assay and expressed as 17β-estradiol equivalents (E2-EQ) decreased by 83.2% (0.031–0.005 ng L −1 ). Effluent E2-EQ values were below ecotoxicological thresholds, indicating negligible estrogenic risk to aquatic organisms. These highlight the strong potential of MS-IFAS for removal of xenoestrogenic contaminants in real wastewater.

Seasonal biochemical fingerprints of outdoor cultivated Spirulina (Limnospira platensis) and Microchloropsis gaditana: insights into compositional and functional shifts - Diana Lopes; Ana S.P. Moreira; Tiago Conde; Andreia Ferreira; Kayane Oliveira; Alexandra Conde; Helena R. Rocha; Marta Coelho; Ana Gomes; Manuela Pintado; Ana Alexandra Ramos; Hugo Pereira; et al. (Algal Research, 2026)

Comparative analysis of Byssal thread production, mechanical properties, and composition in diploid and triploid Mytilus edulis - Kevin Osterheld; John Davidson; Luc A. Comeau; Tiago Hori; José M.F. Babarro; Isabelle Marcotte; Alexandre A. Arnold; Christian Pellerin; Richard Saint-Louis; Réjean Tremblay (Aquaculture, 2026)

Prospect of kitchen wastes for biomaterials and biogas production in a biorefinery approach - Rebeca Esteban-Lustres; Kai L. Baltrusch; Javier Seijo; Sheyma Inoubli; María Dolores Torres; Guido Domingo; Candida Vannini; Patricia A. Romero-Jung; Beatriz Piñeiro-Lago; Antonio Pazos; Alexandre González-Novoa; Andrea Rodríguez Montes; et al. (Bioresource Technology Reports, 2026)

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

A New Poecilia (Pamphorichthys) Species (Cyprinodontiformes: Poeciliidae) and Its Conservation Implications at the Chapada Diamantina, Bahia, Brazil - Luisa Maria Sarmento-Soares; Carlos Augusto Figueiredo; Alexandre Clistenes de A. Santos (Fishes, 2026)
A new species of Poecilia, subgenus Pamphorichthys, is described from the Cachoeirinha River, a tributary of the upper Paraguaçu River basin in the Chapada Diamantina, Bahia, Brazil. Pamphorichthys is diagnosed among the Poecilini by the strongly pigmented gonopodium in mature males and the equally pigmented urogenital region in females. The new species exhibits four diagnostic features defining the Pamphorichthys clade within Poeciliidae. Males display a unique combination of a reticulated body pattern with diffuse vertical bars and a highly modified pelvic fin. The male pelvic fin possesses a subterminal process on the second ray, similar to that found in the limbs of Pamphorichthys, but highly modified. Although it shares the unique pelvic-fin processes of Pamphorichthys, its gonopodium exhibits reduced ornamentation, resembling the condition in P. pertapeh and P. akroa. Its discovery in an isolated drainage within the Chapada Diamantina underscores the notable endemism of the region. However, the species faces an imminent conservation crisis. Its only known habitat has undergone severe degradation in the last few decades. An excessive water withdrawal has collapsed the Utinga River, one of the main tributaries of the upper Paraguaçu River, and anthropogenic degradation can lead to the disappearance of species, even before it becomes known.

Law 22017/2023: a dire threat to the Cerrado's survival and Brazil's environmental leadership - Luciane Martins de Araújo; Manuel Eduardo Ferreira; José Antônio Tietzmann e Silva; Giovanni Martins de A. Mascarenhas; Altair Sales Barbosa; Mariana Pires de Campos Telles; José Alexandre Felizola Diniz-Filho; Ludgero Cardoso Galli Vieira; Geraldo Wilson Fernandes; Stephannie Fernandes; José Aluízio Ferreira Lima; Flávia de Figueiredo Machado (Environmental Development, 2026)

Cost-Effective rhamnolipids production from corn Bran and their application in essential oil extraction - Juliana P. Marques Teixeira; Gabriela Dornelas Marques; Michel Pedro Batista; Karen Stefany Conceição; Thaísa Maria da Roda Lino; Natalia Belebecha Terezo; Cesar Augusto Tischer; Alexandre Orsato; Gerson Nakazato; Nicole Caldas Pan; Josiane A. Vignoli; Doumit Camilios-Neto (World Journal of Microbiology and Biotechnology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Analysis of the energy and nature of bandgap in layered double hydroxides Mg-Al-X and Zn-Al-X (X= Cl − , OH − , CO 3 2 − , or NO 3 − ) - Márcio F. Santos; Pedro Ivo R. Moraes; Sérgio R. Tavares; A.S. Martins; Rodrigo B. Capaz; Fernando Wypych; Alexandre A. Leitão (Applied Clay Science, 2026)

Preliminary pre-formulation studies of novel mexiletine analogs: Focus on solid-state characterization - Michelle A. Sarcinelli; Thalita M. Silva; Cinira Fandaruff; Viviane S. Vaiss; Larissa L. Lima; Emerson T. da Silva; Marcus V.N. de Souza; Alexandre A. Leitão; Fabio F. Ferreira; Jorge C.S. Costa; Marco A. Martins; Helvécio V.A. Rocha (Next Research, 2025)

Kinetics of thermochemical sulfate reduction based on pyrolysis gold-tube experiments on lacustrine oil: Implications for H2S prediction in Brazilian pre-salt reservoirs - Igor V.A.F. Souza; Yongchun Tang; Le Lu; Alexandre A. Ferreira; Geoffrey S. Ellis; Rut A. Díaz; Luiz Felipe Carvalho Coutinho; Ana Luiza S. Albuquerque (Marine and Petroleum Geology, 2025)

Pre-seismic ionospheric disturbances (PIDs) associated With 2021 Mw 7.5 Northern Peru earthquake: GNSS and ground uplift observations - Oluwasegun M. Adebayo; Esfhan A. Kherani; Alexandre A. Pimenta; Babatunde Rabiu (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Soil–climate interactions drive above-ground biomass in the Caatinga, the largest Neotropical seasonally dry tropical forest - Alexandre T. Brunello; Domingos Cardoso; Peter W. Moonlight; Ítalo A. C. Coutinho; John Cunha; Mário M. do Espírito Santo; Magna S. B. de Moura; Luciano P. de Queiroz; Rubens M. dos Santos; Tiina Särkinen; Raquel C. Miatto; Tony C. de S. Oliveira; et al. (Plant and Soil, 2025)

Gut microbiota and NLRP3 inflammasome activation in hemodialysis patients: exploring the link with systemic inflammation - Denise Mafra; Livia Alvarenga; Ludmila F.M.F. Cardozo; Júnia Schultz; Alexandre Soares Rosado; Natália A. Borges (Molecular Biology Reports, 2025)

Crown Exposure Regulates Aboveground Wood Productivity Responses to Soil Fertility in Lowland Tropical Forests - José A. Medina‐Vega; Álvaro Duque; Daniel Zuleta; Nicolás Castaño; Renato Valencia; Salomón Aguilar; David Mitre; Rolando Pérez; Shawn K. Y. Lum; David F. R. P. Burslem; Michael J. O'Brien; Glen Reynolds; et al. (Ecology Letters, 2025)
Understanding the drivers of aboveground wood productivity (AWP) in tropical forests is crucial for explaining ecosystem functioning and predicting their responses to environmental change. While climatic water availability is a well‐established driver, the role of soil nutrients and their interaction with other resources remains uncertain. We investigated how soil nutrients and light interactions shape AWP in lowland tropical forests using fine‐scale soil and tree (≥ 1 cm DBH) data from 15 large forest plots. Canopy‐exposed trees are nutrient‐limited, with AWP increasing more with phosphorus (P) than with potassium (K), indicating P's greater role in plant growth and productivity. Conversely, understory AWP declined in fertile areas, likely due to intensified size‐asymmetric competition. At the population level (mean across canopy layers), no relationship between soil nutrients and AWP emerged because contrasting responses among layers offset any overall association. Our results suggest that fine‐scale heterogeneity and canopy stratification drive nutrient effects on tropical forest productivity.

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Phosphorus recovery from pig manure: Elucidating the competition between vivianite and siderite formation - Sophie Banke; Jacobo Meca Romero; Alexandre Monteiro; Thomas Prot; Leon Korving; Carlo Belloni; Chris Schott; Iulian A. Dugulan; Mark C. M.van Loosdrecht (Chemical Engineering Journal, 2025)

Life cycle and biological parameters of Feltia repleta (Walker, 1857) (Lepidoptera: Noctuidae), an economically important cutworm in tropical America - Alexandre Specht; Fernando M. S. Dias; German San Blas; Willian R. F. Camargo; Murilo Fazolin; Vânia F. Roque-Specht; Tamara A. Takahashi; José R. P. Parra (Phytoparasitica, 2025)

Soft Range Limits Shape Sensitivity to Forest Cover More Strongly Than Hard Range Limits - Natasha R. Granville; Alex L. Pigot; Benjamin Howes; Luiz dos Anjos; Victor Arroyo‐Rodriguez; Luc Barbaro; Jos Barlow; Matthew G. Betts; Alexis Cerezo; Pedro F. Develey; Jack H. Hatfield; Hervé Jactel; et al. (Global Ecology and Biogeography, 2025)
Aim Land‐use change is a major threat to biodiversity, yet there remains considerable unexplained variation in how it affects different populations of the same species. Here, we examine how sensitivity to forest cover changes depending on proximity to different limits of a species' range. By comparing responses as species approach their coastal (‘hard’) and inland (‘soft’) range limits, we aim to provide insight into the relative influence of mass effects, as compared to abiotic and biotic environmental suitability in shaping population sensitivity. Location Global. Time Period 1996–2019. Major Taxa Studied Birds. Methods We combined data from several large databases to obtain a dataset of 2543 bird species surveyed across 116 studies, spanning six continents. Using expert‐verified range maps, we calculated the position of populations relative to their species' nearest inland (‘soft’) and coastal (‘hard’) range limits and categorised the inland limits as equatorward‐ or poleward‐ facing. We investigated how distance to range limits and forest cover, derived from a 30 m‐resolution global dataset, affect the probability of species' incidence. Results We found that bird populations are more sensitive to forest cover when located closer to their species' inland (‘soft’) range limits, whereas this was not the case at coastal (‘hard’) range limits. The heightened sensitivity to forest cover at soft range limits was similar regardless of whether the range limit faced equatorward or poleward. Main Conclusions These results highlight how populations close to the soft limits of their species' ranges are at higher risk of extirpation resulting from loss of forest cover. This suggests that environmental conditions (e.g., climate), which become more challenging away from the core of the species' range, drive variability in sensitivity to forest cover.

Myiasis-causing flies in anurans: new interactions, geographic distribution, and an updated list of records in the Neotropics - Franciele Cristina de Souza; Victor Morais Ghirotto; Alexandre Polletini Neto; Camila Saraiva dos Anjos; André Luís F. da Silva; Rodrigo Lingnau; Emeline da S. Ceccon; Cátia Antunes de Melo-Patiu †; Mirco Solé; Silionamã P. Dantas; Claudio Borteiro; Domingos de J. Rodrigues; et al. (Biologia, 2025)

Nanoencapsulated flavonoids for enhanced modulation of the microbiota-gut-brain axis and neurodegenerative add-on therapy - Thiécla Katiane Osvaldt Rosales; Pedro Brivaldo Viana da Silva; Paulo Alexandre Oliveira; Marcus Vinicius Zanetti; Hélder A. Santos; João Paulo Fabi (Trends in Food Science & Technology, 2025)

Inter-granular damage in experimentally deformed rock-salt investigated by X-ray micro-tomography: confining pressure and brine effects - Nina Du; Michel Bornert; Alexandre Dimanov; Patrick Aimedieu; Laura Blanco-Martín; Jubier A. Jiménez-Camargo (Journal of Structural Geology, 2025)

The legacy and future of multiple anthropogenic stressors: Organohalogen compounds in the vulnerable Guiana dolphin (Sotalia guianensis) - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Monizze Vannuci-Silva; Adriana Castaldo Colosio; Hernani Gomes da Cunha Ramos; Ian Augusto Gusman Cunha; Lupércio Araújo Barbosa; Ana Paula Cazerta Farro; Drienne Messa Faria; Haydée A. Cunha; Tatiana L. Bisi; et al. (Journal of Hazardous Materials, 2025)

Effects of grassland community composition and digestate fertiliser on nitrous oxide emissions from soil - Ali S. Khan; John A. Finn; Alexandre B. de Menezes; Dominika J. Krol (Journal of Environmental Management, 2025)

Screening for Viruses in Pallas’s Long-Tongued Bats (Glossophaga soricina) in Brazil - Alexandre Sita; Gabriela E. Birlem; Deivid S. da Silva; Larissa Mallmann; Meriane Demoliner; Mariana S. da Silva; Juliana S. Gularte; Vyctoria M. A. G. Pereira; Paula R. de Almeida; Alana W. Hansen; André A. Witt; Juliane D. Fleck; et al. (Journal of Molecular Evolution, 2025)

Humidity Control and Its Implications in the Storage of Apples and Pears: A Review - Robert K. Prange; A. Harrison Wright; Barbara J. Daniels-Lake; Daniel Alexandre Neuwald; Dirk Köpcke; Luiz Carlos Argenta (Applied Fruit Science, 2025)
At harvest, the water content of apples and pears is at its maximum, about 83–85% by mass. The rate of fruit water loss after harvest is a function of three factors: the fruit surface area, the epidermis water vapour permeance, and the difference in internal and external fruit water vapour pressure. However, the water vapour pressure difference is the only factor that can be controlled during storage, i.e. by altering the storage humidity. Curiously, most publications on apple and pear storage do not discuss storage humidity even though the postharvest quality of both depends largely upon it. Apples and pears can experience up to ~ 2% mass loss without loss of commercial value, but further mass loss creates visible shrivelling, and may also increase bitter pit, depending on the cultivar. The prevailing commercial advice has been to minimise mass loss by maximising the relative humidity at the chosen storage temperature. However, this advice should be re-evaluated, and humidity management protocols revised, from minimising mass loss to optimising mass loss. Growing evidence indicates that storage humidity affects the postharvest performance of apples and pears. A review of the literature over the last 100 years shows that some mass loss, achieved by lowering storage atmosphere humidity, can improve apple and pear quality by reducing non-bitter pit disorders, bruising, respiration, ethylene production and decay, especially if the mass loss occurs at the beginning of storage. The effects of mass loss on calcium-related disorders suggest that mass loss may affect postharvest calcium redistribution in the fruit. The fruit mass loss for refrigerated air and controlled atmosphere rooms can be estimated by collecting the defrost water from the refrigeration cooling coils and expressing this as a percentage of the initial total mass of fruit in the room. A ‘2-in-2’ guideline (up to 2% mass loss in the first 2 months) is proposed, but further research is needed to refine this guidance, especially for cultivars that may benefit from greater mass loss without increasing shrivelling or bitter pit.

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Exogenous enzyme supplementation for beef cattle under different nutritional strategies during the rainy season: Performance and Metabolism - Cibeli A. Pedrini; Anderson P. Acosta; Alexandre Perdigão; Victor V. Carvalho; Tiago S. Acedo; Erika R.S. Gandra; Rafael H.B.T. Goes; Jefferson R. Gandra (Livestock Science, 2025)

Diverse sulfate- and sulfur intermediate- reducing bacteria contributing to annually expanding water anoxia in an oil sands pit lake - Yunyun Yan; James L.S. Arrey; Rui Zhang; Tara Colenbrander-Nelson; Lauren E. Twible; Alexandre Poulain; Lesley A. Warren (Journal of Hazardous Materials, 2025)

Niche specialization modeling and potential occurrence of pest species within the rice stink bug complex in the Americas: to each his own? - Juliana L. Vieira; Thiago L. Costa; Abraão A. Santos; Kevin Maebe; José Alexandre F. Barrigossi; Guy Smagghe; Raul Narciso C. Guedes (Journal of Pest Science, 2025)

Predicting the impact of the urban texture on the Urban Heat Island intensity using Machine Learning: The case for the Iberian Peninsula - Josep A. Ferré; Anton Vernet; Alexandre Fabregat (Urban Climate, 2025)

Miocene marine vertebrate trophic ecology reveals megatooth sharks as opportunistic supercarnivores - Jeremy McCormack; Iris Feichtinger; Benjamin T. Fuller; Klervia Jaouen; Michael L. Griffiths; Nicolas Bourgon; Harry Maisch; Martin A. Becker; Jürgen Pollerspöck; Oliver Hampe; Gertrud E. Rössner; Alexandre Assemat; et al. (Earth and Planetary Science Letters, 2025)

Eat First, Fight Later: Competitive Advantage of an Invasive Cichlid over a Native Competitor for Food Resources - Leonardo Cirillo; Caio A. Miyai; Fábio H. C. Sanches; Alexandre L. Arvigo; Tânia M. Costa (Fishes, 2025)
Competition for resources with invasive species can negatively impact native fauna. Invasive species often exhibit higher aggressiveness and monopolize resources through behavioral interference. However, their feeding behavior also plays a central role in invasion success. We investigated how food resource availability influences agonistic interactions between the invasive cichlid Oreochromis niloticus and the native cichlid Geophagus iporangensis. Specifically, we assessed whether the invasive species interferes with the native species’ feeding behavior. Using neutral arenas, we staged competition trials under two conditions: initially without food and subsequently with food present. The native species served as the focal animal and was exposed to either a conspecific or an invasive competitor. Results showed that native species aggressiveness toward the invasive competitor was three times higher in the absence of food. Although O. niloticus was 1.6 times more aggressive than conspecifics, its presence did not affect the native species’ feeding rate, and no behavioral interference was observed. Instead, the invasive species relied primarily on scramble competition, initiating nine of ten trials and consuming seven times more food than the native cichlid. Our findings suggest that, beyond aggression, feeding behavior and resource exploitation are key mechanisms driving competitive exclusion by invasive species.

Barbatimão bark as an alternative to sodium lasalocid in finishing diets for lambs: Carcass characteristics and meat quality - Aylpy R.D. Santos; Cristiane R. Barbosa; Carla G. Souza; Tatiane Fernandes; Renata A. Chagas; Samuel R. Navarro; Alexandre R.M. Fernandes; Fernando M. Vargas Junior (Meat Science, 2025)

Faecal microbial profiles of Angus beef cattle with divergent immune responses - Brianna N. Maslen; Brad C. Hine; Christian Duff; Pamela A. Alexandre; Sam A. Clark; Julius van der Werf; Jason D. White; Sameer D. Pant (Livestock Science, 2025)

Unlocking biochemical profile of Chaetoceros calcitrans, Cylindrotheca fusiformis, and Nannofrustulum shiloi (Bacillariophyta) for nutritional and added-value applications - Ana S.P. Moreira; Helena R. Rocha; Susana Aveiro; Andreia S. Ferreira; Kayane Oliveira; Alexandra Conde; Marta Coelho; Alexandre M.C. Rodrigues; Natacha Coelho; Hugo Pereira; Ana Gomes; Manuela Pintado; et al. (Algal Research, 2025)

Microplastic contamination and biological alterations in Atlantic wild fish populations, and human health risks associated to fillet consumption - Sara C. Lourenço; Alexandre A.M.R.A. Aleluia; L. Gabriel A. Barboza; Xosé L. Otero; Sara C. Cunha; José O. Fernandes; Lúcia Guilhermino (Marine Environmental Research, 2025)

Harnessing genotype and phenotype data for population-scale variant classification using large language models and bayesian inference - Toby R. Manders; Christopher A. Tan; Yuya Kobayashi; Alexander Wahl; Carlos Araya; Alexandre Colavin; Flavia M. Facio; Hillery Metz; Jason Reuter; Laure Frésard; Samskruthi R. Padigepati; David A. Stafford; et al. (Human Genetics, 2025)

Maternal malnutrition induces inflammatory pathways and oxidative stress in the dorsolateral prostate of male offspring rats - Renato Mattos; Matheus Naia Fioretto; Sérgio Alexandre Alcantara dos Santos; Isabelle Tenori Ribeiro; Maycon Tavares Emílio-Silva; Luiz Marcos Frediani Portela; Clélia Akiko Hiruma Lima; Fabio Rodrigues Ferreira Seiva; Luis A. Justulin (Biogerontology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Ecological Specialisation of Reef Fishes Peaks in Global Biodiversity Hotspots - Zoé Delecambre; Renato A. Morais; Alexandre C. Siqueira; Emma Paul Costesec; Caroline E. Dubé; Sergio R. Floeter; Alan M. Friedlander; Fabien Leprieur; Yves Letourneur; Lucas T. Nunes; Jordan M. Casey; Valeriano Parravicini (Global Ecology and Biogeography, 2025)
Aim The role of ecological specialisation in shaping biogeographic and evolutionary patterns remains unresolved. To date, few studies have quantitatively examined consumer niche breadth at a global scale. We describe global biogeographic and diversification patterns of specialisation, measured using trophic and thermal niches, for a highly diverse assemblage of consumers: reef fishes. First, we investigated the confluence of specialisation with global biogeographic patterns in species richness and reef area. Then, we tested whether these patterns could be explained by differences in diversification rates and geographic ranges. Location Tropical reefs across the globe. Time Period Present. Major Taxa Studied Reef fishes. Methods To estimate trophic specialisation, we compiled a comprehensive dataset on reef fish trophic interactions from published gut content analyses, including dietary information for ~5000 individuals across 387 fish species. We used the geographic range of species and global temperature data to estimate thermal specialisation of reef fishes. We used distributional data and Bayesian Structural Equation Modelling to test for the correlation between biogeographic variables, species richness, and the prevalence of trophic or thermal specialisation in reef fish assemblages. Moreover, we used linear models to test for a correlation between reef fish diversification rates, geographic range, and their degree of trophic and thermal specialisation. Results Our analysis suggests that species richness is positively associated with trophic specialisation in reef fishes, with isolated and species‐depauperate communities supporting assemblages dominated by trophic and thermal generalists. We found no effect of trophic and thermal specialisation on diversification rates and geographic range at the species level. Main Conclusions Our findings indicate that specialisation is favoured in large, biodiversity‐rich regions, but specialists might show lower capacity for colonisation, with lower representation on smaller, isolated reefs. These results contribute to our understanding of the dynamics shaping fish biogeography on coral reefs.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Strengthening Rigor and Reproducibility in Epigenome-Wide Association Studies of Social Exposures and Brain-Based Health Outcomes - Brooke G. McKenna; Alexandre A. Lussier; Matthew J. Suderman; Esther Walton; Andrew J. Simpkin; Anke Hüls; Erin C. Dunn (Current Environmental Health Reports, 2025)

Spatial distribution and aggregation patterns of Triozoida limbata immatures in guava cultivars: implications for targeted pest management strategies - Isaias de Oliveira; Manoel A. Uchoa; Marcos Gino Fernandes; Odival Faccenda; Thiago Alexandre Mota; Inessa Steffany Torres de Oliveira (International Journal of Tropical Insect Science, 2025)

Potentiating-antibiotic and antibacterial properties of Luetzelburgia auriculata (ALLEMÃO) Ducke against MDR bacterial strains - Thiago S. Freitas; Janaina E. Rocha; Marcos J. F. Lima; Carla F. A. Nonato; Cicera J. Camilo; Cicera L. R. Paulo; Maria A. S. Alencar; Isaac M. Araújo; Karla S. T. G. Belém; Selvina P. Silva; Francisco N. Pereira Junior; Hélcio S. Santos; et al. (Vegetos, 2025)

Impact of a bimodal dust distribution on the 2018 Martian global dust storm with the NASA Ames Mars global climate model - Richard A. Urata; Tanguy Bertrand; Melinda A. Kahre; R. John Wilson; Alexandre M. Kling; Michael J. Wolff (Icarus, 2025)

Integrating socio-economic variables in urban flood damage assessments: a case study of Bengaluru, India - Abhishek A. Pathak; Apoorva R. Mathad; Alexandre S. Gagnon (Natural Hazards, 2025)

New experimental constraints on seismic velocities and densities across the $$α $$–$$β $$ quartz transition at deep crustal conditions - Giulia Mingardi; Julien Gasc; Matteo Ardit; Ross J. Angel; Wilson A. Crichton; Dmitrii Druzhbin; Jerome Aubry; Alexandre Schubnel; Matteo Alvaro (Contributions to Mineralogy and Petrology, 2025)
At the pressure and temperature conditions of the lower crust, quartz undergoes a displacive phase transition from a trigonal ( $$α $$ ) to a hexagonal phase ( $$β $$ ). At room pressure, the $$α $$ – $$β $$ quartz transition occurs at 574.1 °C and it is associated with large changes in the thermodynamic and elastic properties. For that reason, it is interpreted as the cause of significant seismic velocity contrasts in the crust seen by seismic tomography. Existing thermodynamic models and Equations of State (EoS) of quartz are mostly constrained by data collected at room pressure (or at high pressure and room temperature). In this work we characterized the $$α $$ – $$β $$ quartz transition experimentally at simultaneous HP – HT conditions using synchrotron X-ray diffraction and acoustic measurements, and derived values of $$V_p$$ , $$V_s$$ , the adiabatic bulk modulus ( $$K_s$$ ) and the shear modulus ( G ). The data collected in the $$α $$ field agree with the models from the literature, so entrapment pressures of $$α $$ -quartz inclusions calculated via elastic barometry with these EoS should be reliable. However, our measured $$V_p$$ , $$V_s$$ , and $$K_s$$ are significantly lower than those predicted for $$β $$ -quartz. Whatever the cause of this discrepancy, interpretations of seismic data in terms of the properties of $$β $$ -quartz in the lower crust and calculations of entrapment conditions of quartz inclusions in the stability field of $$β $$ -quartz should be treated with caution.

Multiyear temperature variation in tropical mountain peatlands from the southern Espinhaço Mountain Range in Brazil - Diego Tassinari; Cristiano Christofaro; Uidemar M. Barral; Camila R. Costa; Thiago A. A. Pinto; William J. Do Carmo; Bárbara P. C. Silva; Érica P. Cardozo; Alexandre C. Silva (Journal of Mountain Science, 2025)

Using eDNA to Supplement Population Genetic Analyses for Cryptic Marine Species: Identifying Population Boundaries for Alaska Harbour Porpoises - Kim M. Parsons; Samuel A. May; Zachary Gold; Marilyn Dahlheim; Christine Gabriele; Janice M. Straley; John R. Moran; Kimberly Goetz; Alexandre N. Zerbini; Linda Park; Phillip A. Morin (Molecular Ecology, 2025)
Isolation by distance and biogeographical boundaries define patterns of population genetic structure for harbour porpoise along the Pacific coast from California to British Columbia. Until recently, inadequate sample sizes in many regions constrained efforts to characterise population genetic structure throughout the coastal waters of Alaska. Here, tissue samples from beachcast strandings and fisheries bycatch were supplemented with targeted environmental DNA (eDNA) samples in key regions of Alaska coastal and inland waters. Using a geographically explicit, hierarchical approach, we examined the genetic structure of Alaska harbour porpoises, using both mitochondrial DNA (mtDNA) sequence data and multilocus SNP genotypes. Despite a lack of evidence of genetic differentiation from nuclear SNP loci, patterns of relatedness and genetic differentiation from mtDNA suggest natal philopatry at multiple geographic scales, with limited gene flow among sites possibly mediated by male dispersal. A priori clustering of sampled areas at an intermediate scale (eastern and western Bering Sea, Gulf of Alaska and Southeast Alaska) best explained the genetic variance (12.37%) among regions. In addition, mtDNA differentiation between the Gulf of Alaska and eastern Bering Sea, and among regions within the Gulf of Alaska, indicated significant genetic structuring of harbour porpoise populations in Southeast Alaska. The targeted collection of eDNA samples from strata within Southeast Alaska was key for elevating the statistical power of our mtDNA dataset, and findings indicate limited dispersal between neighbouring strata within coastal and inland waters. These results provide evidence supporting a population boundary within the currently recognised Southeast Alaska Stock. Together, these findings will prove useful for ongoing management efforts to reduce fisheries conflict and conserve genetic diversity in this iconic coastal species.

Relief determines patterns of structure and composition of tree vegetation in seasonal forests in the Brazilian Cerrado - Maxwell R. Oliveira; Francielli Bao; Evaldo B. Souza; Arnildo Pott; Rosa H. Silva; Pedro Isaac; Joanice Lube Battilani; Vivian Ribeiro Baptista Maria; Edna Scremin-Dias; Vali Joana Pott; Alexandre de Matos Martins Pereira; Geraldo A. Damasceno Junior (Brazilian Journal of Botany, 2025)

Soybean2035: A decadal vision for soybean functional genomics and breeding - Zhixi Tian; Alexandre Lima Nepomuceno; Qingxin Song; Robert M. Stupar; Bin Liu; Fanjiang Kong; Jianxin Ma; Suk-Ha Lee; Scott A. Jackson (Molecular Plant, 2025)

Using δ65Cu and δ34S to determine the fate of copper in stream waters draining porphyry mineralization: Implications for exploration targeting - James A. Kidder; Christopher E. Beckett-Brown; Alexandre Voinot; Zhaoping Yang; Pierre Pelchat; Duane C. Petts; Matthew Polivchuk; John B. Chapman; Scott Casselman; Matthew I. Leybourne (Chemical Geology, 2025)

Cannabidiol-Induced Autophagy Ameliorates Tau Protein Clearance - Talita A. M. Vrechi; Gabriel C. Guarache; Rafaela Brito Oliveira; Erika da Cruz Guedes; Adolfo G. Erustes; Anderson H. F. F. Leão; Vanessa C. Abílio; Antonio W. Zuardi; Jaime Eduardo C. Hallak; José Alexandre Crippa; Claudia Bincoletto; Rodrigo P. Ureshino; et al. (Neurotoxicity Research, 2025)
Tau is a neuronal protein that confers stability to microtubules; however, its hyperphosphorylation and accumulation can lead to an impairment of protein degradation pathways, such as autophagy. Autophagy is a lysosomal catabolic process responsible for degrading cytosolic components, being essential for cellular homeostasis and survival. In this context, autophagy modulation has been postulated as a possible therapeutic target for the treatment of neurodegenerative diseases. Studies point to the modulatory and neuroprotective role of the cannabinoid system in neurodegenerative models and here it was investigated the effects of cannabidiol (CBD) on autophagy in a human neuroblastoma strain (SH-SY5Y) that overexpresses the EGFP-Tau WT (Wild Type) protein in an inducible Tet-On system way. The results demonstrated that CBD (100 nM and 10 µM) decreased the expression of AT8 and total tau proteins, activating autophagy, evidenced by increased expression of light chain 3-II (LC3-II) protein and formation of autophagosomes. Furthermore, the cannabinoid compounds CBD, ACEA (CB1 agonist) and GW-405,833 (CB2 agonist) decreased the fluorescence intensity of EGFP-Tau WT; and when chloroquine, an autophagic blocker, was used, there was a reversal in the fluorescence intensity of EGFP-Tau WT with CBD (1 and 10 µM) and GW-405,833 (2 µM), demonstrating the possible participation of autophagy in these groups. Thus, it was possible to conclude that CBD induced autophagy in EGFP-Tau WT cells which increased tau degradation, showing its possible neuroprotective role. Hence, this study may contribute to a better understanding of how cannabinoids can modulate autophagy and present a potential therapeutic target in a neurodegeneration model. Graphical Abstract

Morphology and genetics of non-topotypes Pimelodus platicirris catfish suggest synonymy with P. maculatus - Rafael A. Baggio; Vinicius Abilhoa; Grazielle H. F. de Menezes; Emanuel Razzolini; Ana Carolina Lacerda Rego; Átila Rodrigues de Araújo; Mateus Moreira de Carvalho; Alexandre L. Godinho (Conservation Genetics, 2025)

Assessing water quality restoration measures in Lake Pampulha (Brazil) through remote sensing imagery - Alexandre Assunção; Talita F. G. Silva; Lino A. S. de Carvalho; Brigitte Vinçon-Leite (Environmental Science and Pollution Research, 2025)

Epilithic algal composition and the functioning of Anthropocene coral reefs - Sterling B. Tebbett; Michael J. Emslie; Michelle J. Jonker; Scott D. Ling; Morgan S. Pratchett; Alexandre C. Siqueira; Angus A. Thompson; Helen F. Yan; David R. Bellwood (Marine Pollution Bulletin, 2025)

Beyond the threshold - Different accumulation of organochlorine compounds in common dolphins (Delphinus delphis) inhabiting continental and insular ecosystems in the Northeast Atlantic - Raul Valente; Nara de Oliveira-Ferreira; Rita Ferreira; Ana M. Correia; Bárbara M.R. Manhães; Ágatha Gil; Annalisa Sambolino; Elitieri B. Santos-Neto; L. Filipe C. Castro; Haydée A. Cunha; Alexandre F. Azevedo; Ana Dinis; et al. (Environmental Pollution, 2025)

17O-excess of grass leaf phytoliths across the North American prairies records late-growing season daytime relative humidity - Minger Guo; Anne Alexandre; Fred J. Longstaffe; Christophe Peugeot; Elizabeth A. Webb (Chemical Geology, 2025)

Small-scale fisheries in ecologically sensitive areas in Latin America and the Caribbean: Do marine protected areas benefit fisheries governance? - Ana Cinti; Luisa Ramirez; Mauricio Castrejón; Jaime A. Aburto; Luciana Loto; Stuart Fulton; Mario Rueda; Alexandre Schiavetti; Francisco J. Fernández-Rivera Melo; Manuel Bravo; Daniela Trigueirinho Alarcon; Valéria Penchel Araújo; et al. (Ambio, 2025)
Many small-scale fisheries (SSFs) in Latin America and the Caribbean (LAC) operate in ecologically sensitive areas, where balancing conservation and resource use is challenging. 'Multiple-use' marine protected areas (MPAs) have been implemented to accommodate SSFs (among other uses) within areas designated for conservation, creating opportunities and challenges for SSF governance. We analyzed eleven case studies from LAC to explore: (1) how different MPA institutional designs affect key aspects of SSF governance and (2) the links between these effects and the type of initiative that promoted MPA establishment (origin). Results indicate that the existence of an MPA benefited SSF governance in many ways, with more pronounced positive effects in MPAs with mixed to bottom-up origin supported by well-organized fishing groups. In addition, the presence of supportive MPA authorities that leveraged local capacities and initiatives and adopted flexible and collaborative governance systems made a difference in several cases. Lessons for integrating MPA and SSF governance are drawn.

A hint on the unknown diversity of eastern Andes: high endemicity and new species of mammals revealed through DNA barcoding - Silvia E. Pavan; Edson F. Abreu; Pamela Y. Sánchez-Vendizú; Romina Batista; Roberta A. Murta-Fonseca; Renzo Pradel; Edgardo M. Rengifo; Mariela Leo; Víctor Pacheco; Alexandre Aleixo; Alexandre R. Percequillo; Pedro Peloso (Systematics and Biodiversity, 2024)

Comprehensive characterization of European house dust contaminants: Concentrations and profiles, geographical variability, and implications for chemical regulation and health risk - Peter Haglund; Nikiforos A. Alygizakis; Adrian Covaci; Lisa Melymuk; Pernilla Bohlin Nizzetto; Pawel Rostkowski; Alexandre Albinet; Sylvana Alirai; Dagny Aurich; Stefan Bieber; Ana Ballesteros-Gómez; Amanda A. Brennan; et al. (Science of The Total Environment, 2024)

Aerobic performance in rats subjected to incremental-speed running exercise: A multiple regression analysis study emphasizing thermoregulation-related variables - Marcelo T. Andrade; Nicolas H.S. Barbosa; Roberto C.S. Souza-Junior; Cletiana G. Fonseca; William C. Damasceno; Kássya Regina-Oliveira; Lucas R. Drummond; Myla A. Bittencourt; Ana C. Kunstetter; Pedro V.R. Andrade; Alexandre S.R. Hudson; Thales N. Prímola-Gomes; et al. (Journal of Thermal Biology, 2024)

Green solvent γ-Valerolactone as a sustainable alternative for the production of polymeric membranes for pharmaceutically active compounds (PhACs) removal from water - Andreza P. Cardoso; Alexandre Giacobbo; Andréa M. Bernardes; Carlos A. Ferreira (Journal of Environmental Chemical Engineering, 2024)

Diel movement patterns in nominally nocturnal coral reef fishes (Haemulidae and Lutjanidae): Intra vs. Interspecific variation - William P. Collins; David R. Bellwood; Renato A. Morais; Nathan J. Waltham; Alexandre C. Siqueira (Coral Reefs, 2024)
Movement of animals, habitat connectivity, and nutrient transport are key elements in the ecological functioning of coral reef ecosystems. However, most studies have focused on the diurnal component of these aspects; nocturnal patterns are less known. Our study aims to address this knowledge gap by assessing diel movement patterns in ecologically and commercially important nocturnal coral reef fishes. We evaluate 122-days of acoustic telemetry data from 4 nocturnal species in 2 coral reef fish families (Haemulidae and Lutjanidae) on the Great Barrier Reef. For all species, we found a clear division between daytime resting areas on the reef and a move towards off-reef areas at night. This was highlighted in the low number of detections at night and the high average transitions between receivers at twilight. Over our study period, average nocturnal space use area (minimum convex polygon) of Plectorhincus gibbosus was 328,089 m 2 , Plectorhincus lineatus 28,828 m 2 , and Lutjanus carponotatus 20,369 m 2 . However, results from a Principal Component Analysis revealed that space use, and movement, varied substantially within species; for 3 of the 4 species the main axis of variation correlated with individual-level behaviour. These large differences in individual space use patterns highlight the need for caution when using species averages when considering ecosystem functions. Overall, our preliminary observations provide a glimpse into the large spatial extent, potential habitat connectivity, and intra and interspecific variation in activity patterns among large nocturnal Indo-Pacific reef fishes. This highlights their potential importance in maintaining ecosystem links between coral reefs and adjacent habitats.

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Assessing South Indian Ocean tropical cyclone characteristics in HighResMIP simulations - Pardeep Pall; Alexandre S. Gagnon; Massimo A. Bollasina; Colin M. Zarzycki; Yuner Huang; Christopher T. S. Beckett; Harinaivo Ramanantoanina; Thomas P. S. Reynolds (International Journal of Climatology, 2024)
Several damaging tropical cyclones (TCs) have occurred recently over the South Indian Ocean (SIO) region, causing enormous social and economic losses. Yet, while many studies have examined SIO TC characteristics using observations and reanalysis, only a few have assessed these characteristics specifically for this region in climate models, and fewer have investigated their projections under climate change. Here we do this for a historical (1980–2010) and future (2020–2050) period, using multimodel simulations from the High Resolution Model Intercomparison Project, as well as examine biases in the historical period relative to a reanalysis (ERA5). The models have horizontal resolutions of 25–50 km, which has enabled an improved ability to represent tropical cyclones globally in previous studies. TempestExtremes software is employed to detect tropical storm and cyclone tracks. In cases where TempestExtremes cannot be applied due to a lack of requisite variables in a dataset, we instead examine extreme wind speeds in that dataset. For the historical period, we find considerable variation in model biases compared to ERA5, which itself exhibits realistic spatial patterns of tracks and their monthly distribution. Models do at least agree on positive biases in track frequency east of Madagascar and somewhat in the Mozambique Channel. However, the models and ERA5 only produce Category 3 tropical cyclones at best. Wind speeds for 25 km resolution models have much larger positive biases than for 50 km ones, suggesting the former can simulate even higher‐category tropical cyclones. Considerable intermodel variation is also found in track changes between the future and historical periods. No systematic intercategory pattern of change exists, and low signal‐to‐noise may obscure any such patterns in the limited timespan of available data. Thus, no meaningful conclusions can be drawn regarding changes in track intensity. Nevertheless, track frequency broadly decreases across models for the region, as does accumulated cyclone energy. An east‐to‐west shift in track location from east of Madagascar toward the Mozambique Channel is also implied by track frequency and wind speed changes. Our findings provide information to potentially improve storm resiliency in this vulnerable region.

Relationships between radiation, wildfire and the soil microbial communities in the Chornobyl Exclusion Zone - Alexandre Barretto de Menezes; Sergii Gashchak; Michael D. Wood; Nicholas A. Beresford (Science of The Total Environment, 2024)

Are microplastics a new cardiac threat? A pilot study with wild fish from the North East Atlantic Ocean - Luís Gabriel A. Barboza; Sara Couto Lourenço; Alexandre Aleluia; Giovanni Paolo Senes; Xosé L. Otero; Lúcia Guilhermino (Environmental Research, 2024)

Molecular events accompanying aggregation-induced energy quenching in fucoxanthin-chlorophyll proteins - Maxime T.A. Alexandre; Tjaart P.J. Krüger; Andrew A. Pascal; Vasyl Veremeienko; Manuel J. Llansola-Portoles; Kathi Gundermann; Rienk van Grondelle; Claudia Büchel; Bruno Robert (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Turbidity-based scaling detection system for batch reverse osmosis combined with gypsum crystal recovery - Alexander M. Schwiebert; John A. Bush; Alexandre Bray; Ivan Reyes; Agusberto Cortijo; Hans Portilla; Pablo García-Chevesich; Christopher Bellona; Tzahi Y. Cath; Johan Vanneste (Desalination, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Within-well patterns in bigeye tuna catch composition and implications for purse-seine port-sampling and catch estimation for the Eastern Pacific Ocean - Cleridy E. Lennert-Cody; Cristina De La Cadena; Marti McCracken; Luis Chompoy; Nickolas W. Vogel; Mark N. Maunder; Brad A. Wiley; Ernesto Altamirano Nieto; Alexandre Aires-da-Silva (Fisheries Research, 2024)

Recent deep-sea nematodes and agglutinated foraminifera select specific grains and bioclasts from their environments: Ecological implications - Sunil K. Das; Raj K. Singh; Mariem Saavedra-Pellitero; Julia Gottschalk; Carlos A. Alvarez Zarikian; Lester Lembke-Jene; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; Chandranath Basak; Anieke Brombacher; et al. (Marine Micropaleontology, 2024)

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Joining forces to fight wildfires: Science and management in a protected area of Pantanal, Brazil - Patrícia S. Silva; Julia A. Rodrigues; Joana Nogueira; Livia C. Moura; Alexandre Enout; Cristina Cuiabália; Carlos C. DaCamara; Allan A. Pereira; Renata Libonati (Environmental Science & Policy, 2024)

Protist communities as indicators of fertilization-induced changes in a species-rich grassland ecosystem - Shuo Sun; Alexandre Jousset; Stefan Geisen; Enrique Lara; Pengfei Zhang; Rong Li; Francisco Dini-Andreote; Mohammadhossein Ravanbakhsh; Qirong Shen; George A. Kowalchuk; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Drivers of seasonal rainfall variability over the Angolan and Namibian plateaus - Carlos A. Pereira; João P. Martins; Andreas H. Fink; Joaquim G. Pinto; Alexandre M. Ramos (International Journal of Climatology, 2024)
Southern Africa has been strongly affected by ongoing climate change in recent decades. Rainfall variability is modulated by regional patterns of moisture advection and convergence in the lower troposphere. Using reanalysis, ground and satellite‐based rainfall products and observations from 10 weather stations, we perform a synoptic and climatological analysis focussing on atmospheric circulation, moisture transport and their relationship with rainfall anomalies over the Angolan and Namibian Plateau region. Results clearly show that a stronger (weaker) Zambezi low level jet (LLJ) magnitudes are associated with above (below) normal rainfalls over the main Angolan and Namibian plateaus. With lower confidence, a stronger Limpopo LLJ may also lead to enhanced rainfall over Namibia and southeast Angola. The Zambezi LLJ moisture fluxes are moderately controlled by Mozambique Chanel Trough and Angola Low intensities, while the Limpopo LLJ intensities have very low influence from the Mozambique Chanel Trough and Angola Low, respectively. The Angola Low in its tropical phase is associated with deeper moisture convergence and stronger vertical velocities, leading to higher amounts of precipitable water within the air column, thus enhancing precipitation over the region. It is shown that the major moisture source of rainfall, which is advected to via the Zambezi LLJ, is the Indian Ocean. Meanwhile, the Atlantic Ocean plays a minor role. Given the current lack of observations and projected climate change, further research and investments are urgently needed in the region, for example, regarding the expansion of the surface data network.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Microcystin-degrading bacteria reduce bioaccumulation in Fragaria vulgaris and enhance fruit yield and quality - Mohammed Haida; Fatima El Khalloufi; Yasser Essadki; Diogo A. M. Alexandrino; Richard Mugani; Abdessamad Hejjaj; Alexandre Campos; Vitor Vasconcelos; Maria F. Carvalho; Leticia Díez-Quijada; Ana M. Cameán; Brahim Oudra (Environmental Science and Pollution Research, 2024)
In Morocco, red fruit production has thrived, primarily utilizing hydroponic methods to control crops, increase fruit yield and quality, and avoid soil-related problems. However, the irrigation of these expansive hydroponic farms relies heavily on water sourced from dams, many of which are contaminated with Microcystins (MCs). To address this contamination issue, ongoing research is focused on discovering effective and cost-efficient biological solutions for eliminating MCs. In this study, we isolate and identify bacterial strains capable of degrading MCs, evaluate the rate of degradation, and investigate how soil inoculated with these bacteria affects the accumulation of MCs in plant tissue. The partial 16S rRNA analyses of three bacterial sequences were conducted, identifying them through NCBI as follows: Ensifer sp. (B1) isolated from soil, Shinella sp. (B2) from a cyanobacterial bloom, and Stutzerimonas sp. (B3) from water. These bacteria exhibited the ability to degrade MCs, with approximately 34.75%, 73.75%, and 30.1% of the initial concentration (20 µg/L) being removed after a 6-day period for B1, B2, and B3, respectively. Moreover, strawberry plants were cultivated hydroponically in a greenhouse for a duration of 90 days. These plants were subjected to extracts of cyanobacteria containing 10 and 20 µg/L of Microcystins (MC), as well as water from an artificial lake contaminated with MC, both with and without the presence of isolated bacterial strains. Among these strains, Shinella sp. exhibited the highest efficacy in mitigating MC accumulation. Specifically, it resulted in a reduction of approximately 1.159 µg of MC per kilogram of root dry weight, leading to complete elimination in the leaves and fruits. The findings also indicated that the inoculation of perlite with the three MC-degrading bacterial strains significantly enhanced growth, photosynthetic pigments, yield, biochemical constituents, and quality attributes of strawberries (p ≤ 0.05). These promising outcomes suggest the potential of this approach for addressing the adverse impacts of crops irrigated with MC-contaminated water in future agricultural practices.

Late Miocene to Early Pliocene paleoceanographic evolution of the Central South Pacific: A deep-sea benthic foraminiferal perspective - Sunil K. Das; N. Mahanta; B. Sahoo; Raj K. Singh; Carlos A. Alvarez Zarikian; Manish Tiwari; Nishant Vats; Nihal; Frank Lamy; Gisela Winckler; Jennifer L. Middleton; Helge W. Arz; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Brine-granite interaction and lithium leaching in a continental rift (Soultz-sous-Forêts, Rhine Graben, France) - Elza J.M. Dugamin; Marie-Christine Boiron; Michel Cathelineau; Antonin Richard; Chantal Peiffert; Alexandre Lebreton; David A. Banks; Frank Despinois (Lithos, 2024)

Sigmoid allometries generate male dimorphism in secondary sexual traits: a comment on Packard (2023) - Bruno A. Buzatto; Glauco Machado; Alexandre V. Palaoro (Evolutionary Ecology, 2024)

Follicular DNA Damage and Pesticide Exposure Among Latinx Children in Rural and Urban Communities - Cassandra Lepetit; Mohamed Gaber; Ke Zhou; Haiying Chen; Julia Holmes; Phillip Summers; Kim A. Anderson; Richard P. Scott; Carey N. Pope; Kirstin Hester; Paul J. Laurienti; Sara A. Quandt; et al. (Exposure and Health, 2024)
The intersectional risks of children in United States immigrant communities include environmental exposures. Pesticide exposures and their biological outcomes are not well characterized in this population group. We assessed pesticide exposure and related these exposures to DNA double-strand breaks (DSBs) in Latinx children from rural, farmworker families (FW; N = 30) and from urban, non-farmworker families (NFW; N = 15) living in North Carolina. DSBs were quantified in hair follicular cells by immunostaining of 53BP1, and exposure to 72 pesticides and pesticide degradation products were determined using silicone wristbands. Cholinesterase activity was measured in blood samples. DSB frequencies were higher in FW compared to NFW children. Seasonal effects were detected in the FW group, with highest DNA damage levels in April–June and lowest levels in October–November. Acetylcholinesterase depression had the same seasonality and correlated with follicular DNA damage. Organophosphate pesticides were more frequently detected in FW than in NFW children. Participants with organophosphate detections had increased follicular DNA damage compared to participants without organophosphate detection. Follicular DNA damage did not correlate with organochlorine or pyrethroid detections and was not associated with the total number of pesticides detected in the wristbands. These results point to rural disparities in pesticide exposures and their outcomes in children from vulnerable immigrant communities. They suggest that among the different classes of pesticides, organophosphates have the strongest genotoxic effects. Assessing pesticide exposures and their consequences at the individual level is key to environmental surveillance programs. To this end, the minimally invasive combined approach used here is particularly well suited for children.

Antibacterial and Antibiofilm Activity of Croton urticifolius Lam. Essential Oil Via Membrane Disruption - Ellen Araújo Malveira; Aluska Kelly A. Nunes; Alexandre Lopes Andrade; Gabriel Lucas Carvalho Melo; Wildson Max Barbosa da Silva; Selene Maia de Morais; Hélcio Silva dos Santos; Leandro Bezerra de Lima; Cynthia Cavalcanti de Albuquerque; Diego Nathan do Nascimento Souza; Edson Holanda Teixeira; Mayron Alves de Vasconcelos (Current Microbiology, 2024)

Lightning-induced fire regime in Portugal based on satellite-derived and in situ data - Lucas S. Menezes; Ana Russo; Renata Libonati; Ricardo M. Trigo; José M.C. Pereira; Akli Benali; Alexandre M. Ramos; Célia M. Gouveia; Carlos A. Morales Rodriguez; Ricardo Deus (Agricultural and Forest Meteorology, 2024)

Correction: Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)

Granzyme B degrades extracellular matrix and promotes inflammation and choroidal neovascularization - Gideon Obasanmi; Manjosh Uppal; Jing Z. Cui; Jeanne Xi; Myeong Jin Ju; Jun Song; Eleanor To; Siqi Li; Wania Khan; Darian Cheng; John Zhu; Lyden Irani; et al. (Angiogenesis, 2024)
Age-related macular degeneration (AMD) is a common retinal neurodegenerative disease among the elderly. Neovascular AMD (nAMD), a leading cause of AMD-related blindness, involves choroidal neovascularization (CNV), which can be suppressed by anti-angiogenic treatments. However, current CNV treatments do not work in all nAMD patients. Here we investigate a novel target for AMD. Granzyme B (GzmB) is a serine protease that promotes aging, chronic inflammation and vascular permeability through the degradation of the extracellular matrix (ECM) and tight junctions. Extracellular GzmB is increased in retina pigment epithelium (RPE) and mast cells in the choroid of the healthy aging outer retina. It is further increased in donor eyes exhibiting features of nAMD and CNV. Here, we show in RPE-choroidal explant cultures that exogenous GzmB degrades the RPE-choroid ECM, promotes retinal/choroidal inflammation and angiogenesis while diminishing anti-angiogenic factor, thrombospondin-1 (TSP-1). The pharmacological inhibition of either GzmB or mast-cell degranulation significantly reduces choroidal angiogenesis. In line with our in vitro data, GzmB-deficiency reduces the extent of laser-induced CNV lesions and the age-related deterioration of electroretinogram (ERG) responses in mice. These findings suggest that targeting GzmB, a serine protease with no known endogenous inhibitors, may be a potential novel therapeutic approach to suppress CNV in nAMD.

A New Species of the Anastrepha pseudoparallela Group (Diptera: Tephritidae) with a Synopsis of the Group in Brazil - Alexandre S. Araújo; Allen L. Norrbom; Roberto A. Zucchi; Marcoandre Savaris (Neotropical Entomology, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Trophic ecology and small‐scale differentiation of ecological groups of franciscana dolphin, Pontoporia blainvillei , in southeastern Brazil, revealed by carbon and nitrogen stable isotopes - Pedro H. O. Teixeira; Gleici Montanini; Ana P. C. Farro; Adriana C. Colosio; Hernani G. C. Ramos; Lupércio A. Barbosa; Ian A. G. Cunha; Maurício Hostim‐Silva; Alexandre F. Azevedo; Haydée A. Cunha; José Lailson‐Brito; Tatiana L. Bisi (Marine Mammal Science, 2024)
The franciscana, Pontoporia blainvillei, is an endemic dolphin off the east coast of South America and is considered the most endangered cetacean in the western South Atlantic. In the present study, we analyzed the muscle tissue of 24 franciscana dolphins found on the coast of Espírito Santo (ES) between 2010 and 2019 to investigate trophic ecology using carbon and nitrogen stable isotope analysis. In addition, 127 prey were analyzed to identify the preferred prey. The most important prey species in the diet of the franciscana dolphins were Trichiurus lepturus , Chirocentrodon bleekerianus , and Pellona harroweri . The franciscana dolphins were grouped into three subareas according to where they were collected throughout the distribution: 1 (North), 2 (Center), and 3 (South). In subarea 1, the preferred prey were Stellifer spp., Isopisthus parvipinnis, and P. harroweri , while in subareas 2 and 3, the prey were similar, changing the order of preference among them ( Stellifer spp., T. lepturus, and C. bleekerianus ). Finally, we identify two possible ecological groups of franciscana dolphins on the coast of ES, influenced by different carbon sources. Our results improve our understanding of the franciscana dolphin's trophic ecology and habitat use, providing new information and guidelines for species conservation in the region.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

A deep learning-based workflow for fast prediction of 3D state variables in geological carbon storage: A dimension reduction approach - Hongsheng Wang; Seyyed A. Hosseini; Alexandre M. Tartakovsky; Jianqiao Leng; Ming Fan (Journal of Hydrology, 2024)

Four-week experimental plus 1-week taper period using live high train low does not alter muscle glycogen content - Danilo R. Bertucci; Carlos Dellavechia de Carvalho; Pedro P. M. Scariot; Carlos A. Kalva-Filho; Gabriel Luches-Pereira; Tarine B. Arruda; Isabela S. Alves; Camila B. Gardim; Marcelo Castiglia; Marcelo Riberto; Claudio Alexandre Gobatto; Marcelo Papoti (European Journal of Applied Physiology, 2024)

In silico investigation of herbicide release from intercalated layered double hydroxides - Sergio R. Tavares; Pedro Ivo R. Moraes; Alexandre A. Leitão (Applied Clay Science, 2024)

Assessing the euryhaline characteristics and metabolic responses of meagre (Argyrosomus regius) when reared under different salinities: Opportunities for aquaculture refinement - Marco F.L. Lemos; Cátia S.E. Silva; Lénia D. Rato; Alexandre F.S. Marques; Ricardo Passos; Irina A. Duarte; Bernardo Duarte; Vanessa F. Fonseca; Sara C. Novais (Aquaculture, 2024)

Scaled mass index derived from aerial photogrammetry associated with predicted metabolic pathway disruptions in free-ranging St. Lawrence Estuary belugas - Meredith Sherrill; Alexandre Bernier-Graveline; Jessica Ewald; Zhiqiang Pang; Michel Moisan; Mathieu Marzelière; Maris Muzzy; Tracy A. Romano; Robert Michaud; Jonathan Verreault (Frontiers in Marine Science, 2024)
The St. Lawrence Estuary (SLE) belugas (Quebec, Canada) are an endangered population whose numbers remain low despite ongoing conservation efforts. Multiple anthropogenic factors and changing environmental conditions are thought to have contributed to the recent 20-year decline in blubber fatty acid concentrations reported in stranded SLE belugas. Despite this evidence that energy reserves within the population are declining, there is currently no method for estimating the body condition of free-ranging animals. The potential metabolic consequences of declining fat reserves have also yet to be explored. The objectives of this study were to use unmanned aerial vehicle (UAV)-based photogrammetry to estimate the scaled mass index (SMI) of free-ranging SLE belugas, and to compare this proxy of body condition to the lipidome of outer-layer blubber samples collected from the same individuals via remote biopsy darting. Morphometric analysis of aerial images ( n = 44 SLE belugas), combined with data collected from animals under professional human care, produced SMI estimates (females: 807 ± 98 kg, males: 743 ± 39 kg) similar in range to those previously calculated for SLE beluga carcasses of known weight. A non-targeted lipidomic analysis followed by pathway enrichment analysis, identified metabolic pathways predicted to show altered activity in association with SMI in the blubber of free-ranging male SLE belugas ( n = 27). Mapping of enriched pathways compared to the Kyoto Encyclopedia of Genes and Genomes (KEGG) metabolic pathways maps, revealed that enriched pathways pertained to the metabolism of multiple lipid classes including fatty acyls and glycerophospholipids. Vitamin A, Vitamin E, and tyrosine metabolism pathways were also enriched in correlation with SMI. This study provides the basis for the development of a non-invasive technique for estimating the body condition of free-ranging SLE belugas and identifies metabolic pathways that merit further exploration to improve our understanding of the potential metabolic impacts of energy loss in cetaceans.

Presence of the neurotoxin β-N-methylamino-L-alanine in irrigation water and accumulation in cereal grains with human exposure risk - Zakaria A. Mohamed; Rehab O. Elnour; Saad Alamri; Mohamed Hashem; Alexandre Campos; Vitor Vasconcelos; Hanan Badawye (Environmental Science and Pollution Research, 2024)

Why does identification matter? Thrips species (Thysanoptera: Thripidae) found in soybean in southern Brazil show great geographical and interspecific variation in susceptibility to insecticides - Luiz F. Warpechowski; Eduardo A. Steinhaus; Rafaella P. Moreira; Daniela N. Godoy; Venicius E. Preto; Luiz E. Braga; Amanda de F. Wendt; Alexandre C. Reis; Élison F.B. Lima; Juliano R. Farias; Oderlei Bernardi (Crop Protection, 2024)

Not seen before. Unveiling depositional context and Mammuthus meridionalis exploitation at Fuente Nueva 3 (Orce, southern Iberia) through taphonomy and microstratigraphy - José Yravedra; Lloyd A. Courtenay; Mario Gutiérrez-Rodríguez; Juan Francisco Reinoso-Gordo; Juha Saarinen; Natalia Égüez; Carmen Luzón; Juan José Rodríguez-Alba; José A. Solano; Stefania Titton; Eva Montilla-Jiménez; José Cámara-Donoso; et al. (Quaternary Science Reviews, 2024)

Intercity connectivity and urban innovation - Xiaofan Liang; César A. Hidalgo; Pierre-Alexandre Balland; Siqi Zheng; Jianghao Wang (Computers, Environment and Urban Systems, 2024)

GIS-FA: an approach to integrating thematic maps, factor-analytic, and envirotyping for cultivar targeting - Maurício S. Araújo; Saulo F. S. Chaves; Luiz A. S. Dias; Filipe M. Ferreira; Guilherme R. Pereira; André R. G. Bezerra; Rodrigo S. Alves; Alexandre B. Heinemann; Flávio Breseghello; Pedro C. S. Carneiro; Matheus D. Krause; Germano Costa-Neto; et al. (Theoretical and Applied Genetics, 2024)

Photo‐identification and satellite telemetry connect southern right whales from South Georgia Island (Islas Georgias del Sur) with multiple feeding and calving grounds in the southwest Atlantic - Amy S. Kennedy; Emma L. Carroll; Alexandre N. Zerbini; C. Scott Baker; Manuela Bassoi; Nazarena A. Beretta; Danielle L. Buss; Susannah Calderan; Ted Cheeseman; Martin A. Collins; Paula Costa‐Urrutia; Paul Ensor; et al. (Marine Mammal Science, 2024)
The sub‐Antarctic waters of South Georgia Island (Islas Georgias del Sur, SG/IG) are a regularly visited feeding ground for southern right whales ( Eubalaena australis , SRW) in the southwest Atlantic. Satellite telemetry and photo‐identification records were compared to better understand the role of SG/IG in the SRW migratory network. We present the first insights from SRW satellite‐tracked from the SG/IG feeding ground, habitat use patterns in the Scotia Arc, and movements to Antarctic habitats. Photo‐identification comparisons to calving and feeding areas across the South Atlantic and a review of sightings of cetaceans reported from Bird Island (west of SG/IG) since 1979 illuminate long‐term habitat use patterns in SG/IG. We present the first recorded migratory movement between SG/IG and multiple countries: Argentina, Uruguay, and Brazil. Photo‐identification (1) linked SG/IG to a female SRW with a long‐term sighting history in Brazil, and (2) provided the first match between SG/IG and the western Antarctic Peninsula, suggesting the latter could extend the feeding area for southwest Atlantic SRW. Satellite tracking and opportunistic sightings suggest that shelf and coastal waters west of SG/IG represent an important multi‐season SRW feeding habitat and add to our overall understanding of habitats and ranges occupied by recovering southwest Atlantic SRW.

Genetic parameters for host-response to acanthocephaliasis caused by the endoparasite Neoechinorhynchus buttnerae in the Amazon fish Colossoma macropomum - John F.G. Agudelo; Baltasar F.G. Neto; Vito A. Mastrochirico-Filho; Raquel B. Ariede; Luis F.S. Moreira; Leilane da Silva Noronha; José M. Yáñez; Alexandre Honczaryk; Gustavo M.R. Valladão; Diogo T. Hashimoto (Aquaculture, 2024)

Relational place-based solutions for environmental policy misalignments - Hannah M. Kobluk; Anne K. Salomon; Adam T. Ford; Andrew N. Kadykalo; Mateen A. Hessami; Pierre-Alexandre Labranche; Carmen Richter; Wendy J. Palen; ḥapinyuuk Tommy Happynook; Murray M. Humphries; Elena M. Bennett (Trends in Ecology & Evolution, 2024)

Effects of the Northern Hemisphere sudden stratospheric warmings on the Sporadic-E layers in the Brazilian sector - Pedro A. Fontes; Marcio T.A.H. Muella; Laysa C.A. Resende; Rodolfo de Jesus; Paulo R. Fagundes; Paulo P. Batista; Valdir G. Pillat; Alexandre Tardelli; Vania F. Andrioli (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Effects of daytime exposure to short-wavelength-enriched white light on alertness and cognitive function among moderately sleep-restricted university students - Mushfiqul Anwar Siraji; Leilah K. Grant; Alexandre Schaefer; Shamsul Haque; Shadab A. Rahman; Steven W. Lockley; Vineetha Kalavally (Building and Environment, 2024)

Full-fat corn germ improves the performance and milk fat yield of Girolando cows fed sugarcane bagasse and cactus cladodes as forage sources - Camila S. da Silva; Marco Antônio S. da Gama; Erick Alexandre M. Silva; Emília F. Ribeiro; Silas B. Felix; Carolina C. F. Monteiro; Robert E. Mora-Luna; Júlio Cesar V. de Oliveira; Djalma C. dos Santos; Marcelo A. de Ferreira (Tropical Animal Health and Production, 2024)

Concentrations, sources and risks of polycyclic aromatic hydrocarbons in sediments from the Parnaiba Delta basin, Northeast Brazil - Analine D.C. Andrade; Gabrielle M. Fernandes; Davi A. Martins; Rivelino M. Cavalcante; Michel R.B. Chaves; Alexandre A. de Souza; Jeremias P. da S. Filho; Ronaldo F. Nascimento; Sidney G. de Lima (Chemosphere, 2024)

Unveiling functional linkages between habitats and organisms: Macroalgal habitats as influential factors of fish functional traits - José A. Sanabria-Fernández; Alexandre Génin; Vasilis Dakos (Marine Environmental Research, 2024)

Molecular Verification of Trichophyton in the Brazilian URM Culture Collection - Tatiana F. Oliveira; Carlos A. T. Valeriano; M. Daniela S. Buonafina-Paz; Cristina M. Souza-Motta; Alexandre R. Machado; Rejane P. Neves; Jadson D. P. Bezerra; Thales D. Arantes; Sybren de Hoog; Oliane M. C. Magalhães (Mycopathologia, 2024)

Intercropping with Trifolium repens contributes disease suppression of banana Fusarium wilt by reshaping soil protistan communities - Xiangyu Ren; Zeyuan Zhou; Manyi Liu; Zongzhuan Shen; Beibei Wang; Alexandre Jousset; Stefan Geisen; Mohammadhossein Ravanbakhsh; George A. Kowalchuk; Rong Li; Qirong Shen; Wu Xiong (Agriculture, Ecosystems & Environment, 2024)

Global patterns and environmental drivers of forest functional composition - Elise Bouchard; Eric B. Searle; Pierre Drapeau; Jingjing Liang; Javier G. P. Gamarra; Meinrad Abegg; Giorgio Alberti; Angelica Almeyda Zambrano; Esteban Alvarez‐Davila; Luciana F. Alves; Valerio Avitabile; Gerardo Aymard; et al. (Global Ecology and Biogeography, 2024)
Aim To determine the relationships between the functional trait composition of forest communities and environmental gradients across scales and biomes and the role of species relative abundances in these relationships. Location Global. Time period Recent. Major taxa studied Trees. Methods We integrated species abundance records from worldwide forest inventories and associated functional traits (wood density, specific leaf area and seed mass) to obtain a data set of 99,953 to 149,285 plots (depending on the trait) spanning all forested continents. We computed community‐weighted and unweighted means of trait values for each plot and related them to three broad environmental gradients and their interactions (energy availability, precipitation and soil properties) at two scales (global and biomes). Results Our models explained up to 60% of the variance in trait distribution. At global scale, the energy gradient had the strongest influence on traits. However, within‐biome models revealed different relationships among biomes. Notably, the functional composition of tropical forests was more influenced by precipitation and soil properties than energy availability, whereas temperate forests showed the opposite pattern. Depending on the trait studied, response to gradients was more variable and proportionally weaker in boreal forests. Community unweighted means were better predicted than weighted means for almost all models. Main conclusions Worldwide, trees require a large amount of energy (following latitude) to produce dense wood and seeds, while leaves with large surface to weight ratios are concentrated in temperate forests. However, patterns of functional composition within‐biome differ from global patterns due to biome specificities such as the presence of conifers or unique combinations of climatic and soil properties. We recommend assessing the sensitivity of tree functional traits to environmental changes in their geographic context. Furthermore, at a given site, the distribution of tree functional traits appears to be driven more by species presence than species abundance.

The 4.5 mb Amargosa earthquake of 30 August 2020, Bahia, Brazil: Implications for the intraplate stress field across the continental margin - Marcelo Assumpção; José Alexandre A. Nogueira; Juraci M. Carvalho; Fábio Dias; Nathalya Shimomura Ito; Lúcio Quadros; José Roberto Barbosa; Marcelo Bianchi; Bruno Collaço; Jackson Calhau (Journal of South American Earth Sciences, 2024)

Deciphering recycling processes during solar system evolution from magnesium-rich relict olivine grains in type II chondrules - Gabriel A. Pinto; Emmanuel Jacquet; Alexandre Corgne; Felipe Olivares; Johan Villeneuve; Yves Marrocchi (Geochimica et Cosmochimica Acta, 2024)

Occurrence of β-N-Methylamino-L-Alanine (BMAA) Toxin in irrigation Water and Field Vegetable Plants and Assessing Its Potential Risk to Human Health - Zakaria A. Mohamed; Rehab O. Elnour; Saad Alamri; Mohamed Hashem; Ali M. Alshehri; Alexandre Campos; Vitor Vasconcelos; Hanan Badawye (Water, Air, & Soil Pollution, 2024)

Marine teleost fishes of the northeastern Brazilian coast: 166 years of compiled data - Ricardo S. Rosa; Aline P. M. Medeiros; Antônio Felinto; Camila Brito; Erika F. C. Santana; Fernanda V. Albuquerque; Jonas A. Santos; Júlio Lustosa; Katherine M. P. Viana; Marianna B. Silva; Rafael Menezes; Viviana Márquez Velásquez; et al. (Systematics and Biodiversity, 2023)

The deep dive of organohalogen compounds: Bioaccumulation in the top predators of mesopelagic trophic webs, pygmy and dwarf sperm whales, from the Southwestern Atlantic ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Vitor L. Carvalho; Letícia Gonçalves; Pedro V. de Castilho; Eduardo R. Secchi; Silvina Botta; Milton C.C. Marcondes; Adriana C. Colosio; Marta J. Cremer; Haydée A. Cunha; et al. (Chemosphere, 2023)

Combining computational tools and experimental studies towards endocrine disruptors mitigation: A review of biocatalytic and adsorptive processes. - Maria Cristina Silva; Alexandre A. de Castro; Karla Lara Lopes; Igor F. Lara Ferreira; Raphael Resende Bretz; Teodorico C. Ramalho (Chemosphere, 2023)

Profiles of body image concerns and their associations with disordered eating behaviors - Sarah Baker; Christophe Maïano; Simon A. Houle; Lindsey Nadon; Annie Aimé; Alexandre J.S. Morin (Appetite, 2023)

Brominated flame retardants and natural organobrominated compounds in a vulnerable delphinid species along the Brazilian coast - Lara G. Vidal; Nara De Oliveira-Ferreira; João Paulo M. Torres; Alexandre F. Azevedo; Ana Carolina O. Meirelles; Leonardo Flach; Camila Domit; Ana Bernadete L. Fragoso; Flávio J. Lima Silva; Vítor Luz Carvalho; Milton Marcondes; Lupércio A. Barbosa; et al. (Science of The Total Environment, 2023)

Integrating remote sensing and machine learning to detect turbidity anomalies in hydroelectric reservoirs - Anderson P. Souza; Bruno A. Oliveira; Mauren L. Andrade; Maria Clara V.M. Starling; Alexandre H. Pereira; Philippe Maillard; Keiller Nogueira; Jefersson A. dos Santos; Camila C. Amorim (Science of The Total Environment, 2023)

Mapping integrated crop-livestock systems in Brazil with planetscope time series and deep learning - Inacio T. Bueno; João F.G. Antunes; Aliny A. Dos Reis; João P.S. Werner; Ana P.S.G.D.D. Toro; Gleyce K.D.A. Figueiredo; Júlio C.D.M. Esquerdo; Rubens A.C. Lamparelli; Alexandre C. Coutinho; Paulo S.G. Magalhães (Remote Sensing of Environment, 2023)

Fruit sizing using AI: A review of methods and challenges - Juan C. Miranda; Jordi Gené-Mola; Manuela Zude-Sasse; Nikos Tsoulias; Alexandre Escolà; Jaume Arnó; Joan R. Rosell-Polo; Ricardo Sanz-Cortiella; José A. Martínez-Casasnovas; Eduard Gregorio (Postharvest Biology and Technology, 2023)

Temperate Primary Forest Biomass Accumulates over Centuries-Long Time Frames - Dheeraj Ralhan; Heather Keith; Jakob Pavlin; Annemiek Irene Stegehuis; William Marchand; Alexandre Fruleux; Miroslav Poláček; Marek Svitok; Thomas A. Nagel; Martin Mikoláš; Daniel Kozák; Arne Buechling; et al. (Ecosystems, 2023)

Geographic Drivers of Genetic and Plumage Color Diversity in the Blue-Crowned Manakin - Pedro Paulo; Fernando Henrique Teófilo; Carolina Bertuol; Érico Polo; Andre E. Moncrieff; Lucas N. Bandeira; Claudia Nuñez-Penichet; Igor Yuri Fernandes; Mariane Bosholn; Arielli F. Machado; Leilton Willians Luna; Willian Thomaz Peçanha; et al. (Evolutionary Biology, 2023)

Rhizosphere shapes the associations between protistan predators and bacteria within microbiomes through the deterministic selection on bacterial communities - Yang Yue; Chen Liu; Boting Xu; Yijin Wang; Qihui Lv; Zeyuan Zhou; Rong Li; George A. Kowalchuk; Alexandre Jousset; Qirong Shen; Wu Xiong (Environmental Microbiology, 2023)
The assembly of bacterial communities in the rhizosphere is well‐documented and plays a crucial role in supporting plant performance. However, we have limited knowledge of how plant rhizosphere determines the assembly of protistan predators and whether the potential associations between protistan predators and bacterial communities shift due to rhizosphere selection. To address this, we examined bacterial and protistan taxa from 443 agricultural soil samples including bulk and rhizosphere soils. Our results presented distinct patterns of bacteria and protistan predators in rhizosphere microbiome assembly. Community assembly of protistan predators was determined by a stochastic process in the rhizosphere and the diversity of protistan predators was reduced in the rhizosphere compared to bulk soils, these may be attributed to the indirect impacts from the altered bacterial communities that showed deterministic process assembly in the rhizosphere. Interestingly, we observed that the plant rhizosphere facilitates more close interrelationships between protistan predators and bacterial communities, which might promote a healthy rhizosphere microbial community for plant growth. Overall, our findings indicate that the potential predator–prey relationships within the microbiome, mediated by plant rhizosphere, might contribute to plant performance in agricultural ecosystems.

Metabolomics and lipidomics reveal the effects of the toxic dinoflagellate Alexandrium catenella on immune cells of the blue mussel, Mytilus edulis - Stéphane Beauclercq; Olivier Grenier; Alexandre A. Arnold; Dror E. Warschawski; Gary H. Wikfors; Bertrand Genard; Réjean Tremblay; Isabelle Marcotte (Harmful Algae, 2023)

Nutritional and chemical composition of Alpinia zerumbet leaves, a traditional functional food - Jefferson Diocesano da Cruz; Maria A. Mpalantinos; Laena Rebouças de Oliveira; Tainara Garcia Branches; Alexandre Xavier; Francisca das Chagas do A. Souza; Jaime P. Lopes Aguiar; José Luiz P. Ferreira; Jefferson Rocha de Andrade Silva; Ana Claudia Fernandes Amaral (Food Research International, 2023)

CO2 capture and conversion to methane with Ni-substituted hydrotalcite dual function extrudates - A. Catarina Faria; C.V. Miguel; Alexandre F.P. Ferreira; A.E. Rodrigues; Luís M. Madeira (Chemical Engineering Journal, 2023)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

Smartwatch-Based Prediction of Single-Stride and Stride-to-Stride Gait Outcomes Using Regression-Based Machine Learning - Christopher A. Bailey; Alexandre Mir-Orefice; Thomas K. Uchida; Julie Nantel; Ryan B. Graham (Annals of Biomedical Engineering, 2023)

A map of white matter tracts in a lesser ape, the lar gibbon - Katherine L. Bryant; Paul R. Manger; Mads F. Bertelsen; Alexandre A. Khrapitchev; Jérôme Sallet; R. Austin Benn; Rogier B. Mars (Brain Structure and Function, 2023)
The recent development of methods for constructing directly comparable white matter atlases in primate brains from diffusion MRI allows us to probe specializations unique to humans, great apes, and other primate taxa. Here, we constructed the first white matter atlas of a lesser ape using an ex vivo diffusion-weighted scan of a brain from a young adult (5.5 years) male lar gibbon. We find that white matter architecture of the gibbon temporal lobe suggests specializations that are reminiscent of those previously reported for great apes, specifically, the expansion of the arcuate fasciculus and the inferior longitudinal fasciculus in the temporal lobe. Our findings suggest these white matter expansions into the temporal lobe were present in the last common ancestor to hominoids approximately 16 million years ago and were further modified in the great ape and human lineages. White matter atlases provide a useful resource for identifying neuroanatomical differences and similarities between humans and other primate species and provide insight into the evolutionary variation and stasis of brain organization.

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

Serum of COVID-19 patients changes neuroinflammation and mitochondrial homeostasis markers in hippocampus of aged rats - Yorran Hardman A. Montenegro; Larissa Daniele Bobermin; Patrícia Sesterheim; Richard Steiner Salvato; Fernando Anschau; Maria José Santos de Oliveira; Angela T. S. Wyse; Carlos Alexandre Netto; Carlos-Alberto Saraiva Gonçalves; André Quincozes-Santos; Guilhian Leipnitz (Journal of NeuroVirology, 2023)

High cold tolerance and differential population response of third instars from the Zeugodacus tau complex to phytosanitary cold treatment in navel oranges - Vanessa S. Dias; Guy J. Hallman; Alexandre S. Araújo; Inajara V.G. Lima; Fabio L. Galvão-Silva; Luis A. Caravantes; Martha N.G. Rivera; Jhonatan S. Aguilar; Carlos E. Cáceres-Barrios; Marc J.B. Vreysen; Scott W. Myers (Postharvest Biology and Technology, 2023)

Glacial/interglacial climate variability in southern Spain during the late Early Pleistocene and climate backdrop for early Homo in Europe - Christian Sánchez-Bandera; Ana Fagoaga; Alexia Serrano-Ramos; José Solano-García; Deborah Barsky; Daniel DeMiguel; Juan Ochando; Juha Saarinen; Pedro Piñero; Iván Lozano-Fernández; Lloyd A. Courtenay; Stefania Titton; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Getting fat and stressed: Effects of dietary intake of titanium dioxide nanoparticles in the liver of turbot Scophthalmus maximus - Elza Fonseca; María Vázquez; Laura Rodriguez-Lorenzo; Natalia Mallo; Ivone Pinheiro; Maria Lígia Sousa; Santiago Cabaleiro; Monica Quarato; Miguel Spuch-Calvar; Miguel A. Correa-Duarte; Juan José López-Mayán; Mick Mackey; et al. (Journal of Hazardous Materials, 2023)

In search of the Rheic suture: detrital zircon geochronology of Neoproterozoic to Lower Paleozoic metasedimentary units in the Balkan fold-and-thrust belt in Bulgaria - Jiří Žák; Martin Svojtka; Ianko Gerdjikov; Dian A. Vangelov; Alexandre Kounov; Jiří Sláma; Václav Kachlík (Gondwana Research, 2023)

Quantifying the effectiveness of shaded fuel breaks from ground-based, aerial, and spaceborne observations - Janine A. Baijnath-Rodino; Alexandre Martinez; Robert A. York; Efi Foufoula-Georgiou; Amir AghaKouchak; Tirtha Banerjee (Forest Ecology and Management, 2023)

The role of ion homeostasis imbalance due to citrate accumulation in fluoroacetic acid (FAA) toxicity in Neurospora crassa - João Monteiro; Clive A. Marks; Patrícia C. Braga; Raquel L. Bernardino; Marco G. Alves; Alexandre Lobo-da-Cunha; Arnaldo Videira; Filipe Pereira (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Detection and genetic characterization of circoviruses in more than 80 bat species from eight countries on four continents - Márton Z. Vidovszky; Szilvia Kapitány; Ákos Gellért; Balázs Harrach; Tamás Görföl; Sándor A. Boldogh; Claudia Kohl; Gudrun Wibbelt; Kristin Mühldorfer; Gábor Kemenesi; Guy-Crispin Gembu; Alexandre Hassanin; et al. (Veterinary Research Communications, 2023)
Several bat-associated circoviruses and circular rep-encoding single-stranded DNA (CRESS DNA) viruses have been described, but the exact diversity and host species of these viruses are often unknown. Our goal was to describe the diversity of bat-associated circoviruses and cirliviruses, thus, 424 bat samples from more than 80 species were collected on four continents. The samples were screened for circoviruses using PCR and the resulting amino acid sequences were subjected to phylogenetic analysis. The majority of bat strains were classified in the genus Circovirus and some strains in the genus Cyclovirus and the clades CRESS1 and CRESS3. Some strains, however, could only be classified at the taxonomic level of the order and were not classified in any of the accepted or proposed clades. In the family Circoviridae , 71 new species have been predicted . This screening of bat samples revealed a great diversity of circoviruses and cirliviruses. These studies underline the importance of the discovery and description of new cirliviruses and the need to establish new species and families in the order Cirlivirales.

Correlations between lignin content and related genes, weathering deterioration, and soybean seed quality at pre-harvest - Alana Madureira; Mayla D. C. Molinari; Silvana R. R. Marin; Renata Fuganti Pagliarini; Fernando A. Henning; Alexandre L. Nepomuceno; Taciane Finatto; Liliane M. Mertz-Henning (Journal of Crop Science and Biotechnology, 2023)

Late Alpine multistage exhumation of the northwestern Rhodope Metamorphic Complex (northern Rila Mountains, Bulgaria) - Alexandre Kounov; Ianko Gerdjikov; Milorad D. Antić; Neven Georgiev; Richard A. Spikings (International Journal of Earth Sciences, 2023)
The Rhodope crystalline massif is an Alpine metamorphic complex exposed across several mountain ranges in southern Bulgaria and northern Greece which has experienced a complex history including continental collision, partial subduction and syn-metamorphic nappe stacking followed by syn- to post-contractional extension. We present new 40 Ar/ 39 Ar and fission-track data from samples taken from both sides of the North Rhodopean Detachment that were combined with detailed structural studies to investigate the tectonothermal evolution of the northern Rila Mountains. A migmatite from the hanging wall of the North Rhodopean Detachment yields a 40 Ar/ 39 Ar muscovite age of 100.79 ± 0.55 Ma, a zircon fission-track age of 38.6 ± 1.9 Ma, and an apatite fission-track age of 21.4 ± 1.5 Ma. A biotite schist from the footwall of the detachment yields 40 Ar/ 39 Ar biotite age of 34.90 ± 0.15 Ma, and zircon and apatite fission-track ages of 35.6 ± 5.6 and 13.3 ± 1.1 Ma, respectively. Our new data give evidence of a multistage exhumation of the study area. Late Early Cretaceous (~ 101 ± 0.6 Ma) cooling of the Variscan high-grade metamorphic basement through 440–400 °C was caused by either erosion of the emplacing thrust sheet, or post-contractional denudation. Fast exhumation along the North Rhodopean Extensional System drove a pulse of increased tectonic denudation and cooling during the Eocene (39–35 Ma). Exhumation of the rocks in the northern part of the Rila Mountains below 110 ± 10 °C during the middle–late Miocene was associated with displacement along a system of normal faults.

COVID-19 and candiduria: an investigation of the risk factors and immunological aspects - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; Ana C. Lyon; Olindo A. Martins-Filho; et al. (Brazilian Journal of Microbiology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Relationships among the founding ancestral genomes involved in the origin of sugarcane (Saccharum spp.) based on FISH and GISH comparative analysis - Nina Reis Soares; Gleicy K. Oliveira; Mauro Alexandre Xavier; Silvana A. Creste Dias Souza; Maria Lucia Carneiro Vieira (Brazilian Journal of Botany, 2023)

Contributions of nature-based solutions to reducing people’s vulnerabilities to climate change across the rural Global South - Stephen Woroniecki; Femke A. Spiegelenberg; Alexandre Chausson; Beth Turner; Isabel Key; Haseeb Md. Irfanullah; Nathalie Seddon (Climate and Development, 2023)

[8] and [10]-Gingerol reduces urothelial damage in ifosfamide-induced hemorrhagic cystitis via JAK/STAT/FOXO signaling pathway via IL-10 - Francisco C. S. Ferreira; Marco Clementino; Francisco A. P. Rodrigues; Herlice N. Veras; Dainesy S. Martins; Marcus L. Queiroga; Mikael A. Lima; Dayara O. Silva; Thiago M. de Freitas; Samilly A. Ribeiro; Mario R. L. Mota; James A. da Silva; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Design, synthesis, and in vitro antiplatelet aggregation activities of taiwanin C - Érika C. A. S. K. Daron; Wellington T. Negri; Alexandre Borges; Caroline H. Lescano; Edson Antunes; Rosangela S. de Laurentiz (Natural Product Research, 2023)

Metastatic Sertoli cell tumour in a captive giant anteater (Myrmecophaga tridactyla) - Clarissa H. Santana; Lucas dos R. de Souza; Laice A. da Silva; Ayisa R. Oliveira; Nayara F. de Paula; Daniel O. dos Santos; Fernanda M.A.M. Pereira; André D. Vieira; Letícia N. Ribeiro; Lauro L. Soares-Neto; Alexandre L. da Costa Bicudo; Alícia G. Hippolito; et al. (Journal of Comparative Pathology, 2023)

The IV International Symposium on Fungal Stress and the XIII International Fungal Biology Conference - Alene Alder-Rangel; Alexandre Melo Bailão; Alfredo Herrera-Estrella; Amanda E.A. Rangel; Attila Gácser; Audrey P. Gasch; Claudia B.L. Campos; Christina Peters; Francine Camelim; Fulvia Verde; Geoffrey Michael Gadd; Gerhard Braus; et al. (Fungal Biology, 2023)

A conditional machine learning classification approach for spatio-temporal risk assessment of crime data - Alexandre Rodrigues; Jonatan A. González; Jorge Mateu (Stochastic Environmental Research and Risk Assessment, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

How arsenic contamination influences downslope wetland plant and microbial community structure and function - Kimber E. Munford; Spencer Gilbert-Parkes; Nadia C.S. Mykytczuk; Nathan Basiliko; Kurt M. Yakimovich; Alexandre Poulain; Shaun A. Watmough (Science of The Total Environment, 2023)

Wet brewers’ grains as a source of protein for feedlot lambs: Impacts on intake, apparent nutrient digestibility, ruminal fermentation, and nitrogen balance - Rhaíssa G. de Assis; Isabela J. dos Santos; Jennifer M. Gasparina; Natalia A. Bandoria; Brenda Alves; Paulo C.G. Dias; Ana C.S. Vicente; Letícia C.B. Soares; Daniel M. Polizel; Janaina S. Biava; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

Conservation entrepreneurship: A new frontier in conservation science - Diele Lobo; Peter B. Reich; Alexandre A. Ardichvili (Biological Conservation, 2023)

Harmful Effects of Potentially Toxic Elements in Soils of Cerrado Biomes - João B. P. Cabral; Wanderlubio B. Gentil; Fernanda L. Ramalho; Celso C. Braga; Valter A. Becegato; Alexandre T. Paulino (Water, Air, & Soil Pollution, 2023)

Historical biogeography highlights the role of Miocene landscape changes on the diversification of a clade of Amazonian tree frogs - Diego A. Ortiz; Conrad J. Hoskin; Fernanda P. Werneck; Alexandre Réjaud; Sophie Manzi; Santiago R. Ron; Antoine Fouquet (Organisms Diversity & Evolution, 2023)
The diversification processes underlying why Amazonia hosts the most species-rich vertebrate fauna on earth remain poorly understood. We studied the spatio-temporal diversification of a tree frog clade distributed throughout Amazonia (Anura: Hylidae: Osteocephalus , Tepuihyla , and Dryaderces ) and tested the hypothesis that Miocene mega wetlands located in western and central Amazonia impacted connectivity among major biogeographic areas during extensive periods. We assessed the group’s diversity through DNA-based (16S rRNA) species delimitation to identify Operational Taxonomic Units (OTUs) from 557 individuals. We then selected one terminal for each OTU ( n = 50) and assembled a mitogenomic matrix (~14,100 bp; complete for 17 terminals) to reconstruct a Bayesian, time-calibrated phylogeny encompassing nearly all described species. Ancestral area reconstruction indicates that each genus was restricted to one of the major Amazonian biogeographic areas (western Amazonia, Guiana Shield and Brazilian Shield, respectively) between ~10 and 20 Mya, suggesting that they diverged and diversified in isolation during this period around the Pebas mega wetland. After 10 Mya and the transition to the modern configuration of the Amazon River watershed, most speciation within each genus continued to occur within each area. In Osteocephalus , only three species expanded widely across Amazonia (< 6 Mya), and all were pond-breeders. Species with other breeding modes remained mostly restricted to narrow ranges. The spectacular radiation of Osteocephalus was probably driven by climatic stability, habitat diversity and the acquisition of new reproductive modes along the Andean foothills and western Amazonia. Our findings add evidence to the importance of major hydrological changes during the Miocene on biotic diversification in Amazonia.

Identification of Clinical Trichosporon asteroides Strains by MALDI-TOF Mass Spectrometry: Evaluation of the Bruker Daltonics Commercial System and an In-House Developed Library - Elaine Cristina Francisco; Mexx Ebbing; Arnaldo Lopes Colombo; Ferry Hagen; Guilherme M. Chaves; Ana Verena A. Mendes; Marcio de Oliveira Silva; Maria Goreth de Andrade Barberino; Rejane Pereira Neves; Monica Borges Botura; Rosane C. Hahn; João Nóbrega de Almeida Junior; et al. (Mycopathologia, 2023)

Coexistence of two sympatric hermit crab species from South Brazil: the effect of the shell adequacy index and circadian movement patterns - Alexandre R. da Silva; Renan A. P. Santos; Gabriel F. B. Rodrigues; Neida R. Vieira; Bruna K. Baroni; Rafael A. Gregati (Aquatic Ecology, 2023)

An additional threat to populations predicted to collapse: Organobromine compounds of natural and anthropogenic sources in rough-toothed dolphins from the Southwestern Atlantic Ocean - Nara de Oliveira-Ferreira; Elitieri B. Santos-Neto; Bárbara M.R. Manhães; Camila Domit; Eduardo R. Secchi; Silvina Botta; Haydée A. Cunha; Alexandre F. Azevedo; Tatiana L. Bisi; José Lailson-Brito (Chemosphere, 2023)

To den or not to den. Contributions to the taphonomic history of the Early Pleistocene site of Venta Micena 4 (Orce, Guadix-Baza Basin) - Jose Yravedra Sainz de los Terreros; Carmen Luzón; Jose A. Solano; Gonzalo J. Linares-Matas; Verónica Estaca-Gomez; Juan José Rodríguez-Alba; Lloyd A. Courtenay; Darío Herranz-Rodrigo; Alexia Serrano-Ramos; José Cámara; Juha Saarinen; Christian Sánchez-Bandera; et al. (Quaternary Science Reviews, 2023)

Sea state estimation based on the motion data of a moored FPSO using neural networks: An evaluation with multiple draft conditions - Gustavo A. Bisinotto; João V. Sparano; Alexandre N. Simos; Fabio G. Cozman; Marcos D. Ferreira; Eduardo A. Tannuri (Ocean Engineering, 2023)

Colored shade nets and different harvest times alter the growth, antioxidant status, and quantitative attributes of glandular trichomes and essential oil of Thymus vulgaris L. - Alan da Cunha Honorato; Gabriel A. Nohara; Rafael M.A. de Assis; João F.A. Maciel; Alexandre A. de Carvalho; José E.B.P. Pinto; Suzan K.V. Bertolucci (Journal of Applied Research on Medicinal and Aromatic Plants, 2023)

Whole bone subcutaneous transplantation as a strategy to study precisely the bone marrow niche - Caroline C. Picoli; Patrícia Rocha Martins; Xiao Lin Casey Wong; Thamires Righi; Pedro P. G. Guimarães; Mauro C. X. Pinto; Jaime H. Amorim; Vasco A. C. Azevedo; Silma Regina Pereira; Alexandre Kanashiro; Fabio Cardoso Cruz; Rodrigo R. Resende; et al. (Stem Cell Reviews and Reports, 2023)

Determinants of body core temperatures at fatigue in rats subjected to incremental-speed exercise: The prominent roles of ambient temperature, distance traveled, initial core temperature, and measurement site - Marcelo T. Andrade; Nicolas H. S. Barbosa; Roberto C. S. Souza-Junior; Cletiana G. Fonseca; William C. Damasceno; Kássya Regina-Oliveira; Lucas R. Drummond; Myla A. Bittencourt; Ana C. Kunstetter; Pedro V. R. Andrade; Alexandre S. R. Hudson; Pedro H. Paula; et al. (International Journal of Biometeorology, 2023)

A seasonal transition in biological carbon pump efficiency in the northern Scotia Sea, Southern Ocean - Stephanie A. Henson; Nathan Briggs; Filipa Carvalho; Clara Manno; Alexandre Mignot; Sandy Thomalla (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Hyperphosphorylated Tau in Mesial Temporal Lobe Epilepsy: a Neuropathological and Cognitive Study - Eliana C. B. Toscano; Érica L. M. Vieira; Lea T. Grinberg; Natalia P. Rocha; Joseane A. S. Brant; Regina S. Paradela; Alexandre V. Giannetti; Claudia K. Suemoto; Renata E. P. Leite; Ricardo Nitrini; Milene A. Rachid; Antonio L. Teixeira (Molecular Neurobiology, 2023)

Xenarthra richness and activity pattern in the Brazilian Amazon - Maíra Prestes Margarido; Elildo A. R. Carvalho; Whaldener Endo; Alexandre Martins Costa Lopes; Flávia Regina Miranda (Mammalian Biology, 2023)

Antimicrobial and Antibiofilm Activity of Copper-Based Metallic Compounds Against Bacteria Related with Healthcare-Associated Infections - Anna L. Pereira; Mayron A. Vasconcelos; Alexandre L. Andrade; Israel M. Martins; Alda K. M. Holanda; Ana C. S. Gondim; Dayana P. S. Penha; Katherine L. Bruno; Francisco O. N. Silva; Edson H. Teixeira (Current Microbiology, 2023)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Dating hydrothermal processes related to the formation of the Lagoa Real uranium deposits using in situ U–Pb dating of andradite and titanite - Camila Marques; Kathryn A. Cutts; Alexandre Raphael Cabral; Cristiano Lana; Francisco Javier Rios; Ian Buick (Journal of South American Earth Sciences, 2023)

Estimation of susceptibility to erosion-soil loss in drainage basins: a case study - Marcelo D. R. Pereira; João B. P. Cabral; Michaela A. B. Camara; Francisco D. Maldonado; Valter A. Becegato; Alexandre T. Paulino; Fernanda L. Ramalho (Natural Hazards, 2023)

TimeFISH : Long‐term assessment of reef fish assemblages in a transition zone in the Southwestern Atlantic - Juan P. Quimbayo; Lucas T. Nunes; Fernanda C. Silva; Antônio B. Anderson; Diego R. Barneche; Angela M. Canterle; Isadora Cord; Andrea Dalben; Débora S. Ferrari; Luisa Fontoura; Thiago M. J. Fiuza; Ana M. R. Liedke; et al. (Ecology, 2023)
The TimeFISH database provides the first public time‐series dataset on reef fish assemblages in the southwestern Atlantic (SWA), comprising 15 years of data (2007–2022) based on standardized Underwater Visual Censuses (UVCs). The rocky reefs covered by our dataset are influenced by pronounced seasonal cycles of ocean temperatures with warm tropical waters from the Brazil Current in the summer (~27°C) and colder waters from the La Plata River Plume discharge and upwelling from the South Atlantic Central Water in the winter (~18°C). These oceanographic conditions characterize this area as the southernmost tropical–subtropical climatic transition zone in the Atlantic Ocean. As a result, reef fish assemblages are comprised of both tropical and subtropical species. All records included in TimeFISH were collected using UVCs, a nondestructive method that allows the estimation of fish species richness, abundance, and body size distributions. UVCs were performed through 40 m 2 belt transects by scuba diving in nine locations along the southern Brazilian coast (25–29°S). Four of these locations lie within the boundaries of the no‐entry Arvoredo Marine Biological Reserve, where fishing and recreational activities are forbidden, and the remaining locations are unprotected from these activities. During each belt transect, a diver swam at a constant depth above and parallel to the reef, identifying fish species, counting the number of individuals, and estimating the total body length (Lt in cm) of all detected individuals. All fish individuals in the water column (up to 2 m above the substratum) and at the bottom were targeted. In total, 202,965 individuals belonging to 163 reef fish species and 53 families were recorded across 1857 UVCs. All survey campaigns were funded by either public or mixed capital (private–public) sources, including seven grants from the Brazilian federal and Santa Catarina state governments. Part of the data has already been used in multiple MS.c. and Ph.D. theses and scientific articles. TimeFISH represents an important contribution for future studies aiming to examine temporal and spatial variations of reef fish assemblages in transition zones. No copyright restrictions apply to the use of this data set, other than citing this publication.

Are birds more afraid in urban parks or cemeteries? A Latin American study contrasts with results from Europe - Federico Morelli; Lucas M. Leveau; Peter Mikula; Ian MacGregor-Fors; M. Lucia Bocelli; Sergio Gabriel Quesada-Acuña; César González-Lagos; Pablo Gutiérrez-Tapia; Gabriela Franzoi Dri; Carlos A. Delgado-V.; Alvaro Garitano Zavala; Jackeline Campos; et al. (Science of The Total Environment, 2023)

Essential oil from Arnica montana alters the protein metabolism in lambs fed with high-concentrate diets - Paulo César G. Dias Junior; Isabela J. dos Santos; Jennifer M. Gasparina; Natália A. Bandoria; Letícia C.B. Soares; Adrielly L.A. da Silva; Rhaissa G. de Assis; Daniel M. Polizel; Janaina S. Biava; Alexandre V. Pires; Evandro M. Ferreira (Small Ruminant Research, 2023)

What’s up and where to go in social life cycle impact assessment cause-effect model development? - Cássia Ugaya; Jaylton Bonacina de Araújo; Alexandre Souza; Breno Barros Telles do Carmo; Sueli A. de Oliveira; Vinícius Gonçalves Maciel (The International Journal of Life Cycle Assessment, 2023)

Differential proteomics of Zika virus (ZIKV) infection reveals molecular changes potentially involved in immune system evasion by a Brazilian strain of ZIKV - Juliana M. Tatara; Rafael L. Rosa; Ana Paula M. Varela; Tais F. Teixeira; Patrícia Sesterheim; Anderson Gris; David Driemeier; Amanda N. S. Moraes; Markus Berger; Ramon D. Peña; Paulo M. Roehe; Diogo O. G. Souza; et al. (Archives of Virology, 2023)

Tissue-resident glial cells associate with tumoral vasculature and promote cancer progression - Beatriz G. S. Rocha; Caroline C. Picoli; Bryan O. P. Gonçalves; Walison N. Silva; Alinne C. Costa; Michele M. Moraes; Pedro A. C. Costa; Gabryella S. P. Santos; Milla R. Almeida; Luciana M. Silva; Youvika Singh; Marcelo Falchetti; et al. (Angiogenesis, 2023)

Improving the accuracy of beef cattle methane inventories in Latin America and Caribbean countries - Guilhermo F.S. Congio; André Bannink; Olga L. Mayorga; João P.P. Rodrigues; Adeline Bougouin; Ermias Kebreab; Paulo C.F. Carvalho; Telma T. Berchielli; Maria E.Z. Mercadante; Sebastião C. Valadares-Filho; Ana L.C.C. Borges; Alexandre Berndt; et al. (Science of The Total Environment, 2023)

Sedimentary PAH and oxidative stress biomarkers responses on Namalycastis abiuma (Polychaeta: Nereididae) from an urbanized Amazon estuary - Silvia K. Kawakami; Leonardo Mello; Antônio L. Dergan; Camila Evangelista; Rafael F. Aquino; Rosivaldo A. Mendes; Alexandre M.C. Carmo; Lílian L. Amado (Regional Studies in Marine Science, 2023)

Slow and steady wins the race: Diversification rate is independent from body size and lifestyle in Malagasy skinks (Squamata: Scincidae: Scincinae) - Francesco Belluardo; A. Jesus Muñoz-Pajares; Aurélien Miralles; Daniele Silvestro; Walter Cocca; Fanomezana Mihaja Ratsoavina; Andrea Villa; Sam Hyde Roberts; Marcello Mezzasalma; Alexander Zizka; Alexandre Antonelli; Angelica Crottini (Molecular Phylogenetics and Evolution, 2023)

Comparative study of the production of cellulose nanofibers from agro-industrial waste streams of Salicornia ramosissima by acid and enzymatic treatment - Alexandre R. Lima; Nathana L. Cristofoli; Ana M. Rosa da Costa; Jorge A. Saraiva; Margarida C. Vieira (Food and Bioproducts Processing, 2023)

Machine learning directed multi-objective optimization of mixed variable chemical systems - Oliver J. Kershaw; Adam D. Clayton; Jamie A. Manson; Alexandre Barthelme; John Pavey; Philip Peach; Jason Mustakis; Roger M. Howard; Thomas W. Chamberlain; Nicholas J. Warren; Richard A. Bourne (Chemical Engineering Journal, 2023)

Winter wheat evapotranspiration and irrigation requirements across tropical and sub-tropical producing regions in Brazil - Rodolfo A. A. Pereira; Evandro H. F. M. Silva; Alexandre O. Gonçalves; Murilo S. Vianna; Tonny J. A. Silva; William Fenner; Paulo V. D. Vieira; Fábio R. Marin (Theoretical and Applied Climatology, 2023)

The role of hydration water in inorganic M+n -magadiites (M+n = K+, Ca+2, Mg+2): Advances in structural and electronic analysis by DFT calculations. - Bruna Nádia N. Silva; Heloise O. Pastore; Alexandre A. Leitão (Applied Clay Science, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Molecular taxonomic identification and species-level phylogeny of the narrow-mouthed frogs of the genus Rhombophryne (Anura: Microhylidae: Cophylinae) from Madagascar - Francesco Belluardo; Mark D. Scherz; Bárbara Santos; Franco Andreone; Alexandre Antonelli; Frank Glaw; A. Jesus Muñoz-Pajares; Jasmin E. Randrianirina; Achille P. Raselimanana; Miguel Vences; Angelica Crottini (Systematics and Biodiversity, 2022)

Estimating abundance of an elusive cetacean in a complex environment: Harbor porpoises (Phocoena phocoena) in inland waters of Southeast Alaska - Alexandre N. Zerbini; Kimberly T. Goetz; Karin A. Forney; Charlotte Boyd (Frontiers in Marine Science, 2022)
The harbor porpoise ( Phocoena phocoena ) is common in temperate waters of the eastern North Pacific Ocean, including Southeast Alaska inland waters, a complex environment comprised of open waterways, narrow channels, and inlets. Two demographically independent populations are currently recognized in this region. Bycatch of porpoises in the salmon drift gillnet fisheries is suspected to occur regularly. In this study, we apply distance sampling to estimate abundance of harbor porpoise during ship surveys carried out in the summer of 2019. A stratified survey design was implemented to sample different harbor porpoise habitats. Survey tracklines were allocated following a randomized survey design with uniform coverage probability. Density and abundance for the northern and southern Southeast Alaska inland water populations were computed using a combination of design-based line- and strip-transect methods. A total of 2,893 km was surveyed in sea state conditions ranging from Beaufort 0 to 3 and 194 harbor porpoise groups (301 individuals) were detected. An independent sighting dataset from surveys conducted between 1991 and 2012 were used to calculate the probability of missing porpoise groups on the survey trackline (g[0]=0.53, CV=0.11). Abundance of the northern and southern populations were estimated at 1,619 (CV=0.26) and 890 (CV=0.37) porpoises, respectively. Bycatch estimates, which were only obtained for a portion of the drift gillnet fishery, suggest that mortality within the range of the southern population may be unsustainable. Harbor porpoises are highly vulnerable to mortality in gillnets, therefore monitoring abundance and bycatch is important for evaluating the potential impact of fisheries on this species in Southeast Alaska.

The impact of COVID-19 on antimicrobial prescription and drug resistance in fungi and bacteria - Junya L. Singulani; Danielle L. Silva; Caroline M. Lima; Vanessa C. R. Magalhães; Ludmila M. Baltazar; Nalu T. A. Peres; Rachel B. Caligiorne; Alexandre S. Moura; Ana Raquel O. Santos; Tatiani Fereguetti; Juliana C. Martins; Lívia F. Rabelo; et al. (Brazilian Journal of Microbiology, 2022)

Resource availability drives bacteria community resistance to pathogen invasion via altering bacterial pairwise interactions - Mei Li; Thomas Pommier; Yue Yin; Wenhui Cao; Xiaohui Zhang; Jie Hu; Yann Hautier; Tianjie Yang; Yangchun Xu; Qirong Shen; George A. Kowalchuk; Alexandre Jousset; et al. (Environmental Microbiology, 2022)
Microbial interactions within resident communities are a major determinant of resistance to pathogen invasion. Yet, interactions vary with environmental conditions, raising the question of how community composition and environments interactively shape invasion resistance. Here, we use resource availability (RA) as a model parameter altering the resistance of model bacterial communities to invasion by the plant pathogenic bacterium Ralstonia solanacearum . We found that at high RA, interactions between resident bacterial species were mainly driven by the direct antagonism, in terms of the means of invader inhibition. Consequently, the competitive resident communities with a higher production of antibacterial were invaded to a lesser degree than facilitative communities. At low RA, bacteria produced little direct antagonist potential, but facilitative communities reached a relatively higher community productivity, which showed higher resistance to pathogen invasion than competitive communities with lower productivities. This framework may lay the basis to understand complex microbial interactions and biological invasion as modulated by the dynamic changes of environmental resource availability.

Dispersal syndromes in challenging environments: A cross‐species experiment - Julien Cote; Maxime Dahirel; Nicolas Schtickzelle; Florian Altermatt; Armelle Ansart; Simon Blanchet; Alexis S. Chaine; Frederik De Laender; Jonathan De Raedt; Bart Haegeman; Staffan Jacob; Oliver Kaltz; et al. (Ecology Letters, 2022)
Dispersal is a central biological process tightly integrated into life‐histories, morphology, physiology and behaviour. Such associations, or syndromes, are anticipated to impact the eco‐evolutionary dynamics of spatially structured populations, and cascade into ecosystem processes. As for dispersal on its own, these syndromes are likely neither fixed nor random, but conditional on the experienced environment. We experimentally studied how dispersal propensity varies with individuals' phenotype and local environmental harshness using 15 species ranging from protists to vertebrates. We reveal a general phenotypic dispersal syndrome across studied species, with dispersers being larger, more active and having a marked locomotion‐oriented morphology and a strengthening of the link between dispersal and some phenotypic traits with environmental harshness. Our proof‐of‐concept metacommunity model further reveals cascading effects of context‐dependent syndromes on the local and regional organisation of functional diversity. Our study opens new avenues to advance our understanding of the functioning of spatially structured populations, communities and ecosystems.

Observing the spread of Agulhas Leakage into the Western South Atlantic by tracking mode waters within ocean rings - Luiz Alexandre A. Guerra; Guilherme N. Mill; Afonso M. Paiva (Frontiers in Marine Science, 2022)
The Agulhas rings transport warm and salty waters that feed the surface limb of the Atlantic Meridional Overturning Circulation. Some studies have focused on the conveying capacity of ocean eddies, and recently, the role of the Agulhas rings in advecting water masses and organisms has been explored. Here we show evidence that the Agulhas rings are responsible for the advection of mode waters from the Cape Basin to the western side of the Atlantic. We analyzed more than 3,200 temperature profiles and 2,400 salinity profiles from historical databases collocated with 52 long-lived Agulhas rings tracked from 1993 through 2016. An automated algorithm was used to identify thermostads in the profiles acquired within the rings. The data revealed mode water layers trapped inside 88% of the rings. The joint distribution of temperature and salinity indicated two types of mode waters in the range 16.2 ± 0.6°C, 35.6 ± 0.1 (Type I) and 12.9 ± 0.7°C, 35.2 ± 0.1 (Type II). The majority (67%) of the rings carrying mode waters had both types detected inside. Moreover, considering only those rings sampled west of the Mid-Atlantic Ridge, we found that 45% of them advected mode waters to the western basin. Therefore, our results demonstrate that, despite the long journey, interaction with the bottom topography and other vortices, ocean-atmosphere exchanges, and decay, the Agulhas rings are responsible for spreading mode waters initially available at the Cape Basin throughout the South Atlantic, contributing to a positive anomaly in temperature and salinity along the eddy corridor joining the Cape Basin to the Brazil Basin.

Assessing bias in aerial surveys for cetaceans: Results from experiments conducted with the franciscana dolphin - Federico Sucunza; Daniel Danilewicz; Artur Andriolo; Franciele R. de Castro; Marta Cremer; Pablo Denuncio; Emanuel Ferreira; Paulo A. C. Flores; Paulo H. Ott; Martin S. Perez; Dan Pretto; Camila M. Sartori; et al. (Frontiers in Marine Science, 2022)
Line transect aerial surveys are widely used for estimating abundance of biological populations, including threatened species. However, estimates obtained with data collected from aircraft are often underestimated because of visibility bias and bias in estimating group sizes from a fast-moving platform. An assessment of multiple sources of bias in aerial surveys were carried out in Brazilian coastal waters by experiments on multiple survey platforms (i.e., boat, airplane and helicopter). These studies focused on evaluating visibility bias (perception and availability bias) and potential differences in the estimation of group sizes from different types of platforms used in franciscana ( Pontoporia blainvillei ) abundance surveys. The ultimate goal was to develop correction factors to improve accuracy of estimates of density and population size for this threatened dolphin. Estimates of density and group sizes computed from boats were assumed to be unbiased and were compared to estimates of these quantities obtained from an airplane in the same area and period. In addition, helicopter surveys were conducted in two areas where water turbidity differed (clear vs. murky waters) to determine surfacing-diving intervals of franciscana groups and to estimate availability for aerial platforms. Abundance computed from the aerial survey data underestimated the true abundance by about 4-5 times, with ~70% of the total bias resulting from visibility bias (~80% from availability bias and ~20% from perception bias) and ~30% from bias in estimates of group size. The use of multiple survey platforms in contrasting habitats provided the opportunity to compute correction factors that can be used to refine range wide abundance estimates of the threatened franciscana given certain assumptions are met. Visibility bias and group size bias were substantial and clearly indicate the importance for accounting for such correction factors to produce unequivocal population assessment based on aerial survey data.

Can parasitism by Tamarixia radiata (Hymenoptera: Eulophidae) affect the movement and oviposition behavior of Diaphorina citri (Hemiptera: Psyllidae)? - Juliana S. Oliveira; Carolina Reigada; Alexandre J.F. Diniz; Idemauro A.R. Lara; Rafael A. Moral; José R.P. Parra (Journal of Insect Behavior, 2022)

Identifying stakeholders and discussing a strategy for the participatory management of a protected area: the case of Engenho Pequeno, in Rio de Janeiro State, Brazil - Júlia de Marins Costa; Larry A. Swatuk; Alexandre Ferreira Lopes (Environment, Development and Sustainability, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

The Balkan terranes: a missing link between the eastern and western segments of the Avalonian–Cadomian orogenic belt? - Jiří Žák; Martin Svojtka; Ianko Gerdjikov; Alexandre Kounov; Dian A. Vangelov (International Geology Review, 2022)

In vitro and in silico cytotoxicity of hinokinin-loaded PLGA microparticle systems against tumoral SiHa cells - Regiane G. de Lima; Flavia C. R. Lisoni; Thais B. Picão; Fransérgio F. dos Santos; Renato P. Orenha; Alexandre Borges; Eduardo F. Molina; Renato L. T. Parreira; Márcio L. A. e Silva; Mario F. C. Santos; Rosangela da S. de Laurentiz (Natural Product Research, 2022)

A morphological study of Aristolochia holostylis (Aristolochiaceae) reveals the presence of a new species - Dominik Frank; Julio A. Lombardi; Alexandre K. Monro (Brittonia, 2022)

Function predicts the allometry of contest-related traits, but not sexual or male dimorphism in the amazonian tusked harvestman - Alexandre V. Palaoro; Solimary García-Hernández; Bruno A. Buzatto; Glauco Machado (Evolutionary Ecology, 2022)

Arsenic in Caribbean bivalves in the context of Sargassum beachings: A new risk for seafood consumers - Emma Modestin; Damien A. Devault; Alexandre Baylet; Félix Massat; Franck Dolique (Environmental Monitoring and Assessment, 2022)

Diffusion of H 2 S from anaerobic thiolated ligand biodegradation rapidly generates bioavailable mercury - Benjamin R. Stenzler; Rui Zhang; Jeremy D. Semrau; Alan A. DiSpirito; Alexandre J. Poulain (Environmental Microbiology, 2022)
Summary Methylmercury is a potent neurotoxin that biomagnifies through food webs and which production depends on anaerobic microbial uptake of inorganic mercury (Hg) species. One outstanding knowledge gap in understanding Hg methylation is the nature of bioavailable Hg species. It has become increasingly obvious that Hg bioavailability is spatially diverse and temporally dynamic but current models are mostly built on single thiolated ligand systems, omitting ligand exchanges and interactions, or the inclusion of dissolved gaseous phases. In this study, we used a whole‐cell anaerobic biosensor to determine the role of a mixture of thiolated ligands on Hg bioavailability. Serendipitously, we discovered how the diffusion of trace amounts of exogenous biogenic H 2 S, originating from anaerobic microbial ligand degradation, can alter Hg speciation – away from H 2 S production site – to form bioavailable species. Regardless of its origins, H 2 S stands as a mobile mediator of microbial Hg metabolism, connecting spatially separated microbial communities. At a larger scale, global planetary changes are expected to accelerate the production and mobilization of H 2 S and Hg, possibly leading to increased production of the potent neurotoxin; this work provides mechanistic insights into the importance of co‐managing biogeochemical cycle disruptions.

Exploring the Use of Seabirds as a Dynamic Ocean Management Tool to Mitigate Anthropogenic Risk to Large Whales - Tammy L. Silva; Kevin D. Powers; Jooke Robbins; Regina Asmutis-Silvia; Timothy V. N. Cole; Alex N. Hill; Laura J. Howes; Charles A. Mayo; Dianna Schulte; Michael A. Thompson; Linda J. Welch; Alexandre N. Zerbini; et al. (Frontiers in Marine Science, 2022)
Vessel strike and entanglement in fishing gear are global threats to large whales. United States management actions to reduce human-induced serious injury and mortality to large whales have been inadequate, partially due to static, spatial protection schemes that fail to adjust to distribution shifts of highly mobile animals. Whale conservation would benefit from dynamic ocean management, but few tools exist to inform dynamic approaches. Seabirds are often found in association with whales and can be tagged at lower cost and in higher numbers than whales. We explored the use of satellite-tagged seabirds (great shearwaters) as dynamic ocean management tools for near real-time identification of habitats where humpback and North Atlantic right whales aggregate, potentially increasing anthropogenic risk. We identified shearwater habitat use areas in the Gulf of Maine with 50% kernel density utilization distributions at yearly, monthly, and weekly scales using satellite-telemetry data from 2013-2018. We quantified overlap using whale sightings and whale satellite telemetry data at two spatial scales: Stellwagen Bank National Marine Sanctuary and the Gulf of Maine. Within the sanctuary, shearwaters overlapped with >50% of humpback sightings in 4 of 6 (67%) years, 15 of 23 (65%) months, and 50 of 89 (56%) of weeks. At the Gulf of Maine scale, shearwater use areas overlapped >50% of humpback sightings in 5 of 6 years (83%) and 16 of 22 (73%) months, and encompassed humpback 50% utilization distributions (based on satellite telemetry) in 2 of 3 (66%) years and 7/12 (58%) months analyzed. Overlap between shearwaters and right whales was much lower, with >50% overlap in only 1 of 6 (17%) years and 3 of 23 (13%) months. These initial results demonstrate that satellite-tagged shearwaters can be indicators of humpback whale habitat use in both space and time. With further study, tagged shearwaters may provide near-real time information necessary to operationalize dynamic management to mitigate human impacts on humpback whales.

Role of 5-HT2A receptors in the effects of ayahuasca on ethanol self-administration using a two-bottle choice paradigm in male mice - Yasmim A. Serra; Thaísa Barros-Santos; Alexia Anjos-Santos; Natali D. Kisaki; Caio Jovita-Farias; João P. C. Leite; Maria C. E. Santana; João P. S. A. Coimbra; Nailton M. S. de Jesus; Agnieszka Sulima; Paulo C. R. Barbosa; Elena L. A. Malpezzi-Marinho; et al. (Psychopharmacology, 2022)

Activation of Neuropeptide Y2 Receptor Can Inhibit Global Cerebral Ischemia-Induced Brain Injury - Reggie Hui-Chao Lee; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Alexandre Couto e Silva; Harlee E. Possoit; Garrett A. Clemons; Christina H. Acosta; Victoria A. de la Llama; Jake T. Neumann; Hung Wen Lin (NeuroMolecular Medicine, 2022)

Spatio‐temporal evolution of the catuaba clade in the Neotropics: Morphological shifts correlate with habitat transitions - Maria Fernanda Calió; Verônica A. Thode; Christine D. Bacon; Daniele Silvestro; Alexandre Antonelli; Lúcia G. Lohmann (Journal of Biogeography, 2022)
Aim The biotic assembly of one of the most species‐rich savannas, the Brazilian Cerrado, has involved recruitment of lineages from several surrounding regions. However, we lack a clear understanding about the timing and pathways of biotic exchanges among these regions and about the role those interchanges had in the assembly of Neotropical biodiversity. We investigated the timing and routes of species movements between wet or seasonally dry habitats across Neotropical regions and assessed the potential for ecological adaptation by evaluating the habitat transitions correlated with morphological shifts. Location Neotropics. Taxon The plant genus Anemopaegma (Bignonieae, Bignoniaceae). Methods We inferred a Bayesian molecular phylogeny of Anemopaegma using one nuclear and two chloroplast markers. We sampled more than 90% of the known species diversity of Anemopaegma , covering its full geographical range. We estimated divergence times using a Bayesian relaxed‐clock approach and inferred ancestral ranges as well as shifts in habitat and morphological characters. Results Phylogenetic analyses recovered seven main clades within Anemopaegma . The genus likely originated in Amazonia in the late Oligocene. Early‐diverging lineages diversified in situ in Amazonia, particularly during the Miocene, with independent dispersal events to the Andes, Atlantic Forest and Cerrado. Shifts from seasonally dry forest to savanna habitats were correlated with shifts from liana to shrub and the loss of tendrils. Main Conclusions The timing of diversification of major lineages within Anemopaegma is consistent with major geological and climatic events that occurred during the late Palaeogene and Neogene, such as the Andean uplift and the Middle Miocene Climatic Optimum. Movements across different regions within the Neotropics were relatively common but shifts between habitats were not. The correlation in the evolution of the shrubby habit, the loss of tendrils and the shifts from forest to savanna are consistent with a scenario of ecological adaptation.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Correction to: Use of meat resources in the Early Pleistocene assemblages from Fuente Nueva 3 (Orce, Granada, Spain) - José Yravedra; José Antonio Solano; Lloyd A. Courtenay; Juha Saarinen; Gonzalo Linares‑Matás; Carmen Luzón; Alexia Serrano‑Ramos; Darío Herranz‑Rodrigo; José Miguel Cámara; Auxiliadora Ruiz; Stefania Titton; Juan José Rodríguez‑Alba; et al. (Archaeological and Anthropological Sciences, 2022)

First satellite‐tracked movements of pygmy blue whales ( Balaenoptera musculus brevicauda ) in New Zealand waters - Kimberly T. Goetz; Simon J. Childerhouse; David Paton; Mike Ogle; Krista van der Linde; Rochelle Constantine; Michael C. Double; Virginia Andrews‐Goff; Alexandre N. Zerbini; Paula A. Olson (Marine Mammal Science, 2022)

Baccharis trimera (Less.) DC leaf derivatives and eupatorin activities against Leishmania amazonensis - Esther Della Nina Sahid; Josiane Clarice Claudino; Fernando Bombarda Oda; Flávio Alexandre Carvalho; André Gonzaga dos Santos; Marcia A. S. Graminha; Leandro da Costa Clementino (Natural Product Research, 2022)

A dosimetric comparison of CT- and photogrammetry- generated 3D printed HDR brachytherapy surface applicators - Corey A. Bridger; Paul D. Reich; Alexandre M. Caraça Santos; Michael J. J. Douglass (Physical and Engineering Sciences in Medicine, 2022)

Extreme storms in Southwest Asia (Northern Arabian Peninsula) under current and future climates - Alexandre Tuel; Yeon-Woo Choi; Duaij AlRukaibi; Elfatih A. B. Eltahir (Climate Dynamics, 2022)

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Ergogenic potential of foods for performance and recovery: a new alternative in sports supplementation? A systematic review - Matheus S. Costa; Luciana T. Toscano; Lydiane de Lima Tavares Toscano; Vanessa R. Luna; Rayanne A. Torres; Janilson A. Silva; Alexandre S. Silva (Critical Reviews in Food Science and Nutrition, 2022)

Optimization of Ozonation Process to Remove Psychoactive Drugs from Two Municipal Wastewater Treatment Plants - Deivisson L. Cunha; Alexandre S. A. da Silva; Rodrigo Coutinho; Marcia Marques (Water, Air, & Soil Pollution, 2022)

Long distance pollen dispersal and intrapopulation genetic structure determined by clonal diversity in Hymenaea stigonocarpa populations of the Brazilian savanna - Maria A. Moreno; David Boshier; Roberto Tarazi; Evandro V. Tambarussi; Bruna I. Aguiar; Elza M. Ferraz; Paulo Y. Kageyama; Alexandre M. Sebbenn (Trees, 2022)

Certification of açaí agroforestry increases the conservation potential of the Amazonian tree flora - Gabriel Damasco; Mandy Anhalt; Ricardo O. Perdiz; Florian Wittmann; Rafael L. de Assis; Jochen Schöngart; Maria T. F. Piedade; Christine D. Bacon; Alexandre Antonelli; Paul V. A. Fine (Agroforestry Systems, 2022)
The harvesting of açaí berries (palm fruits from the genus Euterpe ) in Amazonia has increased over the last 20 years due to a high local and global market demand and triggered by their widely acclaimed health benefits as a ‘superfood’. Although such increase represents a financial boom for local communities, unregulated extraction in Amazonia risks negative environmental effects including biodiversity loss through açai intensification and deforestation. Alternatively, the introduction of certified sustainable agroforestry production programs of açaí has been strategically applied to reduce the exploitation of Amazonian forests. Local açaí producers are required to follow principles of defined sustainable management practices, environmental guidelines, and social behaviors, paying specific attention to fair trade and human rights. In this study we investigate whether sustainable agroforestry and certification effectively promotes biodiversity conservation in Amazonia. To address this question, we conducted a forestry inventory in two hectares of long-term certified açai harvesting areas to gain further knowledge on the plant diversity and forest structure in açaí managed forests and to understand the contribution of certification towards sustainable forest management. On average, we found that certified managed forests harbor 50% more tree species than non-certified açaí groves. Trees in certified areas also have significantly higher mean basal area, meaning larger and hence older individuals are more likely to be protected. Certified harvesting sites also harbor dense populations of threatened species as classified by the International Union for Conservation of Nature (e.g. Virola surinamensis, classified as ‘endangered’). Besides increasing the knowledge of plant diversity in açaí managed areas, we present baseline information for monitoring the impact of harvesting activities in natural ecosystems in Amazonia.

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Arsenic and chlordecone contamination and decontamination toxicokinetics in Sargassum sp. - Damien A. Devault; Félix Massat; Alexandre Baylet; Franck Dolique; Pascal-Jean Lopez (Environmental Science and Pollution Research, 2022)

Recovery from Severe Mistletoe Infection After Heat- and Drought-Induced Mistletoe Death - Anne Griebel; Daniel Metzen; Elise Pendall; Rachael H. Nolan; Hamish Clarke; Alexandre A. Renchon; Matthias M. Boer (Ecosystems, 2022)

Estimating Bycatch Mortality for Marine Mammals: Concepts and Best Practices - Jeffrey E. Moore; Dennis Heinemann; Tessa B. Francis; Philip S. Hammond; Kristy J. Long; André E. Punt; Randall R. Reeves; Maritza Sepúlveda; Guðjón Már Sigurðsson; Margaret C. Siple; Gísli A. Víkingsson; Paul R. Wade; et al. (Frontiers in Marine Science, 2021)
Fisheries bycatch is the greatest current source of human-caused deaths of marine mammals worldwide, with severe impacts on the health and viability of many populations. Recent regulations enacted in the United States under the Fish and Fish Product Import Provisions of its Marine Mammal Protection Act require nations with fisheries exporting fish and fish products to the United States (hereafter, “export fisheries”) to have or establish marine mammal protection standards that are comparable in effectiveness to the standards for United States commercial fisheries. In many cases, this will require estimating marine mammal bycatch in those fisheries. Bycatch estimation is conceptually straightforward but can be difficult in practice, especially if resources (funding) are limiting or for fisheries consisting of many, small vessels with geographically-dispersed landing sites. This paper describes best practices for estimating bycatch mortality, which is an important ingredient of bycatch assessment and mitigation. We discuss a general bycatch estimator and how to obtain its requisite bycatch-rate and fisheries-effort data. Scientific observer programs provide the most robust bycatch estimates and consequently are discussed at length, including characteristics such as study design, data collection, statistical analysis, and common sources of estimation bias. We also discuss alternative approaches and data types, such as those based on self-reporting and electronic vessel-monitoring systems. This guide is intended to be useful to managers and scientists in countries having or establishing programs aimed at managing marine mammal bycatch, especially those conducting first-time assessments of fisheries impacts on marine mammal populations.

Using semi-latin square design for screening and comparison of local and improved Zea maize varieties tolerant to climate change in centre of Benin (West Africa) - Assota Bonanventure; Gbemavo D. S. J. Charlemagne; Adjahossou Naesse; Laly Judicael; Gbaguidi A. Anicet; Moussa A. Alio; Dansi A. Alexandre (Journal of Crop Science and Biotechnology, 2021)

Use of meat resources in the Early Pleistocene assemblages from Fuente Nueva 3 (Orce, Granada, Spain) - José Yravedra; José Antonio Solano; Lloyd A. Courtenay; Juha Saarinen; Gonzalo Linares-Matás; Carmen Luzón; Alexia Serrano-Ramos; Darío Herranz-Rodrigo; José Miguel Cámara; Auxiliadora Ruiz; Stefania Titton; Juan José Rodríguez-Alba; et al. (Archaeological and Anthropological Sciences, 2021)
Over the last few decades, several types of evidence such as presence of hominin remains, lithic assemblages, and bones with anthropogenic surface modifications have demonstrated that early human communities inhabited the European subcontinent prior to the Jaramillo Subchron (1.07–0.98 Ma). While most studies have focused primarily on early European lithic technologies and raw material management, relatively little is known about food procurement strategies. While there is some evidence showing access to meat and other animal-based food resources, their mode of acquisition and associated butchery processes are still poorly understood. This paper presents a taphonomic and zooarchaeological analysis of the Fuente Nueva-3 (FN3) (Guadix-Baza, Spain) faunal assemblage, providing a more in-depth understanding of early hominin subsistence strategies in Europe. The present results show that hominins had access to the meat and marrow of a wide range of animal taxa, including elephants, hippopotami, and small- and medium-sized animals. At the same time, evidence of carnivore activity at the site suggests that these communities likely faced some degree of competition from large predators when acquiring and processing carcasses.

Livestock activities in agroforestry systems in Guadeloupe: systems of production and functions - G. Alexandre; A. Cheval; J. Perrette; M. Apatout; J. L. Diman; A. Larade; A. Vinglassalon (Agroforestry Systems, 2021)

Best Practices for Assessing and Managing Bycatch of Marine Mammals - Paul R. Wade; Kristy J. Long; Tessa B. Francis; André E. Punt; Philip S. Hammond; Dennis Heinemann; Jeffrey E. Moore; Randall R. Reeves; Maritza Sepúlveda; Genoa Sullaway; Guðjón Már Sigurðsson; Margaret C. Siple; et al. (Frontiers in Marine Science, 2021)
Bycatch in marine fisheries is the leading source of human-caused mortality for marine mammals, has contributed to substantial declines of many marine mammal populations and species, and the extinction of at least one. Schemes for evaluating marine mammal bycatch largely rely on estimates of abundance and bycatch, which are needed for calculating biological reference points and for determining conservation status. However, obtaining these estimates is resource intensive and takes careful long-term planning. The need for assessments of marine mammal bycatch in fisheries is expected to increase worldwide due to the recently implemented Import Provisions of the United States Marine Mammal Protection Act. Managers and other stakeholders need reliable, standardized methods for collecting data to estimate abundance and bycatch rates. In some cases, managers will be starting with little or no data and no system in place to collect data. We outline a comprehensive framework for managing bycatch of marine mammals. We describe and provide guidance on (1) planning for an assessment of bycatch, (2) collecting appropriate data (e.g., abundance and bycatch estimates), (3) assessing bycatch and calculating reference points, and (4) using the results of the assessment to guide marine mammal bycatch reduction. We also provide a brief overview of available mitigation techniques to reduce marine mammal bycatch in various fisheries. This paper provides information for scientists and resource managers in the hope that it will lead to new or improved programs for assessing marine mammal bycatch, establishing best practices, and enhancing marine mammal conservation globally.

Diffusion MRI data, sulcal anatomy, and tractography for eight species from the Primate Brain Bank - Katherine L. Bryant; Dirk Jan Ardesch; Lea Roumazeilles; Lianne H. Scholtens; Alexandre A. Khrapitchev; Benjamin C. Tendler; Wenchuan Wu; Karla L. Miller; Jerome Sallet; Martijn P. van den Heuvel; Rogier B. Mars (Brain Structure and Function, 2021)
Large-scale comparative neuroscience requires data from many species and, ideally, at multiple levels of description. Here, we contribute to this endeavor by presenting diffusion and structural MRI data from eight primate species that have not or rarely been described in the literature. The selected samples from the Primate Brain Bank cover a prosimian, New and Old World monkeys, and a great ape. We present preliminary labelling of the cortical sulci and tractography of the optic radiation, dorsal part of the cingulum bundle, and dorsal parietal–frontal and ventral temporal-frontal longitudinal white matter tracts. Both dorsal and ventral association fiber systems could be observed in all samples, with the dorsal tracts occupying much less relative volume in the prosimian than in other species. We discuss the results in the context of known primate specializations and present hypotheses for further research. All data and results presented here are available online as a resource for the scientific community.

Benzophenone and Diethyl Phthalate Removal from Real Wastewater by a Multi-stage Hybrid Reactor - Amanda F. do Amaral; Alexandre S. A. da Silva; Rodrigo Coutinho; Deivisson L. Cunha; Marcia Marques (Water, Air, & Soil Pollution, 2021)

Anxiolytic-like effect of natural product 2-hydroxy-3,4,6-trimethoxyacetophenone isolated from Croton anisodontus in adult zebrafish via serotonergic neuromodulation involvement of the 5-HT system - Antonio Wlisses da Silva; Maria Kueirislene A. Ferreira; Emanuela L. Rebouças; Francisco Rogenio S. Mendes; Atilano Lucas dos S. Moura; Jane Eire S. A. de Menezes; Márcia Machado Marinho; Emmanuel Silva Marinho; Hélcio S. Santos; Alexandre M. R. Teixeira (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Multiple lionfish (Pterois spp.) new occurrences along the Brazilian coast confirm the invasion pathway into the Southwestern Atlantic - Osmar J. Luiz; Wagner C. R. dos Santos; Alexandre P. Marceniuk; Luiz A. Rocha; Sergio R. Floeter; Clara E. Buck; Alex G. C. M. de Klautau; Carlos E. L. Ferreira (Biological Invasions, 2021)

Molecular characterization of a putative new cavemovirus isolated from wild chicory (Cichorium intybus) - Leonardo A. Silva; Brenda R. de Camargo; Marcelo Eiras; Alexandre L. R. Chaves; Bergmann M. Ribeiro (Archives of Virology, 2021)

Epidemiological features of the first Unusual Mortality Event linked to cetacean morbillivirus in the South Atlantic (Brazil, 2017–2018) - Haydée A. Cunha; Elitieri B. Santos‐Neto; Rafael R. Carvalho; Joana M. P. Ikeda; Katia R. Groch; Josué Díaz‐Delgado; Emi B. Guari; Juliana A. Brião; Raissa B. Oliveira; Leonardo Flach; Tatiana L. Bisi; José L. Catão‐Dias; et al. (Marine Mammal Science, 2021)
Since the 1980s, cetacean morbillivirus (CeMV) has caused mass mortality events worldwide. However, no epizootics had been recorded in the South Atlantic, until an unusual mortality event (UME) linked to Guiana dolphin cetacean morbillivirus (GD‐CeMV) began in Ilha Grande Bay, southeastern Brazil, in November 2017. In a five‐month period, the UME spread to neighboring Sepetiba Bay and accounted for the death of at least 277 Guiana dolphins ( Sotalia guianensis ). Prevalence of morbillivirus positive dolphins, as estimated from RT‐PCR diagnostics, was 92.3% (24/26) in Ilha Grande Bay and 91.9% (57/62) in Sepetiba Bay. Females had higher mortality rates during the UME (1.5:1), in contrast with historical mortality data from both bays that showed a 2:1 male to female death ratio. Calf mortality rates also increased in both bays. These results suggest that females and calves were more vulnerable to morbilliviral infection. Herein, we discuss possible explanations for such sex‐biased death pattern during the UME and their implication for the conservation of endangered Guiana dolphins. We also speculate about the origin and spread of morbillivirus in the South Atlantic Ocean.

Albatrosses respond adaptively to climate variability by changing variance in a foraging trait - Samantha C. Patrick; Julien G. A. Martin; Caroline C. Ummenhofer; Alexandre Corbeau; Henri Weimerskirch (Global Change Biology, 2021)
The ability of individuals and populations to adapt to a changing climate is a key determinant of population dynamics. While changes in mean behaviour are well studied, changes in trait variance have been largely ignored, despite being assumed to be crucial for adapting to a changing environment. As the ability to acquire resources is essential to both reproduction and survival, changes in behaviours that maximize resource acquisition should be under selection. Here, using foraging trip duration data collected over 7 years on black‐browed albatrosses ( Thalassarche melanophris ) on the Kerguelen Islands in the southern Indian Ocean, we examined the importance of changes in the mean and variance in foraging behaviour, and the associated effects on fitness, in response to the El Niño Southern Oscillation (ENSO). Using double hierarchical models, we found no evidence that individuals change their mean foraging trip duration in response to a changing environment, but found strong evidence of changes in variance. Younger birds showed greater variability in foraging trip duration in poor conditions as did birds with higher fitness. However, during brooding, birds showed greater variability in foraging behaviour under good conditions, suggesting that optimal conditions allow the alteration between chick provisioning and self‐maintenance trips. We found weak correlations between sea surface temperature and the ENSO, but stronger links with sea‐level pressure. We suggest that variability in behavioural traits affecting resource acquisition is under selection and offers a mechanism by which individuals can adapt to a changing climate. Studies which look only at effects on mean behaviour may underestimate the effects of climate change and fail to consider variance in traits as a key evolutionary force.

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Assessment of ecosystem services provided by livestock agroecosystems in the tropics: a case study of tropical island environment of Guadeloupe - J.-L. Gourdine; A. Fourcot; C. Lefloch; M. Naves; G. Alexandre (Tropical Animal Health and Production, 2021)
The present study aims to assess (1) the ecosystem services (ES) provided by LFS and (2) the differential ES between local (Creole) and exotic breeds from pig, cattle and goat. The ES are defined as the benefits that humans derive from LFS. They were summarized in 12 ES indicators that cover services related to provisioning, ecological and socio-cultural aspects and territorial vitality. A total of 106 LFS units that covers the five agroecological zones of Guadeloupe were analysed. Functional typologies of LFS per species were created from surveys. The effect of breed on the ES indicators was tested. Results showed that the 40 pig LFS units were separated into 3 clusters that were differentiated in ES according to provisioning ES (cluster 1), cultural use and sale to the neighborhood (cluster 2) and pork self-consumption (cluster 3). The typology of the 57 farms with cattle distinguished 4 clusters with differences in ES provided in self-consumption (cluster1), ecological ES (cluster 2), socio-cultural ES for racing or draught oxen (cluster 3) and ES associated with territory vitality (cluster 4). The 66 goat LFS units were classified into 3 clusters different in ES concerning self-consumption (cluster 1), cultural aspects (cluster 2) and provisioning ES (cluster 3). Our study highlights that ES indicators are not breed dependent ( P > 0.10) but rather livestock farming system dependent. The ES rely more on the rearing management than on the breed type, and up to now, there are no specifications in Guadeloupe to differentiate management between breeds.

Correction to: Fungal biodegradation and removal of cyanobacteria and microcystins: potential applications and research needs - Zakaria A. Mohamed; Mohamed Hashem; Saad Alamri; Alexandre Campos; Vitor Vasconcelos (Environmental Science and Pollution Research, 2021)

Influence of high temperatures on physical properties and microstructure of gneiss - K. O. B. Costa; G. C. Xavier; M. T. Marvila; J. Alexandre; A. R. G. Azevedo; S. N. Monteiro (Bulletin of Engineering Geology and the Environment, 2021)

Plant growth–promoting traits of yeasts isolated from the tank bromeliad Vriesea minarum L.B. Smith and the effectiveness of Carlosrosaea vrieseae for promoting bromeliad growth - Andréa R. Marques; Alessandra A. Resende; Fátima C. O. Gomes; Ana Raquel O. Santos; Carlos A. Rosa; Alexandre A. Duarte; José Pires de Lemos-Filho; Vera Lúcia dos Santos (Brazilian Journal of Microbiology, 2021)

Glass ionomer cement modified by a imidazolium salt: adding antifungal properties to a biomaterial - Alexandre Ehrhardt; Jéssica Zolim Andreatto Mandelli; Vanessa Bérgamo; William Lopes; Ricardo Keitel Donato; Régis A. Zanette; Alexandre Meneghello Fuentefria (Brazilian Journal of Microbiology, 2021)

Complete genome sequence and analysis of a Saccharomyces cerevisiae strain used for sugarcane spirit production - Ane Catarine Tosi Costa; Jacob Hornick; Tathiana Ferreira Sá Antunes; Alexandre Martins Costa Santos; A Alberto R. Fernandes; James R. Broach; Patricia M. B. Fernandes (Brazilian Journal of Microbiology, 2021)

The Brazilian Cerrado is becoming hotter and drier - Gabriel S. Hofmann; Manoel F. Cardoso; Ruy J. V. Alves; Eliseu J. Weber; Alexandre A. Barbosa; Peter M. de Toledo; Francisco B. Pontual; Leandro de O. Salles; Heinrich Hasenack; José L. P. Cordeiro; Francisco E. Aquino; Luiz F. B. de Oliveira (Global Change Biology, 2021)
The Brazilian Cerrado is a global biodiversity hotspot with notoriously high rates of native vegetation suppression and wildfires over the past three decades. As a result, climate change can already be detected at both local and regional scales. In this study, we used three different approaches based on independent datasets to investigate possible changes in the daytime and nighttime temperature and air humidity between the peak of the dry season and the beginning of the rainy season in the Brazilian Cerrado. Additionally, we evaluated the tendency of dew point depression, considering it as a proxy to assess impacts on biodiversity. Monthly increases of 2.2−4.0℃ in the maximum temperatures and 2.4−2.8℃ in the minimum temperatures between 1961 and 2019 were recorded, supported by all analyzed datasets which included direct observations, remote sensing, and modeling data. The warming raised the vapor pressure deficit, and although we recorded an upward trend in absolute humidity, relative humidity has reduced by ~15%. If these tendencies are maintained, gradual air warming will make nightly cooling insufficient to reach the dew point in the early hours of the night. Therefore, it will progressively reduce both the amount and duration of nocturnal dewfall, which is the main source of water for numerous plants and animal species of the Brazilian Cerrado during the dry season. Through several examples, we hypothesize that these climate changes can have a high impact on biodiversity and potentially cause ecosystems to collapse. We emphasize that the effects of temperature and humidity on Cerrado ecosystems cannot be neglected and should be further explored from a land use perspective.

Systematics of Brucepattersonius Hershkovitz, 1998 (Rodentia, Sigmodontinae): molecular species delimitation and morphological analyses suggest an overestimation in species diversity - Edson Fiedler Abreu; Diego Marques Henriques Jung; Alexandre Uarth Christoff; Victor Hugo Valiati; Sharon A. Jansa; Alexandre Reis Percequillo (Systematics and Biodiversity, 2021)

Effect of temperature on Colletotrichum truncatum growth, and evaluation of its inoculum potential in soybean seed germination - Manoel Batista da Silva Júnior; Mário Lúcio Vilela Resende; Edson A. Pozza; José da Cruz Machado; Alexandre Ribeiro Maia de Resende; Acleide Maria Santos Cardoso; Sarah da Silva Costa Guimarães; Deila Magna dos Santos Botelho (European Journal of Plant Pathology, 2021)

Regulatory approaches for genome edited agricultural plants in select countries and jurisdictions around the world - Jon Entine; Maria Sueli S. Felipe; Jan-Hendrik Groenewald; Drew L. Kershen; Martin Lema; Alan McHughen; Alexandre Lima Nepomuceno; Ryo Ohsawa; Reynante L. Ordonio; Wayne A. Parrott; Hector Quemada; Carl Ramage; et al. (Transgenic Research, 2021)
Genome editing in agriculture and food is leading to new, improved crops and other products. Depending on the regulatory approach taken in each country or region, commercialization of these crops and products may or may not require approval from the respective regulatory authorities. This paper describes the regulatory landscape governing genome edited agriculture and food products in a selection of countries and regions.

Contrasting patterns of phylogenetic turnover in amphibians and reptiles are driven by environment and geography in Neotropical savannas - Josué A. R. Azevedo; Cristiano de C. Nogueira; Alexandre Antonelli; Søren Faurby (Journal of Biogeography, 2021)
Aim Cross‐taxonomic congruence in biodiversity patterns is key to understanding the main drivers of community structure, for biogeographical regionalization and to guide conservation. We aim to map the patterns of phylogenetic turnover and disentangle the geographical and environmental factors that drive the phylogenetic composition of distinct faunal assemblages. Location The Cerrado savannas of South America. Taxa Reptiles and amphibians. Methods We measured the proportion of phylogenetic branches shared among sites (i.e. phylogenetic turnover) using presence‐absence matrices for all species in the Cerrado and for endemics only, including only well‐sampled localities from previously compiled inventories. We then tested whether phylogenetic turnover is different from null expectations based on taxonomic turnover. We used generalized dissimilarity modelling (GDM) to test whether geography, topography, soil or climate best explain phylogenetic turnover. Finally, we mapped the observed and the GDM‐predicted clustering of phylogenetic turnover to assess geographical congruence between reptiles and amphibians. Results For all reptiles, geographical distance is the most important factor explaining phylogenetic turnover, whereas for endemic reptiles and amphibians, in general, a set of climatic variables and relief roughness are more important. We did not find any significant correlation between the phylogenetic turnover of reptiles and amphibians, as evidenced by non‐congruent phylogenetic clustering and by different responses to geographical and environmental gradients. Main conclusions The different relationships of phylogenetic turnover of reptiles and amphibians to geographical and environmental distances have ultimately shaped the phylogenetic regionalization of these two groups. This incongruence indicates the differential importance of niche filtering, dispersal limitation and the influence of neighbouring biomes in the regionalization of different groups of organisms. Therefore, diversity patterns of one group should ideally not be used as a surrogate to map general patterns or to understand the drivers of diversity of other co‐occurring groups. Thus, conservation efforts need to be designed and implemented for each organismal group.

Co-occurrences of tropical trees in eastern South America: disentangling abiotic and biotic forces - Emma-Liina Marjakangas; Otso Ovaskainen; Nerea Abrego; Vidar Grøtan; Alexandre A. de Oliveira; Paulo I. Prado; Renato A. F. de Lima (Plant Ecology, 2021)
Species co-occurrences in local communities can arise independent or dependent on species’ niches. However, the role of niche-dependent processes has not been thoroughly deciphered when generalized to biogeographical scales, probably due to combined shortcomings of data and methodology. Here, we explored the influence of environmental filtering and limiting similarity, as well as biogeographical processes that relate to the assembly of species’ communities and co-occurrences. We modelled jointly the occurrences and co-occurrences of 1016 tropical tree species with abundance data from inventories of 574 localities in eastern South America. We estimated species co-occurrences as raw and residual associations with models that excluded and included the environmental effects on the species’ co-occurrences, respectively. Raw associations indicate co-occurrence of species, whereas residual associations indicate co-occurrence of species after accounting for shared responses to environment. Generally, the influence of environmental filtering exceeded that of limiting similarity in shaping species’ co-occurrences. The number of raw associations was generally higher than that of the residual associations due to the shared responses of tree species to the environmental covariates. Contrary to what was expected from assuming limiting similarity, phylogenetic relatedness or functional similarity did not limit tree co-occurrences. The proportions of positive and negative residual associations varied greatly across the study area, and we found a significant tendency of some biogeographical regions having higher proportions of negative associations between them, suggesting that large-scale biogeographical processes limit the establishment of trees and consequently their co-occurrences.

Fungal biodegradation and removal of cyanobacteria and microcystins: potential applications and research needs - Zakaria A. Mohamed; Mohamed Hashem; Saad Alamri; Alexandre Campos; Vitor Vasconcelos (Environmental Science and Pollution Research, 2021)

Occurrence but not intensity of mortality rises towards the climatic trailing edge of tree species ranges in European forests - Alexandre Changenet; Paloma Ruiz‐Benito; Sophia Ratcliffe; Thibaut Fréjaville; Juliette Archambeau; Annabel J. Porte; Miguel A. Zavala; Jonas Dahlgren; Aleksi Lehtonen; Marta Benito Garzón (Global Ecology and Biogeography, 2021)
Aim Tree mortality is increasing world‐wide, leading to changes in forest composition and altering global biodiversity. Nonetheless, owing to the multifaceted stochastic nature of tree mortality, large‐scale spatial patterns of mortality across species ranges and their underlying drivers remain difficult to understand. Our main goal was to describe the geographical patterns and drivers of the occurrence of mortality (presence of a mortality event) and the intensity of tree mortality (amount of mortality related to that mortality event) in Europe. We hypothesized that the occurrence of mortality represents background mortality and is higher in the margin than in core populations, whereas the intensity of mortality could have a more even distribution according to the spatial and temporal stochasticity of die‐off events. Location Europe (Spain, France, Germany, Belgium, Sweden and Finland). Major taxa studied More than 1.5 million trees belonging to 20 major forest tree species. Methods We developed binomial and truncated negative binomial models to tease apart the occurrence and intensity of tree mortality in National Forest Inventory plots at the range‐wide scale. The occurrence of mortality indicated that at least one tree had died in the plot, whereas the intensity of mortality referred to the number of dead trees per plot. Results The highest occurrence of mortality was found in peripheral regions and the climatic trailing edge linked with drought, whereas the intensity of mortality was driven by competition, drought and high temperatures and was scattered uniformly across species ranges. Main conclusions We show that tree background mortality, but not die‐off, is generally higher in the trailing‐edge populations. It remains to be explored whether other demographic traits, such as growth, reproduction and regeneration, also decrease at the trailing edge of European tree populations.

Strain Evolution and Instability of an Anticyclonic Eddy From a Laboratory Experiment - Guoqing Han; Changming Dong; Jingsong Yang; Joel Sommeria; Alexandre Stegner; Rui M. A. Caldeira (Frontiers in Marine Science, 2021)
Using the 13 m diameter LEGI-Coriolis rotating platform, the evolution processes of a generated anticyclonic eddy throughout its lifecycle are analyzed. Experimental results have shown that the eddy lasted for approximately 3 T 0 , where T 0 is the rotating period of 90 s. After T = 0.3 T 0 , the eddy enters its mature phase, whereby following this event, eddy intensity slowly decreases from its maximum rotation speed. By T = 2.6 T 0 , the eddy enters a stage of rapid weakening. In its decay period, two underlying mechanisms for this decay have been identified as inertial instability and eddy–eddy interactions.

Evaluation of camera settings for photogrammetric reconstruction of humanoid phantoms for EBRT bolus and HDR surface brachytherapy applications - Corey A. Bridger; Michael J. J. Douglass; Paul D. Reich; Alexandre M. Caraça Santos (Physical and Engineering Sciences in Medicine, 2021)

Using a machine learning proxy for localization in ensemble data assimilation - Johann M. Lacerda; Alexandre A. Emerick; Adolfo P. Pires (Computational Geosciences, 2021)

Annotated checklist of the birds of Brazil by the Brazilian Ornithological Records Committee—second edition - José Fernando Pacheco; Luís Fábio Silveira; Alexandre Aleixo; Carlos Eduardo Agne; Glayson A. Bencke; Gustavo A. Bravo; Guilherme R. R. Brito; Mario Cohn-Haft; Giovanni Nachtigall Maurício; Luciano N. Naka; Fabio Olmos; Sérgio R. Posso; et al. (Ornithology Research, 2021)

First detailed insights into the life‐history traits of the alien shrimp Athanas nitescens (Decapoda: Alpheidae) in the western Atlantic - Régis A. Pescinelli; Fernando L. Mantelatto; Alexandre O. Almeida; Rogerio C. Costa (Marine Ecology, 2021)
Information on the population biology of alien species in non‐natural areas is essential to understanding their impacts on native species. Here, we investigated the life‐history traits, the propagule pressure and the supply potential of Athanas nitescens in a non‐native area. Sampling was monthly performed from April 2015 to March 2016 in an inter‐tidal estuary in the south‐eastern Brazilian coast. The population had a female‐biased sex ratio with a predominance of ovigerous females. Sexual dimorphism was evidenced by the mean body size and the positive allometry of chelipeds in males and of the second pleonal pleuron in females, evidencing an energy allocation to weaponry body structures and reproduction, respectively. The estimated size at which 50% of females reach functional sexual maturity was 3.3 mm of carapace length. The mean fecundity, 117 ± 40.03 eggs/female (53–263), had a positive correlation with the carapace length. The egg volume increased (83%) from the initial to the final stage of development. The presence of females carrying eggs in different stages of development indicates that A . nitescens is completing its life cycle in the studied region and shows a high propagule pressure. We provided the first insights into the biology of A . nitescens in Brazilian waters after the first record in 2009 in São Paulo coast, contributing to a better understanding of its biology and ecology in non‐natural areas.

Systematics and biogeography of the Boana albopunctata species group (Anura, Hylidae), with the description of two new species from Amazonia - Antoine Fouquet; Pedro Marinho; Alexandre Réjaud; Thiago R. Carvalho; Marcel A. Caminer; Martin Jansen; Raíssa N. Rainha; Miguel T. Rodrigues; Fernanda P. Werneck; Albertina P. Lima; Tomas Hrbek; Ariovaldo A. Giaretta; et al. (Systematics and Biodiversity, 2021)

Metabolic status is not associated with job stress in individuals with obesity: the ELSA-Brasil baseline - Lia Imbiriba; Beatriz H. Tess; Rosane H. Griep; Maria J. M. Fonseca; Alexandre C. Pereira; Maria F. S. Diniz; Paulo A. Lotufo; Isabela M. Bensenor; Itamar S. Santos (International Archives of Occupational and Environmental Health, 2021)

Detection and application of novel SSR markers from transcriptome data for Astronium fraxinifolium Schott, a threatened Brazilian tree species - Maiara R. Cornacini; Ricardo O. Manoel; Marcelo A. M. Alcantara; Mário L. T. Moraes; Edvaldo A. A. Silva; Leonel G. Pereira Neto; Alexandre M. Sebbenn; Bruno C. Rossini; Celso L. Marino (Molecular Biology Reports, 2021)

AMPAr GluA1 Phosphorylation at Serine 845 in Limbic System Is Associated with Cardiac Autonomic Tone - Hiago Murilo Melo; Cristiane Ribeiro de Carvalho; Alexandre Ademar Hoeller; Jefferson Luiz Brum Marques; Marcelo Neves Linhares; Mark William Lopes; Guilherme Loureiro Fialho; Peter Wolf; Katia Lin; Zuner A. Bortolotto; Jeremy M. Henley; André D’Ávila; et al. (Molecular Neurobiology, 2021)

Novelties in Lactifluus subg. Gymnocarpi (Russulales, Basidiomycota) from Brazilian tropical forests - Alexandre G. S. Silva-Filho; Mariana C. A. Sá; Dirce L. Komura; Iuri G. Baseia; Paulo Marinho; Jean-Marc Moncalvo; Mélanie Roy; Felipe Wartchow (Mycological Progress, 2021)

Shallow‐water habitat use and population parameters of rough‐toothed dolphins, Steno bredanensis ( G. Cuvier in Lesson, 1828) in southeastern Brazil - Rafael R. Carvalho; José Lailson‐Brito; Maja Kajin; Carlos Eduardo P. Quintana; Karina S. Pereira; Tatiana L. Bisi; Haydée A. Cunha; Alexandre F. Azevedo (Marine Mammal Science, 2021)
The rough‐toothed dolphin ( Steno bredanensis ) is a poorly known species along its distribution especially in the Southern Hemisphere where data on habitat use and population parameters are scarce. Boat‐based surveys were conducted from 2009 to 2017 in a shallow water environment in southeastern Brazil. During focal‐group observations, S. bredanensis was more commonly found in mean depths of 22 m with varying group size and composition. Generalized additive models showed that group size was influenced by environmental variables such as sea surface and bottom temperatures, depth, and season. Photo‐identification effort allowed us to catalogue 173 well‐distinct marked individuals. Estimates of population parameters showed high and constant survival (Φ = 0.99) corroborating site fidelity but time varying capture probabilities ( p = .03–.71). An open population model also indicated a small abundance estimate ( Nt = 218) of S. bredanensis in the study area, improving knowledge for this species in shallow water environments of the southwestern Atlantic Ocean.

Ten golden rules for reforestation to optimize carbon sequestration, biodiversity recovery and livelihood benefits - Alice Di Sacco; Kate A. Hardwick; David Blakesley; Pedro H. S. Brancalion; Elinor Breman; Loic Cecilio Rebola; Susan Chomba; Kingsley Dixon; Stephen Elliott; Godfrey Ruyonga; Kirsty Shaw; Paul Smith; et al. (Global Change Biology, 2021)
Urgent solutions to global climate change are needed. Ambitious tree‐planting initiatives, many already underway, aim to sequester enormous quantities of carbon to partly compensate for anthropogenic CO 2 emissions, which are a major cause of rising global temperatures. However, tree planting that is poorly planned and executed could actually increase CO 2 emissions and have long‐term, deleterious impacts on biodiversity, landscapes and livelihoods. Here, we highlight the main environmental risks of large‐scale tree planting and propose 10 golden rules, based on some of the most recent ecological research, to implement forest ecosystem restoration that maximizes rates of both carbon sequestration and biodiversity recovery while improving livelihoods. These are as follows: (1) Protect existing forest first; (2) Work together (involving all stakeholders); (3) Aim to maximize biodiversity recovery to meet multiple goals; (4) Select appropriate areas for restoration; (5) Use natural regeneration wherever possible; (6) Select species to maximize biodiversity; (7) Use resilient plant material (with appropriate genetic variability and provenance); (8) Plan ahead for infrastructure, capacity and seed supply; (9) Learn by doing (using an adaptive management approach); and (10) Make it pay (ensuring the economic sustainability of the project). We focus on the design of long‐term strategies to tackle the climate and biodiversity crises and support livelihood needs. We emphasize the role of local communities as sources of indigenous knowledge, and the benefits they could derive from successful reforestation that restores ecosystem functioning and delivers a diverse range of forest products and services. While there is no simple and universal recipe for forest restoration, it is crucial to build upon the currently growing public and private interest in this topic, to ensure interventions provide effective, long‐term carbon sinks and maximize benefits for biodiversity and people.

Recent developments combining ensemble smoother and deep generative networks for facies history matching - Smith W. A. Canchumuni; Jose D. B. Castro; Júlia Potratz; Alexandre A. Emerick; Marco Aurélio C. Pacheco (Computational Geosciences, 2021)

Understanding climate change over the southwestern Mediterranean using high-resolution simulations - Alexandre Tuel; Suchul Kang; Elfatih A. B. Eltahir (Climate Dynamics, 2021)

Cypermethrin- and fipronil-based insecticides cause biochemical changes in Physalaemus gracilis tadpoles - Camila F. Rutkoski; Natani Macagnan; Alexandre Folador; Vrandrieli J. Skovronski; Aline M. B. do Amaral; Jossiele Wesz Leitemperger; Maiara Dorneles Costa; Paulo A. Hartmann; Caroline Müller; Vania L. Loro; Marilia T. Hartmann (Environmental Science and Pollution Research, 2021)

Asymmetric interlateral transfer of motor learning in unipedal dynamic balance - Alexandre J. Marcori; Luis A. Teixeira; Kelyn R. Mathias; Juliana B. Dascal; Victor H. A. Okazaki (Experimental Brain Research, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Rhizosphere microbiome functional diversity and pathogen invasion resistance build up during plant development - Jie Hu; Zhong Wei; George A. Kowalchuk; Yangchun Xu; Qirong Shen; Alexandre Jousset (Environmental Microbiology, 2020)
Summary The rhizosphere microbiome is essential for plant growth and health, and numerous studies have attempted to link microbiome functionality to species and trait composition. However, to date little is known about the actual ecological processes shaping community composition, complicating attempts to steer microbiome functionality. Here, we assess the development of microbial life history and community‐level species interaction patterns that emerge during plant development. We use microbial phenotyping to experimentally test the development of niche complementarity and life history traits linked to microbiome performance. We show that the rhizosphere microbiome assembles from pioneer assemblages of species with random resource overlap into high‐density, functionally complementary climax communities at later stages. During plant growth, fast‐growing species were further replaced by antagonistic and stress‐tolerant ones. Using synthetic consortia isolated from different plant growth stages, we demonstrate that the high functional diversity of ‘climax’ microbiomes leads to a better resistance to bacterial pathogen invasion. By demonstrating that different life‐history strategies prevail at different plant growth stages and that community‐level processes may supersede the importance of single species, we provide a new toolbox to understand microbiome assembly and steer its functionality at a community level.

Ayahuasca blocks the reinstatement of methylphenidate-induced conditioned place preference in mice: behavioral and brain Fos expression evaluations - Henrique S. Reis; Isa R. S. Rodrigues; Alexia Anjos-Santos; Matheus Libarino-Santos; Yasmim A. Serra; Elisângela G. Cata-Preta; Daniella Oliveira-Campos; Natali D. Kisaki; Thaísa Barros-Santos; Thais S. Yokoyama; Fabio C. Cruz; Alexandre J. Oliveira-Lima; et al. (Psychopharmacology, 2020)

Mapping the effectiveness of nature‐based solutions for climate change adaptation - Alexandre Chausson; Beth Turner; Dan Seddon; Nicole Chabaneix; Cécile A. J. Girardin; Valerie Kapos; Isabel Key; Dilys Roe; Alison Smith; Stephen Woroniecki; Nathalie Seddon (Global Change Biology, 2020)
Nature‐based solutions (NbS) to climate change currently have considerable political traction. However, national intentions to deploy NbS have yet to be fully translated into evidence‐based targets and action on the ground. To enable NbS policy and practice to be better informed by science, we produced the first global systematic map of evidence on the effectiveness of nature‐based interventions for addressing the impacts of climate change and hydrometeorological hazards on people. Most of the interventions in natural or semi‐natural ecosystems were reported to have ameliorated adverse climate impacts. Conversely, interventions involving created ecosystems (e.g., afforestation) were associated with trade‐offs; such studies primarily reported reduced soil erosion or increased vegetation cover but lower water availability, although this evidence was geographically restricted. Overall, studies reported more synergies than trade‐offs between reduced climate impacts and broader ecological, social, and climate change mitigation outcomes. In addition, nature‐based interventions were most often shown to be as effective or more so than alternative interventions for addressing climate impacts. However, there were substantial gaps in the evidence base. Notably, there were few studies of the cost‐effectiveness of interventions compared to alternatives and few integrated assessments considering broader social and ecological outcomes. There was also a bias in evidence toward the Global North, despite communities in the Global South being generally more vulnerable to climate impacts. To build resilience to climate change worldwide, it is imperative that we protect and harness the benefits that nature can provide, which can only be done effectively if informed by a strengthened evidence base.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Sea-ice and water dynamics and moonlight impact the acoustic backscatter diurnal signal over the eastern Beaufort Sea continental slope - Igor A. Dmitrenko; Vladislav Petrusevich; Gérald Darnis; Sergei A. Kirillov; Alexander S. Komarov; Jens K. Ehn; Alexandre Forest; Louis Fortier; Søren Rysgaard; David G. Barber (Ocean Science, 2020)
A 2-year-long time series of currents and acoustic backscatter from an acoustic Doppler current profiler, moored over the eastern Beaufort Sea continental slope from October 2003 to September 2005, were used to assess the dynamics and variability of the sound-scattering layer. It has been shown that acoustic backscatter is dominated by a synchronized diel vertical migration (DVM) of zooplankton. Our results show that DVM timings (i) were synchronous with sunlight and (ii) were modified by moonlight and sea ice, which attenuates light transmission to the water column. Moreover, DVM is modified or completely disrupted during highly energetic current events. Thicker ice observed during winter–spring 2005 lowered the backscatter values but favored extending DVM toward the midnight sun. In contrast to many previous studies, DVM occurred through the intermediate water layer during the ice-free season of the midnight sun in 2004. In 2005, the midnight-sun DVM was likely impacted by a high acoustic scattering generated by suspended particles. During full moon at low cloud cover, the nighttime moonlight illuminance led to zooplankton avoidance of the subsurface layer, disrupting DVM. Moreover, DVM was disrupted by upwelling, downwelling, and eddy passing. We suggest that these deviations are consistent with DVM adjusting to avoid enhanced water dynamics. For upwelling and downwelling, zooplankton likely respond to the along-slope water dynamics dominated by surface- and depth-intensified flow, respectively. This drives zooplankton to adjust DVM by aggregating in the low or upper intermediate water layer for upwelling and downwelling, respectively. The baroclinic eddy reversed DVM below the eddy core.

Phylogenomic analyses reveal a rare new genus of wasp (Hymenoptera, Ichneumonidae, Cryptinae) from the Brazilian Atlantic Forest - Fernanda A. Supeleto; Bernardo F. Santos; Seán G. Brady; Alexandre P. Aguiar (Systematics and Biodiversity, 2020)

Single-Component and Multi-Component Metal Abatement in Water Using a Hydrogel Based on Chitosan: Characterization, Isotherm, Kinetic, and Thermodynamic Results - Pâmela B. Vilela; Amanda Dalalibera; Valter A. Becegato; Alexandre T. Paulino (Water, Air, & Soil Pollution, 2020)

Bacillus thuringiensis endotoxin production: a systematic review of the past 10 years - José Manoel W. Duarte Neto; Maria Carolina de A. Wanderley; Túlio Alexandre F. da Silva; Daniela A. Viana Marques; Gilvanda R. da Silva; Josimar Fernandes Gurgel; José de Paula Oliveira; Ana Lúcia F. Porto (World Journal of Microbiology and Biotechnology, 2020)

Assessing drought in the drylands of northeast Brazil under regional warming exceeding 4 °C - Jose A. Marengo; Ana Paula M. A. Cunha; Carlos A. Nobre; Germano G. Ribeiro Neto; Antonio R. Magalhaes; Roger R. Torres; Gilvan Sampaio; Felipe Alexandre; Lincoln M. Alves; Luz A. Cuartas; Karinne R. L. Deusdará; Regina C. S. Álvala (Natural Hazards, 2020)

Characterization and Partitioning Behavior of Creosote in Different Matrices: Soil, Water, and Air - Rayanne Macêdo Aranha; Vivian M. A. Magalhães; Gabriela P. Mendes; Lélia C. R. Soares; Alexandre Muselli Barbosa; Claudio A. O. Nascimento; Marilda M. G. R. Vianna; Osvaldo Chiavone-Filho (Water, Air, & Soil Pollution, 2020)

A computational approach for the inverse problem of neuronal conductances determination - Jemy A. Mandujano Valle; Alexandre L. Madureira; Antonio Leitão (Journal of Computational Neuroscience, 2020)

Phylogeography of feral Monteiro pig in the Brazilian Pantanal Ecosystem - Elizabete C. Silva; Concepta McManus; Ubiratan Piovezan; Danielle A. Faria; Carla A. Souza; Alexandre R. Caetano; Samuel R. Paiva (Genetica, 2020)

An update of the Worldwide Integrated Assessment (WIA) on systemic pesticides. Part 4: Alternatives in major cropping systems - Andrea Veres; Kris A. G. Wyckhuys; Jozsef Kiss; Ferenc Tóth; Giovanni Burgio; Xavier Pons; Carlos Avilla; Stefan Vidal; Jaka Razinger; Renata Bazok; Ewa Matyjaszczyk; Ivan Milosavljević; et al. (Environmental Science and Pollution Research, 2020)
We present a synthetic review and expert consultation that assesses the actual risks posed by arthropod pests in four major crops, identifies targets for integrated pest management (IPM) in terms of cultivated land needing pest control and gauges the implementation “readiness” of non-chemical alternatives. Our assessment focuses on the world’s primary target pests for neonicotinoid-based management: western corn rootworm (WCR, Diabrotica virgifera virgifera ) in maize; wireworms ( Agriotes spp.) in maize and winter wheat; bird cherry-oat aphid ( Rhopalosiphum padi ) in winter wheat; brown planthopper (BPH, Nilaparvata lugens ) in rice; cotton aphid ( Aphis gossypii ) and silver-leaf whitefly (SLW, Bemisia tabaci ) in cotton. First, we queried scientific literature databases and consulted experts from different countries in Europe, North America, and Asia about available IPM tools for each crop-pest system. Next, using an online survey, we quantitatively assessed the economic relevance of target pests by compiling country-level records of crop damage, yield impacts, extent of insecticide usage, and “readiness” status of various pest management alternatives (i.e., research, plot-scale validation, grower-uptake). Biological control received considerable scientific attention, while agronomic strategies (e.g., crop rotation), insurance schemes, decision support systems (DSS), and innovative pesticide application modes were listed as key alternatives. Our study identifies opportunities to advance applied research, IPM technology validation, and grower education to halt or drastically reduce our over-reliance on systemic insecticides globally.

Impact of Drug-Polymer Interaction in Amorphous Solid Dispersion Aiming for the Supersaturation of Poorly Soluble Drug in Biorelevant Medium - Cassiana Mendes; Rafael G. Andrzejewski; Juliana M. O. Pinto; Leice M. R. de Novais; Andersson Barison; Marcos A. S. Silva; Alexandre L. Parize (AAPS PharmSciTech, 2020)

Freshwater Inflow Variability Affects the Relative Importance of Allochthonous Sources for Estuarine Fishes - Bianca Possamai; David J. Hoeinghaus; Clarisse Odebrecht; Paulo C. Abreu; Leonardo E. Moraes; Alexandre C. A. Santos; Alexandre M. Garcia (Estuaries and Coasts, 2020)

Data-space inversion with ensemble smoother - Mateus M. Lima; Alexandre A. Emerick; Carlos E. P. Ortiz (Computational Geosciences, 2020)

Transitions between biomes are common and directional in Bombacoideae (Malvaceae) - Alexander Zizka; Jefferson G. Carvalho‐Sobrinho; R. Toby Pennington; Luciano P. Queiroz; Suzana Alcantara; David A. Baum; Christine D. Bacon; Alexandre Antonelli (Journal of Biogeography, 2020)
Aim To quantify evolutionary transitions between tropical evergreen rain forest and seasonally dry biomes, to test whether biome transitions affect lineage diversification and to examine the robustness of these results to methodological choices. Location The tropics. Time period The Cenozoic. Major taxa studied The plant subfamily Bombacoideae (Malvaceae). Methods We inferred ancestral biomes based on a fossil‐dated molecular phylogeny of 103 species (59% of the clade) and recorded the number of transitions among biomes using biogeographical stochastic mapping based on the dispersal‐extinction‐cladogenesis model. We then estimated diversification rates using state‐specific speciation and extinction rate ( SSE ) methods. Furthermore, we tested the sensitivity of the results to model choice, phylogenetic uncertainty, measurement error and biome definition. Results We found numerous transitions from evergreen rain forest to seasonally dry biomes, and fewer in the opposite direction. These results were robust to methodological choices. Biome type did not influence diversification rates, although this result was subject to uncertainty, especially related to model choice and biome definition. Main conclusions Our results contradict the idea of evolutionary biome conservatism in Bombacoideae, and support previous findings that evergreen rain forests serve as a source for the flora of seasonally dry biomes. The impact of biome classification and biome definition on the results suggest caution when using a biome concept for biogeographical reconstruction and diversification rate analysis.

Phylogenetic structure of geographical co‐occurrence among New World Triatominae species, vectors of Chagas disease - Soledad Ceccarelli; Silvia A. Justi; Jorge E. Rabinovich; José Alexandre F. Diniz Filho; Fabricio Villalobos (Journal of Biogeography, 2020)
Aim The tropical niche conservatism (TNC) hypothesis is one of the most prominent evolutionary hypotheses that has been supported as an explanation for the diversity gradients of several animal taxa, mainly vertebrates. However, the validity of TNC for less‐known taxa such as disease vectors is not clear. Here, we test predictions of TNC in driving the geographical co‐occurrence among triatomine species, vector insects of Chagas disease. We aim to infer the relative effects of ecological and evolutionary processes in determining triatomine species richness at broad spatial scales. Location America. Taxon Triatominae (Hemiptera: Reduviidae). Methods We gathered distributional, phylogenetic and climatic information for 63 triatomine species. We apply the phylogenetic field (PF) framework based on the phylogenetic structure of species co‐occurrences, considering their climatic preferences. We defined PFs of species by estimating the phylogenetic structure of species co‐occurrence within a focal species’ range. Likewise, climatic conditions within focal species’ ranges were defined as their preferred climates. We applied a spatial‐phylogenetic statistical framework to evaluate geographical variation of species’ co‐occurrence and tested the significance of PFs based on biogeographically informed null models. Results Phylogenetic fields of 17 out of 59 triatomine species showed a trend from overdispersed to clustered, coincident with tropical to subtropical–temperate climate. Triatomines co‐occur with more closely related species in temperate areas and more distantly related species in tropical areas. Temperature seasonality was inversely related to the phylogenetic structure of co‐occurrence within species ranges. Main conclusions Geographical co‐occurrence among triatomine species revealed a tropical to subtropical–temperate gradient from overdispersed to clustered PFs and a correspondence between the type of climate in which these species are found and their PFs. Phylogenetic structure within triatomine ranges is explained by their evolutionary history. Our study provides a methodological framework to evaluate the New World triatomine geographical co‐occurrence patterns under a phylogenetic perspective and our results make an important contribution to the understanding of the broad‐scale biodiversity patterns in Triatominae.

The Tropical Seagrass Halophila stipulacea: Reviewing What We Know From Its Native and Invasive Habitats, Alongside Identifying Knowledge Gaps - Gidon Winters; Sven Beer; Demian A. Willette; Inés G. Viana; Kelcie L. Chiquillo; Pedro Beca-Carretero; Betty Villamayor; Tomás Azcárate-García; Rachamim Shem-Tov; Bridget Mwabvu; Luciana Migliore; Alice Rotini; et al. (Frontiers in Marine Science, 2020)

A multiplex RT-PCR method to detect papaya meleira virus complex in adult pre-flowering plants - Marlonni Maurastoni; Tathiana F. Sá-Antunes; Scarlett A. Oliveira; Alexandre M. C. Santos; José A. Ventura; Patricia M. B. Fernandes (Archives of Virology, 2020)

High value-added compounds from fruit and vegetable by-products – Characterization, bioactivities, and application in the development of novel food products - João P. Trigo; Elisabete M. C. Alexandre; Jorge A. Saraiva; Manuela E. Pintado (Critical Reviews in Food Science and Nutrition, 2020)

Conservation assessment of cassava wild relatives in central Brazil - Marcelo F. Simon; Talita S. Reis; J. Moises Mendoza F.; Thalyssa K. M. Arquelão; João B. A. Bringel; Sérgio E. Noronha; Márcio L. L. Martins; Carlos A. S. Ledo; Marcos J. Silva; Alexandre B. Sampaio; Eraldo T. Matricardi; Aldicir Scariot (Biodiversity and Conservation, 2020)

Protein Arginine Methyltransferases in Cardiovascular and Neuronal Function - Alexandre Couto e Silva; Celeste Yin-Chieh Wu; Cristiane T. Citadin; Garrett A. Clemons; HarLee E. Possoit; Mychal S. Grames; Chih-Feng Lien; Alireza Minagar; Reggie Hui-Chao Lee; Adam Frankel; Hung Wen Lin (Molecular Neurobiology, 2020)

Microbial genomes retrieved from High Arctic lake sediments encode for adaptation to cold and oligotrophic environments - Matti O. Ruuskanen; Graham Colby; Kyra A. St.Pierre; Vincent L. St.Louis; Stéphane Aris‐Brosou; Alexandre J. Poulain (Limnology and Oceanography, 2020)
The Arctic is currently warming at an unprecedented rate, which may affect environmental constraints on the freshwater microbial communities found there. Yet, our knowledge of the community structure and functional potential of High Arctic freshwater microbes remains poor, even though they play key roles in nutrient cycling and other ecosystem services. Here, using high‐throughput metagenomic sequencing and genome assembly, we show that sediment microbial communities in the High Arctic's largest lake by volume, Lake Hazen, are phylogenetically diverse, ranging from Proteobacteria, Verrucomicrobia, Planctomycetes, to members of the newly discovered Candidate Phyla Radiation groups. These genomes displayed a high prevalence of pathways involved in lipid chemistry, and a low prevalence of nutrient uptake pathways, which might represent adaptations to the specific, cold (∼ 3.5°C) and extremely oligotrophic conditions in Lake Hazen. Despite these potential adaptations, it is unclear how ongoing environmental changes will affect microbial communities, the makeup of their genomic idiosyncrasies, as well as the possible implications at higher trophic levels.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Stepping stones or stone dead? Fecundity, pollen dispersal and mating patterns of roadside Qualea grandiflora Mart. trees - Carolina M. Potascheff; Sylvie Oddou-Muratorio; Etienne K. Klein; Antonio Figueira; Eduardo A. Bressan; Paulo E. Oliveira; Tonya A. Lander; Alexandre M. Sebbenn (Conservation Genetics, 2019)

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

Revisiting the crop coefficient–reference evapotranspiration procedure for improving irrigation management - Fábio R. Marin; Luiz R. Angelocci; Daniel S. P. Nassif; Murilo S. Vianna; Felipe G. Pilau; Evandro H. F. M. da Silva; Luiz R. Sobenko; Alexandre O. Gonçalves; Rodolfo A. A. Pereira; Kassio S. Carvalho (Theoretical and Applied Climatology, 2019)

High rates of pollen and seed flow in Hymenaea stigonocarpa on a highly fragmented savanna landscape in Brazil - Andrea S. Garcia; Eduardo A. Bressan; Maria Victoria R. Ballester; Antonio Figueira; Alexandre M. Sebbenn (New Forests, 2019)

Synthesis, structural characterization, and cytotoxic evaluation of chalcone derivatives - Paulo N. Bandeira; Telma L. G. Lemos; Hélcio S. Santos; Mylena C. S. de Carvalho; Daniel P. Pinheiro; Manoel O. de Moraes Filho; Cláudia Pessoa; Francisco W. A. Barros-Nepomuceno; Tigressa H. S. Rodrigues; Paulo R. V. Ribeiro; Herbert S. Magalhães; Alexandre M. R. Teixeira (Medicinal Chemistry Research, 2019)

A Fatal Case of Disseminated Mucormycosis Mimicking a Malignancy - Alexandre Malek; Cesar A. Arias; Luis Ostrosky; Stephanie Pankow; Audrey Wanger; Ben Barnett (Mycopathologia, 2019)

Shovelomics root traits assessed on the EURoot maize panel are highly heritable across environments but show low genotype-by-nitrogen interaction - Chantal A. Le Marié; Larry M. York; Alexandre Strigens; Marcos Malosetti; Karl-Heinz Camp; Silvia Giuliani; Jonathan P. Lynch; Andreas Hund (Euphytica, 2019)
The need for sustainable intensification of agriculture in the coming decades requires a reduction in nitrogen (N) fertilization. One opportunity to reduce N application rates without major losses in yield is breeding for nutrient efficient crops. A key parameter that influences nutrient uptake efficiency is the root system architecture (RSA). To explore the impact of N availability on RSA and to investigate the impact of the growth environment, a diverse set of 36 inbred dent maize lines crossed to the inbred flint line UH007 as a tester was evaluated for N-response over 2 years on three different sites. RSA was investigated by excavating and imaging of the root crowns followed by image analysis with REST software. Despite strong site and year effects, trait heritability was generally high. Root traits showing the greatest heritability (> 0.7) were the width of the root stock, indicative of the horizontal expansion, and the fill factor, a measure of the density of the root system. Heritabilities were in a similar range under high or low N application. Under N deficiency the root stock size decreased, the horizontal expansion decreased and the root stock became less dense. However, there was little differential response of the genotypes to low N availability. Thus, the assessed root traits were more constitutively expressed rather than showing genotype-specific plasticity to low N. In contrast, strong differences were observed for ‘stay green’ and silage yield, indicating that these highly heritable traits are good indicators for responsiveness to low N.

Stable isotopes reveal the common winter moult of central rectrices in a long-distance migrant songbird - Frédéric Jiguet; Kevin J. Kardynal; Markus Piha; Tuomas Seimola; José Luis Copete; Michel Alexandre Czajkowski; Valery Dombrovski; Ron Efrat; Simonas Minkevicius; Marko Raković; Michał Skierczyǹski; Keith A. Hobson (Journal of Ornithology, 2019)

Responses of coppiced Eucalyptus to macro- and micronutrient application - José Henrique T. Rocha; Andréa V. A. Wenzel; Eduardo A. S. C. Melo; Ângela Simone Freitag Lima; Rodrigo Eiji Hakamada; Alexandre de Vicente Ferraz; José Carlos Arthur Junior; José Leonardo de Moraes Gonçalves; Gabriela Moreira; Antônio Natal Gonçalves (New Forests, 2019)

Tomato mottle mosaic virus in Brazil and its relationship with Tm-22 gene - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Lázaro E. P. Peres; Déborah Y. A. C. dos Santos (European Journal of Plant Pathology, 2019)

Potential of industrial by-products and wastes from the Iberian Peninsula as carbon sources for sulphate-reducing bacteria - J. D. Carlier; L. M. Alexandre; A. T. Luís; M. C. Costa (International Journal of Environmental Science and Technology, 2019)

Emergence of G12P[6] rotavirus strains among hospitalised children with acute gastroenteritis in Belém, Northern Brazil, following introduction of a rotavirus vaccine - Sylvia F. S. Guerra; Priscylla C. M. S. Fecury; Delana A. M. Bezerra; Patricia S. Lobo; Edvaldo T. Penha Júnior; Edivaldo C. Sousa Júnior; Joana D’Arc P. Mascarenhas; Luana S. Soares; Maria Cleonice A. Justino; Alexandre C. Linhares (Archives of Virology, 2019)

Numerical Modeling of the June 17, 2017 Landslide and Tsunami Events in Karrat Fjord, West Greenland - Alexandre Paris; Emile A. Okal; Cyrielle Guérin; Philippe Heinrich; François Schindelé; Hélène Hébert (Pure and Applied Geophysics, 2019)

Replication and Meta-analysis of the Association between BDNF Val66Met Polymorphism and Cognitive Impairment in Patients Receiving Chemotherapy - Chia Jie Tan; Sheree Wan Ting Lim; Yi Long Toh; Terence Ng; Angie Yeo; Maung Shwe; Koon Mian Foo; Pat Chu; Amit Jain; Si-Lin Koo; Rebecca A. Dent; Raymond Chee Hui Ng; et al. (Molecular Neurobiology, 2019)

Zika Virus Infection of Human Mesenchymal Stem Cells Promotes Differential Expression of Proteins Linked to Several Neurological Diseases - Walter O. Beys-da-Silva; Rafael L. Rosa; Lucélia Santi; Markus Berger; Sung Kyu Park; Alexandre R. Campos; Paula Terraciano; Ana Paula M. Varela; Thais F. Teixeira; Paulo M. Roehe; André Quincozes-Santos; John R. Yates; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Climate change will decrease the range of a keystone fish species in La Plata River Basin, South America - Renata Ruaro; Eliezer O. Conceição; Jislaine C. Silva; Emanuel G. Cafofo; Mirtha A. Angulo-Valencia; Tatiane Mantovano; Alfonso Pineda; Aline C. M. de Paula; Bárbara F. Zanco; Eloiza M. Capparros; Geovani A. Moresco; Isadora J. de Oliveira; et al. (Hydrobiologia, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Magmatic platinum nanoparticles in metasomatic silicate glasses and sulfides from Patagonian mantle xenoliths - José María González-Jiménez; Josep Roqué-Rosell; Abigail Jiménez-Franco; Santiago Tassara; Fernando Nieto; Fernando Gervilla; Sandra Baurier; Joaquín A. Proenza; Edward Saunders; Artur P. Deditius; Manuel Schilling; Alexandre Corgne (Contributions to Mineralogy and Petrology, 2019)

Resource partitioning between two young‐of‐year cownose rays Rhinoptera bonasus and R. brasiliensis within a communal nursery inferred by trophic biomarkers - Bianca de Sousa Rangel; Nigel E. Hussey; Aline D. Gomes; Alexandre Rodrigues; Luiz A. Martinelli; Renata Guimarães Moreira (Journal of Fish Biology, 2019)
Although interspecific trophic interactions plays a principal role within elasmobranch communal nurseries, little is known over variation in foraging strategies adopted by young‐of‐year of sympatric species. To test the hypothesis of dietary resource partitioning between batoids within a communal nursery, we investigated two cownose ray species, Rhinoptera bonasus and R. brasiliensis , which occur in heterospecific groups, a strategy predicted to increase survival and foraging success. Using two biochemical tracers, fatty acids (FA) and stable isotopes (δ 15 N and δ 13 C), the combined effects of maternal investment and the formation of heterospecific groups implying competition for, or partitioning of available food resources were investigated. Through univariate and multivariate analyses of biochemical tracers in several tissues (fin clip, muscle, liver, red blood cells; RBC) and plasma, our results revealed significant interspecific differences in tracers between the two species. Total FAs (∑saturated FA, ∑monounsaturated FA and ∑polyunsaturated FA) and trophic biomarkers ( i.e ., docosahexaenoic acid, arachidonic acid, oleic acid and δ 15 N) were the principle tracers responsible for the differences detected. These data revealed that R. brasiliensis was less enriched in physiologically important essential FAs than R. bonasus . Our findings suggest that these congeneric species differ in maternal investment strategy and moderately partition food resources over relatively fine spatial scales within a single nursery habitat to limit competition. These results provide further knowledge on the foraging strategies adopted by batoids in communal nursery areas, information that is required for improving spatial conservation and management planning.

Stratified sampling in fruit orchards using cluster-based ancillary information maps: a comparative analysis to improve yield and quality estimates - Asier Uribeetxebarria; José A. Martínez-Casasnovas; Alexandre Escolà; Joan R. Rosell-Polo; Jaume Arnó (Precision Agriculture, 2019)

Multivariate statistical analysis correlating 238U, 232Th, and 40K equivalent activities in soil to geochemical data from an agricultural area - Valter A. Becegato; Vitor R. Becegato; Camila A. Baum; Laís Lavnitcki; Alexandre T. Paulino (Journal of Soils and Sediments, 2019)

Genetic variation in thyroid folliculogenesis influences susceptibility to hypothyroidism-induced hearing impairment - Amanda H. Mortensen; Qing Fang; Michelle T. Fleming; Thomas J. Jones; Alexandre Z. Daly; Kenneth R. Johnson; Sally A. Camper (Mammalian Genome, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Phenotypic similarity leads to taxonomic inconsistency: A revision of the lowland's antpittas - Lincoln Carneiro; Gustavo A. Bravo; Alexandre Aleixo (Zoologica Scripta, 2019)
A comprehensive molecular phylogeny of lowland antpittas in the genera Hylopezus and Myrmothera indicated that Hylopezus , as currently defined, is paraphyletic with respect to Myrmothera and Grallaricula . Specifically, both species now placed in Myrmothera, Hylopezus dives , Hylopezus fulviventris and Hylopezus berlepschi form a strongly supported clade that is sister to a clade comprised by Hylopezus perspicillatus , Hylopezus auricularis , Hylopezus ochroleucus , Hylopezus whittakeri , Hylopezus paraensis , Hylopezus macularius, and Hylopezus dilutus . Furthermore, Hylopezus nattereri is sister to a clade glade grouping Myrmothera , Hylopezus , and Grallaricula , representing the most divergent lineage in this complex. Our approach to assess diagnosability and define generic boundaries among these taxa integrates phylogenetic relationships with morphological and acoustic traits. Given that phenotypic and ecological differences do not warrant merging H. nattereri into any other genus, and because there is no generic name available for H. nattereri , we describe herein a new genus for this Atlantic Forest endemic lineage, Cryptopezus gen. n. We also redefine generic limits in Myrmothera and Hylopezus to have a taxonomic classification concordant with their phylogenetic relationships.

ATLANTIC ‐ PRIMATES : a dataset of communities and occurrences of primates in the Atlantic Forests of South America - Laurence Culot; Lucas Augusto Pereira; Ilaria Agostini; Marco Antônio Barreto de Almeida; Rafael Souza Cruz Alves; Izar Aximoff; Alex Bager; María Celia Baldovino; Thiago Ribas Bella; Júlio César Bicca‐Marques; Caryne Braga; Carlos Rodrigo Brocardo; et al. (Ecology, 2019)
Primates play an important role in ecosystem functioning and offer critical insights into human evolution, biology, behavior, and emerging infectious diseases. There are 26 primate species in the Atlantic Forests of South America, 19 of them endemic. We compiled a dataset of 5,472 georeferenced locations of 26 native and 1 introduced primate species, as hybrids in the genera Callithrix and Alouatta . The dataset includes 700 primate communities, 8,121 single species occurrences and 714 estimates of primate population sizes, covering most natural forest types of the tropical and subtropical Atlantic Forest of Brazil, Paraguay and Argentina and some other biomes. On average, primate communities of the Atlantic Forest harbor 2 ± 1 species (range = 1–6). However, about 40% of primate communities contain only one species. Alouatta guariba (N = 2,188 records) and Sapajus nigritus (N = 1,127) were the species with the most records. Callicebus barbarabrownae (N = 35), Leontopithecus caissara (N = 38), and Sapajus libidinosus (N = 41) were the species with the least records. Recorded primate densities varied from 0.004 individuals/km 2 ( Alouatta guariba at Fragmento do Bugre, Paraná, Brazil) to 400 individuals/km 2 ( Alouatta caraya in Santiago, Rio Grande do Sul, Brazil). Our dataset reflects disparity between the numerous primate census conducted in the Atlantic Forest, in contrast to the scarcity of estimates of population sizes and densities. With these data, researchers can develop different macroecological and regional level studies, focusing on communities, populations, species co‐occurrence and distribution patterns. Moreover, the data can also be used to assess the consequences of fragmentation, defaunation, and disease outbreaks on different ecological processes, such as trophic cascades, species invasion or extinction, and community dynamics. There are no copyright restrictions. Please cite this Data Paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Impact of incorporating ABCB1 and CYP4F2 polymorphisms in a pharmacogenetics-guided warfarin dosing algorithm for the Brazilian population - Letícia C. Tavares; Nubia E. Duarte; Leiliane R. Marcatto; Renata A. G. Soares; Jose E. Krieger; Alexandre C. Pereira; Paulo Caleb Junior Lima Santos (European Journal of Clinical Pharmacology, 2018)

Sphagnum Species Modulate their Phenolic Profiles and Mycorrhizal Colonization of Surrounding Andromeda polifolia along Peatland Microhabitats - Geneviève Chiapusio; Vincent E. J. Jassey; Floriant Bellvert; Gilles Comte; Leslie A. Weston; Frederic Delarue; Alexandre Buttler; Marie Laure Toussaint; Philippe Binet (Journal of Chemical Ecology, 2018)

Photoecology of the Antarctic cyanobacterium Leptolyngbya sp. BC1307 brought to light through community analysis, comparative genomics and in vitro photophysiology - Nathan A. M. Chrismas; Christopher J. Williamson; Marian L. Yallop; Alexandre M. Anesio; Patricia Sánchez‐Baracaldo (Molecular Ecology, 2018)
Cyanobacteria are important photoautotrophs in extreme environments such as the McMurdo Dry Valleys, Antarctica. Terrestrial Antarctic cyanobacteria experience constant darkness during the winter and constant light during the summer which influences the ability of these organisms to fix carbon over the course of an annual cycle. Here, we present a unique approach combining community structure, genomic and photophysiological analyses to understand adaptation to Antarctic light regimes in the cyanobacterium Leptolyngbya sp. BC1307. We show that Leptolyngbya sp. BC1307 belongs to a clade of cyanobacteria that inhabits near‐surface environments in the McMurdo Dry Valleys. Genomic analyses reveal that, unlike close relatives, Leptolyngbya sp. BC1307 lacks the genes necessary for production of the pigment phycoerythrin and is incapable of complimentary chromatic acclimation, while containing several genes responsible for known photoprotective pigments. Photophysiology experiments confirmed Leptolyngbya sp. BC1307 to be tolerant of short‐term exposure to high levels of photosynthetically active radiation, while sustained exposure reduced its capacity for photoprotection. As such, Leptolyngbya sp. BC1307 likely exploits low‐light microenvironments within cyanobacterial mats in the McMurdo Dry Valleys.

Dissemination of blaOXA-370 is mediated by IncX plasmids and the Tn6435 transposon - Cibele M. Magagnin; Juliana C. Campos; Darlan A. da Rocha; Suely C. F. Sampaio; Franciéli P. Rozáles; Afonso L. Barth; Alexandre P. Zavascki; Jorge L. M. Sampaio (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Campylobacter jejuni virulence genes and immune-inflammatory biomarkers association with growth impairment in children from Northeastern Brazil - Herlice do Nascimento Veras; Pedro H. Q. S. Medeiros; Samilly A. Ribeiro; Thiago M. Freitas; Ana K. S. Santos; Marília S. M. G. Amaral; Mariana D. Bona; Alexandre Havt; Ila F. N. Lima; Noélia L. Lima; Alessandra Di Moura; Álvaro M. Leite; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Deterministic ensemble smoother with multiple data assimilation as an alternative for history-matching seismic data - Alexandre A. Emerick (Computational Geosciences, 2018)

Recent chapters of Neotropical history overlooked in phylogeography: Shallow divergence explains phenotype and genotype uncoupling in Antilophia manakins - Fabio Raposo do Amaral; Marcos Maldonado‐Coelho; Alexandre Aleixo; Leilton W. Luna; Péricles Sena do Rêgo; Juliana Araripe; Thainara O. Souza; Weber A. G. Silva; Gregory Thom (Molecular Ecology, 2018)
Establishing links between phenotypic and genotypic variation is a central goal of evolutionary biology, as they might provide important insights into evolutionary processes shaping genetic and species diversity in nature. One of the more intriguing possibilities is when no genetic divergence is found to be associated with conspicuous phenotypic divergence. In that case, speciation theory predicts that phenotypic divergence may still occur in the presence of significant gene flow—thereby resulting in little genomic divergence—when genetic loci underpinning phenotypes are under strong divergent selection. However, a finding of phenotypic distinctiveness with weak or no population genetic structure may simply result from low statistical power to detect shallow genetic divergences when small data sets are used. Here, we used a subgenomic data set of 2,386 ultraconserved elements to explore genomewide divergence between two species of Antilophia manakins, which are phenotypically distinct yet evidently lack strong genetic differentiation according to previous studies based on a limited number of loci. Our results revealed clear population structure that matches the two phenotypes, supporting the idea that smaller data sets lacked the power to detect this recent divergence event (likely Cerrado populations. Besides their use in biogeography, subgenomic data sets may help redefine local conservation programmes by revealing cryptic population structure that may be key to population management.

Short-term treatment with metformin reduces hepatic lipid accumulation but induces liver inflammation in obese mice - Alexandre Abilio de Souza Teixeira; Camila O. Souza; Luana A. Biondo; Loreana Sanches Silveira; Edson A. Lima; Helena A. Batatinha; Adriane Pereira Araujo; Michele Joana Alves; Sandro Massao Hirabara; Rui Curi; José Cesar Rosa Neto (Inflammopharmacology, 2018)

Trace metals dynamics under contrasted land uses: contribution of statistical, isotopic, and EXAFS approaches - Caroline A. Bonnot; Alexandre Gélabert; Pascale Louvat; Guillaume Morin; Olivier Proux; Marc F. Benedetti (Environmental Science and Pollution Research, 2018)

5-Nitroimidazole-derived Schiff bases and their copper(II) complexes exhibit potent antimicrobial activity against pathogenic anaerobic bacteria - Alexandre A. Oliveira; Ana P. A. Oliveira; Lucas L. Franco; Micael O. Ferencs; João F. G. Ferreira; Sofia M. P. S. Bachi; Nivaldo L. Speziali; Luiz M. Farias; Paula P. Magalhães; Heloisa Beraldo (BioMetals, 2018)

Marine Biotechnology in Brazil: Recent Developments and Its Potential for Innovation - Fabiano Thompson; Ricardo Krüger; Cristiane C. Thompson; Roberto G. S. Berlinck; Ricardo Coutinho; Melissa F. Landell; Mauro Pavão; Paulo A. S. Mourão; Ana Salles; Naiane Negri; Fabyano A. C. Lopes; Vitor Freire; et al. (Frontiers in Marine Science, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Jaguar movement database: a GPS‐based movement dataset of an apex predator in the Neotropics - Ronaldo G. Morato; Jeffrey J. Thompson; Agustin Paviolo; Jesus A. de La Torre; Fernando Lima; Roy T. McBride; Rogerio C. Paula; Laury Cullen; Leandro Silveira; Daniel L. Z. Kantek; Emiliano E. Ramalho; Louise Maranhão; et al. (Ecology, 2018)
The field of movement ecology has rapidly grown during the last decade, with important advancements in tracking devices and analytical tools that have provided unprecedented insights into where, when, and why species move across a landscape. Although there has been an increasing emphasis on making animal movement data publicly available, there has also been a conspicuous dearth in the availability of such data on large carnivores. Globally, large predators are of conservation concern. However, due to their secretive behavior and low densities, obtaining movement data on apex predators is expensive and logistically challenging. Consequently, the relatively small sample sizes typical of large carnivore movement studies may limit insights into the ecology and behavior of these elusive predators. The aim of this initiative is to make available to the conservation‐scientific community a dataset of 134,690 locations of jaguars ( Panthera onca ) collected from 117 individuals (54 males and 63 females) tracked by GPS technology. Individual jaguars were monitored in five different range countries representing a large portion of the species’ distribution. This dataset may be used to answer a variety of ecological questions including but not limited to: improved models of connectivity from local to continental scales; the use of natural or human‐modified landscapes by jaguars; movement behavior of jaguars in regions not represented in this dataset; intraspecific interactions; and predator‐prey interactions. In making our dataset publicly available, we hope to motivate other research groups to do the same in the near future. Specifically, we aim to help inform a better understanding of jaguar movement ecology with applications towards effective decision making and maximizing long‐term conservation efforts for this ecologically important species. There are no costs, copyright, or proprietary restrictions associated with this data set. When using this data set, please cite this article to recognize the effort involved in gathering and collating the data and the willingness of the authors to make it publicly available.

Diagnosing drought using the downstreamness concept: the effect of reservoir networks on drought evolution - Pieter R. van Oel; Eduardo S. P. R. Martins; Alexandre C. Costa; Niko Wanders; Henny A. J. van Lanen (Hydrological Sciences Journal, 2018)

Study of Interaction Between Glyphosate and Goethite Using Several Methodologies: an Environmental Perspective - Thiago Orcelli; Eduardo di Mauro; Alexandre Urbano; Daniel F. Valezi; Antonio C. S. da Costa; Cássia Thaïs B. V. Zaia; Dimas A. M. Zaia (Water, Air, & Soil Pollution, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

A versatile method for the preparation of particle-loaded microbubbles for multimodality imaging and targeted drug delivery - Joshua Owen; Calum Crake; Jeong Yu Lee; Dario Carugo; Estelle Beguin; Alexandre A Khrapitchev; Richard J Browning; Nicola Sibson; Eleanor Stride (Drug Delivery and Translational Research, 2018)

Hepatitis C virus infection among illicit drug users in an archipelago of the Amazon - Fabricio Q. Silva; Francisco J. A. Santos; Andreia P. Andrade; Suzy D. B. Pacheco; Benedikt Fischer; João Renato R. Pinho; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho (Archives of Virology, 2018)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2018)

Tipping point in plant–fungal interactions under severe drought causes abrupt rise in peatland ecosystem respiration - Vincent E. J. Jassey; Monika K. Reczuga; Małgorzata Zielińska; Sandra Słowińska; Bjorn J. M. Robroek; Pierre Mariotte; Christophe V. W. Seppey; Enrique Lara; Jan Barabach; Michał Słowiński; Luca Bragazza; Bogdan H. Chojnicki; et al. (Global Change Biology, 2018)
Ecosystems are increasingly prone to climate extremes, such as drought, with long‐lasting effects on both plant and soil communities and, subsequently, on carbon (C) cycling. However, recent studies underlined the strong variability in ecosystem's response to droughts, raising the issue of nonlinear responses in plant and soil communities. The conundrum is what causes ecosystems to shift in response to drought. Here, we investigated the response of plant and soil fungi to drought of different intensities using a water table gradient in peatlands—a major C sink ecosystem. Using moving window structural equation models, we show that substantial changes in ecosystem respiration, plant and soil fungal communities occurred when the water level fell below a tipping point of −24 cm. As a corollary, ecosystem respiration was the greatest when graminoids and saprotrophic fungi became prevalent as a response to the extreme drought. Graminoids indirectly influenced fungal functional composition and soil enzyme activities through their direct effect on dissolved organic matter quality, while saprotrophic fungi directly influenced soil enzyme activities. In turn, increasing enzyme activities promoted ecosystem respiration. We show that functional transitions in ecosystem respiration critically depend on the degree of response of graminoids and saprotrophic fungi to drought. Our results represent a major advance in understanding the nonlinear nature of ecosystem properties to drought and pave the way towards a truly mechanistic understanding of the effects of drought on ecosystem processes.

Dexamethasone Inhibits Copper-Induced Alpha-Synuclein Aggregation by a Metallothionein-Dependent Mechanism - Fleur A. McLeary; Alexandre N. Rcom-H’cheo-Gauthier; Jessica Kinder; Michael Goulding; Tien K. Khoo; George D. Mellick; Roger S. Chung; Dean L. Pountney (Neurotoxicity Research, 2018)

Variation in the composition and activity of ants on defense of host plant Turnera subulata (Turneraceae): strong response to simulated herbivore attacks and to herbivore’s baits - Nayara G. Cruz; Paulo F. Cristaldo; Leandro Bacci; Camilla S. Almeida; Gabriela P. Camacho; Alisson S. Santana; Efrem J. M. Ribeiro; Alexandre P. Oliveira; Abraão A. Santos; Ana P. A. Araújo (Arthropod-Plant Interactions, 2018)

Landscape‐level effects on aboveground biomass of tropical forests: A conceptual framework - Melina Melito; Jean Paul Metzger; Alexandre A. de Oliveira (Global Change Biology, 2018)
Despite the general recognition that fragmentation can reduce forest biomass through edge effects, a systematic review of the literature does not reveal a clear role of edges in modulating biomass loss. Additionally, the edge effects appear to be constrained by matrix type, suggesting that landscape composition has an influence on biomass stocks. The lack of empirical evidence of pervasive edge‐related biomass losses across tropical forests highlights the necessity for a general framework linking landscape structure with aboveground biomass. Here, we propose a conceptual model in which landscape composition and configuration mediate the magnitude of edge effects and seed‐flux among forest patches, which ultimately has an influence on biomass. Our model hypothesizes that a rapid reduction of biomass can occur below a threshold of forest cover loss. Just below this threshold, we predict that changes in landscape configuration can strongly influence the patch's isolation, thus enhancing biomass loss. Moreover, we expect a synergism between landscape composition and patch attributes, where matrix type mediates the effects of edges on species decline, particularly for shade‐tolerant species. To test our conceptual framework, we propose a sampling protocol where the effects of edges, forest amount, forest isolation, fragment size, and matrix type on biomass stocks can be assessed both collectively and individually. The proposed model unifies the combined effects of landscape and patch structure on biomass into a single framework, providing a new set of main drivers of biomass loss in human‐modified landscapes. We argue that carbon trading agendas (e.g., REDD +) and carbon‐conservation initiatives must go beyond the effects of forest loss and edges on biomass, considering the whole set of effects on biomass related to changes in landscape composition and configuration.

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

ATLANTIC BIRDS : a data set of bird species from the Brazilian Atlantic Forest - Érica Hasui; Jean Paul Metzger; Rafael G. Pimentel; Luís Fábio Silveira; Alex A. d. A. Bovo; Alexandre C. Martensen; Alexandre Uezu; André L. Regolin; Arthur Â. Bispo de Oliveira; Cassiano A. F. R. Gatto; Charles Duca; Christian B. Andretti; et al. (Ecology, 2018)
South America holds 30% of the world's avifauna, with the Atlantic Forest representing one of the richest regions of the Neotropics. Here we have compiled a data set on Brazilian Atlantic Forest bird occurrence (150,423) and abundance samples ( N = 832 bird species; 33,119 bird individuals) using multiple methods, including qualitative surveys, mist nets, point counts, and line transects). We used four main sources of data: museum collections, on‐line databases, literature sources, and unpublished reports. The data set comprises 4,122 localities and data from 1815 to 2017. Most studies were conducted in the Florestas de Interior (1,510 localities) and Serra do Mar (1,280 localities) biogeographic sub‐regions. Considering the three main quantitative methods (mist net, point count, and line transect), we compiled abundance data for 745 species in 576 communities. In the data set, the most frequent species were Basileuterus culicivorus , Cyclaris gujanensis , and Conophaga lineata . There were 71 singletons, such as Lipaugus conditus and Calyptura cristata . We suggest that this small number of records reinforces the critical situation of these taxa in the Atlantic Forest. The information provided in this data set can be used for macroecological studies and to foster conservation strategies in this biodiversity hotspot. No copyright restrictions are associated with the data set. Please cite this Data Paper if data are used in publications and teaching events.

Assessment of wound healing of tagged gray ( Eschrichtius robustus ) and blue ( Balaenoptera musculus ) whales in the eastern North Pacific using long‐term series of photographs - Stephanie A. Norman; Kiirsten R. Flynn; Alexandre N. Zerbini; Frances M. D. Gulland; Michael J. Moore; Stephen Raverty; David S. Rotstein; Bruce R. Mate; Craig Hayslip; Diane Gendron; Richard Sears; Annie B. Douglas; et al. (Marine Mammal Science, 2018)
Tags have been used to examine migration routes and habitat use of large whales for >40 yr, however, evaluation of tag wound healing has largely been short‐term, anecdotal or generalized. This study developed methods for systematic photographic assessment of long‐term external consequences of tag placement, to determine potential differences in wound healing between species and tag types and thus advise future tagging efforts to possibly minimize undesirable side effects. Tag site appearance and healing characteristics were evaluated by two reviewers and a time series evaluated by five veterinarians from photographs during 995 postdeployment encounters with 34 gray and 63 blue whales tagged in the North Pacific. Blue whale resightings were less frequent, but spanned a longer time period due to earlier tag deployments than the more frequent gray whale follow‐up observations. Swelling occurred in 74% of reencountered gray whales, with the highest frequency 6 mo postdeployment. Swellings were common in blue whales with early tag designs but rare with current models. Depressions occurred in 82% of gray and 71% of blue whales. This study demonstrates the value of follow‐up studies of tagged animals and systematic scoring of photographs to quantitatively compare tag response.

Route Fidelity during Marine Megafauna Migration - Travis W. Horton; Nan Hauser; Alexandre N. Zerbini; Malcolm P. Francis; Michael L. Domeier; Artur Andriolo; Daniel P. Costa; Patrick W. Robinson; Clinton A. J. Duffy; Nicole Nasby-Lucas; Richard N. Holdaway; Phillip J. Clapham (Frontiers in Marine Science, 2017)

Biodiversity and climate determine the functioning of Neotropical forests - Lourens Poorter; Masha T. van der Sande; Eric J. M. M. Arets; Nataly Ascarrunz; Brian J. Enquist; Bryan Finegan; Juan Carlos Licona; Miguel Martínez‐Ramos; Lucas Mazzei; Jorge A. Meave; Rodrigo Muñoz; Christopher J. Nytch; et al. (Global Ecology and Biogeography, 2017)
Aim Tropical forests account for a quarter of the global carbon storage and a third of the terrestrial productivity. Few studies have teased apart the relative importance of environmental factors and forest attributes for ecosystem functioning, especially for the tropics. This study aims to relate aboveground biomass (AGB) and biomass dynamics (i.e., net biomass productivity and its underlying demographic drivers: biomass recruitment, growth and mortality) to forest attributes (tree diversity, community‐mean traits and stand basal area) and environmental conditions (water availability, soil fertility and disturbance). Location Neotropics. Methods We used data from 26 sites, 201 1‐ha plots and >92,000 trees distributed across the Neotropics. We quantified for each site water availability and soil total exchangeable bases and for each plot three key community‐weighted mean functional traits that are important for biomass stocks and productivity. We used structural equation models to test the hypothesis that all drivers have independent, positive effects on biomass stocks and dynamics. Results Of the relationships analysed, vegetation attributes were more frequently associated significantly with biomass stocks and dynamics than environmental conditions (in 67 vs. 33% of the relationships). High climatic water availability increased biomass growth and stocks, light disturbance increased biomass growth, and soil bases had no effect. Rarefied tree species richness had consistent positive relationships with biomass stocks and dynamics, probably because of niche complementarity, but was not related to net biomass productivity. Community‐mean traits were good predictors of biomass stocks and dynamics. Main conclusions Water availability has a strong positive effect on biomass stocks and growth, and a future predicted increase in (atmospheric) drought might, therefore, potentially reduce carbon storage. Forest attributes, including species diversity and community‐weighted mean traits, have independent and important relationships with AGB stocks, dynamics and ecosystem functioning, not only in relatively simple temperate systems, but also in structurally complex hyper‐diverse tropical forests.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Hyperpalatable Diet and Physical Exercise Modulate the Expression of the Glial Monocarboxylate Transporters MCT1 and 4 - Luis V. Portela; Andressa W. Brochier; Clarissa B. Haas; Afonso Kopczynski de Carvalho; Jussania A. Gnoato; Eduardo R. Zimmer; Eduardo Kalinine; Luc Pellerin; Alexandre P. Muller (Molecular Neurobiology, 2017)

Erratum to: VOSalophen: a vanadium complex with a stilbene derivative—induction of apoptosis, autophagy, and efficiency in experimental cutaneous leishmaniasis - Patrícia de A. Machado; Jessica O. F. Moraes; Gustavo S. G. Carvalho; Wallace P. Lima; Gilson C. Macedo; Elizandra A. Britta; Celso V. Nakamura; Adilson D. da Silva; Alexandre Cuin; Elaine S. Coimbra (JBIC Journal of Biological Inorganic Chemistry, 2017)

One pathogen two stones: are Australian tree frog antimicrobial peptides synergistic against human pathogens? - Marc-Antoine Sani; Siobhan Carne; Sarah A. Overall; Alexandre Poulhazan; Frances Separovic (European Biophysics Journal, 2017)

First report of persistent dengue-1-associated autoimmune neurological disturbance: neuromyelitis optica spectrum disorder - Marzia Puccioni-Sohler; Alice M. M. Ornelas; Andrea S. de Souza; Mauro Jorge Cabral-Castro; Jessyca T.M.A. Ramos; Carolina Rosadas; Maria Cecilia F. Salgado; Alexandre A. Castiglione; Fernando Ferry; Jose Mauro Peralta; Carolina Moreira Voloch; Amilcar Tanuri; et al. (Journal of NeuroVirology, 2017)

Comparative study of the structure and interaction of the pore helices of the hERG and Kv1.5 potassium channels in model membranes - Maïwenn Beaugrand; Alexandre A. Arnold; Steve Bourgault; Philip T. F. Williamson; Isabelle Marcotte (European Biophysics Journal, 2017)

Effect of reproductive methods and GnRH administration on long-term protocol in Santa Ines ewes - Marcos V Biehl; Marcos V C Ferraz Junior; Evandro M Ferreira; Daniel M Polizel; Alexandre A Miszura; José P R Barroso; Gabriela B Oliveira; Analisa V Bertoloni; Alexandre V Pires (Tropical Animal Health and Production, 2017)

VOSalophen: a vanadium complex with a stilbene derivative—induction of apoptosis, autophagy, and efficiency in experimental cutaneous leishmaniasis - Patrícia de A. Machado; Jessica O. F. Morais; Gustavo S. G. Carvalho; Wallace P. Lima; Gilson C. Macedo; Elizandra A. Britta; Celso V. Nakamura; Adilson D. da Silva; Alexandre Cuin; Elaine S. Coimbra (JBIC Journal of Biological Inorganic Chemistry, 2017)

Genetic diversity and relationship of Guinea yam (Dioscorea cayenensis Lam.–D. rotundata Poir. complex) germplasm in Benin (West Africa) using microsatellite markers - Yêyinou L. Loko; Ranjana Bhattacharjee; A. Paterne Agre; Innocent Dossou-Aminon; Azize Orobiyi; Gustave L. Djedatin; Alexandre Dansi (Genetic Resources and Crop Evolution, 2017)

Alternatives to regular urea for abating N losses in lettuce production under sub-tropical climate - Rafael R. Cantú; Celso Aita; Alexandre Doneda; Diego A. Giacomini; Alexandre Dessbesell; Marlon Arenhardt; Géssica G. De Bastiani; Stefen B. Pujol; Philippe Rochette; Martin H. Chantigny; Sandro J. Giacomini (Biology and Fertility of Soils, 2017)

Responsiveness to siblings’ need increases with age in vocally negotiating barn owl nestlings - Amélie N. Dreiss; Charlène A. Ruppli; Alice Delarbre; Christof Faller; Alexandre Roulin (Behavioral Ecology and Sociobiology, 2017)

Tidal effects on phytoplankton assemblages in a near‐pristine estuary: a trait‐based approach for the case of a shallow tropical ecosystem in Brazil - Gleyci A. O. Moser; Fernanda Reinhardt Piedras; Anna Beatriz J. Oaquim; Daiana S. Souza; Suzana G. Leles; Domênica T. de Lima; Ana Beatriz A. Ramos; Cássia de O. Farias; Alexandre M. Fernandes (Marine Ecology, 2017)
The study of near‐pristine estuaries can be used as a tool for mitigation projects of harmful effects in anthropogenic eutrophic systems, since one can analyze the effect of temporal and spatial variations generated mainly by natural forces. Phytoplankton taxonomy has been used as a classical indicator to assess changes in transitional water communities, however alternative methods based on morphological, behavioral and physiological traits offer the opportunity to compare sites or moments with different taxonomic compositions. Our goal, in this context, is to evaluate phytoplankton community short‐term and seasonal variability in a near‐pristine estuary, Barra Grande estuary (Ilha Grande, RJ , Brazil), through species functional traits and thus community functional diversity. Samplings were carried out in a mooring in complete tidal cycles, seasonally during 2012. Our results showed a diverse phytoplankton community with 38 frequent and abundant taxa, marked by density variation (1.2 × 10.4–2 × 10.7 cell L −1 ) in depth, with abundance inversely related to tidal currents. The functional structure of the phytoplankton community measured by functional diversity ( FD ), varied seasonally in and across a gradient of tidal energy. A core community, mainly represented by flagellates and dinoflagellates, occurred in all observations and was highly functional (high FD ), exploiting a variety of habitats. The chain‐forming diatoms were associated with high tidal energy, and occurred in higher densities during summer. Phytoplankton cell size, cell shape, and the ability to form colonies are extremely plastic traits that can be regulated by the environment, however, isolated tychopelagic diatoms were present in the study area across all seasons, with higher contributions in autumn and winter, reflecting the shallow characteristic of this system. During the winter, an exposed sandbar was formed, and the lack of connection with the ocean resulted in an abundance of riverine and brackish water taxa. In this near‐pristine estuary the densities and occurrences of HAB phytoplankton are low. Trait‐based analyses add information about community structure, which can be impacted by anthropogenic actions in urbanized coastal systems. Thus the information provided by this study regarding phytoplankton functional diversity and its relation to nutrients and hydrography in Barra Grande Estuary can be applied as a baseline model for the development of public policies.

Resource availability modulates biodiversity‐invasion relationships by altering competitive interactions - Tianjie Yang; Zhong Wei; Ville‐Petri Friman; Yangchun Xu; Qirong Shen; George A. Kowalchuk; Alexandre Jousset (Environmental Microbiology, 2017)
Summary Community diversity affects the survival of newly introduced species via resource competition. Competitive interactions can be modulated by resource availability and we hypothesized that this may alter biodiversity‐invasion relationships. To study this, we assessed the growth of a bacterial invader, Ralstonia solanacearum , when introduced into communities comprised of one to five closely related resident species under different resource concentrations. The invader growth was then examined as a function of resident community richness, species composition and resource availability. We found that the relative density of the invader was reduced by increasing resident community richness and resource availability. Mechanistically, this could be explained by changes in the competitive interactions between the resident species and the invader along the resource availability gradient. At low resource availability, resident species with a high catabolic similarity with the invader efficiently reduced the invader relative density, while at high resource availability, fast‐growing resident species became more important for the invader suppression. These results indicate that the relative importance of different resident community species can change dynamically along to resource availability gradient. Diverse communities could be thus more robust to invasions by providing a set of significant species that can take suppressive roles across different environments.

Phylogeny and the prediction of tree functional diversity across novel continental settings - Nathan G. Swenson; Michael D. Weiser; Lingfeng Mao; Miguel B. Araújo; José Alexandre F. Diniz‐Filho; Johannes Kollmann; David Nogués‐Bravo; Signe Normand; Miguel A. Rodríguez; Raúl García‐Valdés; Fernando Valladares; Miguel A. Zavala; et al. (Global Ecology and Biogeography, 2017)
Aim Mapping the distribution and diversity of plant functional traits is critical for projecting future changes to vegetation under global change. Maps of plant functional traits, however, are scarce due very sparse global trait data matrices. A potential solution to this data limitation is to utilize the known levels of phylogenetic signal in trait data to predict missing values. Here we aim to test existing phylogenetic comparative methods for imputing missing trait data for the purpose of producing continental‐scale maps of plant functional traits. Location North America and Europe. Methods Phylogenetic imputation models and trait data from one continent were used to predict the trait values for tree species on the other continent and to produce trait maps. Predicted maps of trait means, variances and functional diversity were compared with known maps to quantify the degree to which predicted trait values could estimate spatial patterns of trait distributions and diversity. Results We show that the phylogenetic signal in plant functional trait data can be used to provide robust predictions of the geographical distribution of tree functional diversity. However, predictions for traits with little phylogenetic signal, such as maximum height, are error prone. Lastly, trait imputation methods based on phylogenetic generalized least squares tended to outperform those based on phylogenetic eigenvectors. Main conclusions It is possible to predict patterns of functional diversity across continental settings with novel species assemblages for most of the traits studied for which we have no direct trait information, thereby offering an effective method for overcoming a key data limitation in global change biology, macroecology and ecosystem modelling.

Copper/Zinc Bioaccumulation and the Effect of Phytotoxicity on the Growth of Lettuce (Lactuca sativa L.) in Non-contaminated, Metal-Contaminated and Swine Manure-Enriched Soils - Mariane Wolf; Dilmar Baretta; Valter A. Becegato; Vitor de C. Almeida; Alexandre T. Paulino (Water, Air, & Soil Pollution, 2017)

Effect of changes in the nutritional status on the performances of growing Creole kids during an established nematode parasite infection - W. Ceï; H. Archimède; R. Arquet; Y. Félicité; D. Feuillet; A. Nepos; P. Mulciba; T. Etienne; G. Alexandre; J. C. Bambou (Tropical Animal Health and Production, 2017)

Architecture of collapse: regime shift and recovery in an hierarchically structured marine ecosystem - Georgi M. Daskalov; Laura Boicenco; Alexandre N. Grishin; Luminita Lazar; Vesselina Mihneva; Vladislav A. Shlyakhov; Mustafa Zengin (Global Change Biology, 2017)
By the late 20th century, a series of events or ‘natural experiments’, for example the depletion of apex predators, extreme eutrophication and blooms of invasive species, had suggested that the Black Sea could be considered as a large ecosystem ‘laboratory’. The events resulted in regime shifts cascading through all trophic levels, disturbing ecosystem functioning and damaging the water environment. Causal pathways by which the external (hydroclimate, overfishing) and internal (food web interactions) drivers provoke regime shifts are investigated. Statistical data analyses supported by an interpretative framework based on hierarchical ecosystem theory revealed mechanisms of hierarchical incorporation of environmental factors into the ecosystem. Evidence links Atlantic teleconnections to Black Sea hydroclimate, which together with fishing shapes variability in fish stocks. The hydroclimatic signal is conveyed through the food web via changes in productivity at all levels, to planktivorous fish. Fluctuating fish abundance is believed to induce a lagged change in competitor jelly plankton that cascades down to phytoplankton and influences water quality. Deprived of the stabilising role of apex predators, the Black Sea's hierarchical ecosystem organisation is susceptible to both environmental and anthropogenic stresses, and increased fishing makes fish stock collapses highly probable. When declining stocks are confronted with burgeoning fishing effort associated with the inability of fishery managers and decision‐makers to adapt rapidly to changes in fish abundance, there is overfishing and stock collapse. Management procedures are ineffective at handling complex phenomena such as ecosystem regime shifts because of the shortage of suitable explanatory models. The proposed concepts and models reported here relate the hydroclimate, overfishing and invasive species to shifts in ecosystem functioning and water quality, unravelling issues such as the causality of ecosystem interactions and mechanisms and offering potential for finding ways to reverse regime shifts. We advocate a management approach aiming at restoring ecosystem hierarchy that might mitigate the costly consequences of regime shifts.

A multicenter assessment of single-cell models aligned to standard measures of cell health for prediction of acute hepatotoxicity - Rowena L. Sison-Young; Volker M. Lauschke; Esther Johann; Eliane Alexandre; Sébastien Antherieu; Hélène Aerts; Helga H. J. Gerets; Gilles Labbe; Delphine Hoët; Martina Dorau; Christopher A. Schofield; Cerys A. Lovatt; et al. (Archives of Toxicology, 2017)

Mobile terrestrial laser scanner applications in precision fruticulture/horticulture and tools to extract information from canopy point clouds - Alexandre Escolà; José A. Martínez-Casasnovas; Josep Rufat; Jaume Arnó; Amadeu Arbonés; Francesc Sebé; Miquel Pascual; Eduard Gregorio; Joan R. Rosell-Polo (Precision Agriculture, 2017)

Cystic fibrosis in Afro-Brazilians: XK haplotypes analysis supports the European origin of p.F508del mutation - D. A. S. de Souza; F. R. Faucz; R. B. de Alexandre; M. A. Santana; E. L. S. de Souza; F. J. C. Reis; L. Pereira-Ferrari; V. S. Sotomaior; L. Culpi; J. A. Phillips; S. Raskin (Genetica, 2017)

Modulatory effect of the exudates released by the brown kelp Lessonia spicata on the toxicity of copper in early developmental stages of ecologically related organisms - Alexandre Fellous; Santiago Andrade; Francisco Vidal-Ramirez; Ricardo Calderón; Jessica Beltran; Juan A. Correa (Environmental Science and Pollution Research, 2017)

Investigation on Principal Component Analysis Parameterizations for History Matching Channelized Facies Models with Ensemble-Based Data Assimilation - Alexandre A. Emerick (Mathematical Geosciences, 2017)

Male spider mites use chemical cues, but not the female mating interval, to choose between mates - Leonor R. Rodrigues; Alexandre R. T. Figueiredo; Susana A. M. Varela; Isabelle Olivieri; Sara Magalhães (Experimental and Applied Acarology, 2017)

Characterization of hepatitis B virus infection in illicit drug users in the Marajó Archipelago, northern Brazil - Andréia P. Andrade; Suzy D. B. Pacheco; Fabricio Q. Silva; Luiz M. L. Pinheiro; Jairo A. A. Castro; Carlos E. M. Amaral; Renata B. Hermes; Benedikt Fischer; João R. R. Pinho; José Alexandre R. Lemos; Aldemir B. Oliveira-Filho (Archives of Virology, 2017)

Differential Impact of Acclimation and Acute Water Deprivation in the Expression of Key Transcription Factors in Soybean Roots - Fábia Guimarães-Dias; Anna C. Neves-Borges; Alessandra J. Conforte; Leonardo Giovanella-Kampmann; André V. J. Ferreira; Regina M. S. Amorim; Magda A. Benevent; Maria Eugênia Lisei de Sá; Rosilene O. Mesquita; Fabiana A. Rodrigues; Alexandre L. Nepomuceno; Eduardo Romano; et al. (Plant Molecular Biology Reporter, 2016)

Asymmetric biocatalysis of the nerve agent VX by human serum paraoxonase 1: molecular docking and reaction mechanism calculations - Jaqueline Sartorelli; Alexandre A. de Castro; Teodorico C. Ramalho; Juliana O. S. Giacoppo; Daiana T. Mancini; Melissa S. Caetano; Elaine F. F. da Cunha (Medicinal Chemistry Research, 2016)

Assessment of loose and adhered urban street sediments and trace metals: a study in the city of Poços de Caldas, Brazil - Alexandre Silveira; José A. Pereira; Cristiano Poleto; João L. M. P. de Lima; Flávio A. Gonçalves; Livia A. Alvarenga; Jorge M. P. G. Isidoro (Journal of Soils and Sediments, 2016)

Distribution and sources of sterol biomarkers in sediments collected from a tropical estuary in Northeast Brazil - Morgana Frena; Ana Paula Stein Santos; Ewerton Santos; Rosianne P. Silva; Michel R. R. Souza; Luiz A. S. Madureira; Marcelo R. Alexandre (Environmental Science and Pollution Research, 2016)

The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study - Rogier B. Mars; Sean Foxley; Lennart Verhagen; Saad Jbabdi; Jérôme Sallet; MaryAnn P. Noonan; Franz-Xaver Neubert; Jesper L. Andersson; Paula L. Croxson; Robin I. M. Dunbar; Alexandre A. Khrapitchev; Nicola R. Sibson; et al. (Brain Structure and Function, 2016)

Guiana Dolphins (Sotalia guianensis) and DR-CALUX for Screening Coastal Brazilian Environments for Dioxins and Related Compounds - Paulo R. Dorneles; José Lailson-Brito; Tatiana L. Bisi; Camila Domit; Lupércio A. Barbosa; Ana C. O. Meirelles; Vitor L. Carvalho; Olaf Malm; Alexandre F. Azevedo; François Brose; Krishna Das; Marie-Louise Scippo (Archives of Environmental Contamination and Toxicology, 2016)

Adhesio interthalamica and cavum septum pellucidum in mesial temporal lobe epilepsy - Clarissa Trzesniak; Ila M. Linares; Érica R. Coimbra; Alexandre Veriano Júnior; Tonicarlo R. Velasco; Antonio C. Santos; Jaime E. Hallak; Americo C. Sakamoto; Geraldo F. Busatto; José A. Crippa (Brain Imaging and Behavior, 2016)

Response to Heethoff, Norton, and Raspotnig: Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog and Erratum - Jenna R. McGugan; Gary D. Byrd; Alexandre B. Roland; Stephanie N. Caty; Nisha Kabir; Elicio E. Tapia; Sunia A. Trauger; Luis A. Coloma; Lauren A. O’Connell (Journal of Chemical Ecology, 2016)

Erratum to: Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog - Jenna R. McGugan; Gary D. Byrd; Alexandre B. Roland; Stephanie N. Caty; Nisha Kabir; Elicio E. Tapia; Sunia A. Trauger; Luis A. Coloma; Lauren A. O’Connell (Journal of Chemical Ecology, 2016)

Resource availability influences aggression and response to chemical cues in the Neotropical termite Nasutitermes aff. coxipoensis (Termitidae: Nasutitermitinae) - Paulo F. Cristaldo; Ana P. A. Araújo; Camilla S. Almeida; Nayara G. Cruz; Efrem J. M. Ribeiro; Marcos L. C. Rocha; Alisson S. Santana; Abraão A. Santos; Alexandre Passos; Og De Souza; Daniela F. Florencio (Behavioral Ecology and Sociobiology, 2016)

Diversity gradients of Neotropical freshwater fish: evidence of multiple underlying factors in human‐modified systems - Dayani Bailly; Fernanda A. S. Cassemiro; Kirk O. Winemiller; José Alexandre F. Diniz‐Filho; Angelo A. Agostinho (Journal of Biogeography, 2016)
Aim Contemporary patterns of species diversity are the result of a hierarchy of natural processes and modern anthropogenic influences. However, studies of these patterns in human‐modified systems from a macroecological perspective are lacking. Considering that fish assemblages in reservoirs reflect both long‐term evolutionary responses of species and shorter term responses to anthropogenic stressors, we employed a multi‐hypothesis approach using different magnitudes of predictors to analyse the processes that drive fish diversity in reservoirs at a broad spatial scale. Location Brazil. Methods We derived species richness from an extensive database of fish inhabiting Neotropical reservoirs, and using multiple regression analysis, we tested seven hypotheses that link species richness to continuous variables associated with regional, local and population components. We analysed the spatial structure using Moran's I autocorrelation coefficients and used spatial eigenvector mapping to explicitly account for the spatial component when testing the hypotheses by multiple regressions. Partial regressions were performed to map the relative contributions of the different components in explaining species richness. Results Predictors related to six hypotheses were retained in the best‐fit models, and our data supported the species–energy, metabolic, species–area, species–distance from the source and time of habitat alteration hypotheses. However, the predictions of the population abundance hypothesis (PAH) were not supported by the data. The shared effects of the different components explained the greatest proportion of the variation in species richness, indicating that distinct mechanisms related to these alternative hypotheses interact or are not spatially independent. Main conclusions Our findings indicate that the latitudinal diversity gradient typically displayed by freshwater fish is maintained in human‐modified habitats, such as reservoirs, and that multiple mechanisms drive fish diversity in reservoirs over large spatial scales. The lack of support for the PAH implies that mechanisms structuring diversity patterns can be influenced by anthropogenic stressors.

Population structure of a vector‐borne plant parasite - Kelsey M. Yule; Jennifer A. H. Koop; Nicolas M. Alexandre; Lauren R. Johnston; Noah K. Whiteman (Molecular Ecology, 2016)
Parasites are among the most diverse groups of life on Earth, yet complex natural histories often preclude studies of their speciation processes. The biology of parasitic plants facilitates in situ collection of data on both genetic structure and the mechanisms responsible for that structure. Here, we studied the role of mating, dispersal and establishment in host race formation of a parasitic plant. We investigated the population genetics of a vector‐borne desert mistletoe ( Phoradendron californicum ) across two legume host tree species ( Senegalia greggii and Prosopis velutina ) in the Sonoran desert using microsatellites. Consistent with host race formation, we found strong host‐associated genetic structure in sympatry, little genetic variation due to geographic site and weak isolation by distance. We hypothesize that genetic differentiation results from differences in the timing of mistletoe flowering by host species, as we found initial flowering date of individual mistletoes correlated with genetic ancestry. Hybrids with intermediate ancestry were detected genetically. Individuals likely resulting from recent, successful establishment events following dispersal between the host species were detected at frequencies similar to hybrids between host races. Therefore, barriers to gene flow between the host races may have been stronger at mating than at dispersal. We also found higher inbreeding and within‐host individual relatedness values for mistletoes on the more rare and isolated host species ( S. greggii ). Our study spanned spatial scales to address how interactions with both vectors and hosts influence parasitic plant structure with implications for parasite virulence evolution and speciation.

Accounting for habitat and seafloor structure characteristics on southern rock lobster (Jasus edwardsii) assessment in a small marine reserve - Mary A. Young; Daniel Ierodiaconou; Matt Edmunds; Lachlan Hulands; Alexandre C. G. Schimel (Marine Biology, 2016)

Modeling the dynamics of DDT in a remote tropical floodplain: indications of post-ban use? - Annelle Mendez; Carla A. Ng; João Paulo Machado Torres; Wanderley Bastos; Christian Bogdal; George Alexandre dos Reis; Konrad Hungerbuehler (Environmental Science and Pollution Research, 2016)

Non-linear Optical Responses of Low-Density Lipoprotein are Associated with Intima-Media Thickness of Carotid Artery in Athletes - Henrique Andrade R. Fonseca; Célia R. Bittencourt; Francisco A. Fonseca; Andrea M. Monteiro; Priscila R. Santos; Luciano Camargo; Luiz A. R. Costa; Alexandre Murad; Magnus Gidlund; Antonio M. Figueiredo-Neto; Maria Cristina O. Izar (Cell Biochemistry and Biophysics, 2016)

Determinants of variation in heath vegetation structure on coastal dune fields in northeastern South America - Augusto C. Silva; José Luiz A. Silva; Alexandre F. Souza (Brazilian Journal of Botany, 2016)

Ant and Mite Diversity Drives Toxin Variation in the Little Devil Poison Frog - Jenna R. McGugan; Gary D. Byrd; Alexandre B. Roland; Stephanie N. Caty; Nisha Kabir; Elicio E. Tapia; Sunia A. Trauger; Luis A. Coloma; Lauren A. O’Connell (Journal of Chemical Ecology, 2016)

PlanTE-MIR DB: a database for transposable element-related microRNAs in plant genomes - Alan P. R. Lorenzetti; Gabriel Y. A. de Antonio; Alexandre R. Paschoal; Douglas S. Domingues (Functional & Integrative Genomics, 2016)

Coprophilic amoebae and flagellates, including Guttulinopsis, Rosculus and Helkesimastix, characterise a divergent and diverse rhizarian radiation and contribute to a large diversity of faecal‐associated protists - David Bass; Jeffrey D. Silberman; Matthew W. Brown; Rebecca A. Pearce; Alexander K. Tice; Alexandre Jousset; Stefan Geisen; Hanna Hartikainen (Environmental Microbiology, 2016)
Summary A wide diversity of organisms utilize faecal habitats as a rich nutrient source or a mechanism to traverse through animal hosts. We sequenced the 18S rRNA genes of the coprophilic, fruiting body‐forming amoeba Guttulinopsis vulgaris and its non‐fruiting relatives Rosculus ‘ithacus’ CCAP 1571/3, R. terrestris n. sp. and R. elongata n. sp. and demonstrate that they are related to the coprophilic flagellate Helkesimastix in a strongly supported, but highly divergent 18S sister clade. PCR primers specific to both clades were used to generate 18S amplicons from a range of environmental and faecal DNA samples. Phylogenetic analysis of the cloned sequences demonstrated a high diversity of uncharacterised sequence types within this clade, likely representing previously described members of the genera Guttulinopsis , Rosculus and Helkesimastix , as well as so‐far unobserved organisms. Further, an Illumina MiSeq sequenced set of 18S V4‐region amplicons generated from faecal DNAs using universal eukaryote primers showed that core‐cercozoan assemblages in faecal samples are as diverse as those found in more conventionally examined habitats. These results reveal many novel lineages, some of which appear to occur preferentially in faecal material, in particular cercomonads and glissomonads. More broadly, we show that faecal habitats are likely untapped reservoirs of microbial eukaryotic diversity.

Idiosyncratic responses of Amazonian birds to primary forest disturbance - Nárgila G. Moura; Alexander C. Lees; Alexandre Aleixo; Jos Barlow; Erika Berenguer; Joice Ferreira; Ralph Mac Nally; James R. Thomson; Toby A. Gardner (Oecologia, 2016)

Non-dopamine receptor ligands for the treatment of Parkinson’s disease. Insight into the related chemical/property space - Yan A. Ivanenkov; Mark S. Veselov; Nina V. Chufarova; Alexander G. Majouga; Anna A. Kudryavceva; Alexandre V. Ivachtchenko (Molecular Diversity, 2016)

Potato virus Y infection affects flavonoid profiles of Physalis angulata L. - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Déborah Y. A. C. dos Santos (Brazilian Journal of Botany, 2015)

Inhibition of cyclin-dependent kinase CDK1 by oxindolimine ligands and corresponding copper and zinc complexes - Rodrigo Bernardi Miguel; Philippe Alexandre Divina Petersen; Fernando A. Gonzales-Zubiate; Carla Columbano Oliveira; Naresh Kumar; Rafael Rodrigues do Nascimento; Helena Maria Petrilli; Ana Maria da Costa Ferreira (JBIC Journal of Biological Inorganic Chemistry, 2015)

Characterization of postdive recovery using sound recordings and its relationship to dive duration, exertion, and foraging effort of southern elephant seals ( Mirounga leonina ) - Alexandre Génin; Gaëtan Richard; Joffrey Jouma'a; Baptiste Picard; Nory El Ksabi; Jade Vacquié Garcia; Christophe Guinet (Marine Mammal Science, 2015)
It is notoriously difficult to measure physiological parameters in cryptic free‐ranging marine mammals. However, it is critical to understand how marine mammals manage their energy expenditure and their diving behavior in environments where the predation risks are low and where survival is mainly linked to capacities to maintain physiological homeostasis and energy budget balance. Elephant seals are top marine predators that dive deeply and continuously when at sea. Using acoustic recorders deployed on two postbreeding southern elephant seals ( SES ) females, we developed methods to automatically estimate breathing frequency at the surface. Using this method, we found that seals took successive identical breaths at high frequency (0.29 Hz) when recovering at the surface and that breath count was strongly related to postdive surfacing time. In addition, dive depth was the main factor explaining surfacing time through the effects of dive duration and total underwater swimming effort exerted. Finally, we found that recovery does not only occur over one dive timescale, but over a multidive time scale for one individual. The way these predators manage their recovery will determine how they respond to the change in oceanic water column structure in the future.

Species interactions regulate the collapse of biodiversity and ecosystem function in tropical forest fragments - Tom P. Bregman; Alexander C. Lees; Nathalie Seddon; Hannah E. A. MacGregor; Bianca Darski; Alexandre Aleixo; Michael B. Bonsall; Joseph A. Tobias (Ecology, 2015)
Competitive interactions among species with similar ecological niches are known to regulate the assembly of biological communities. However, it is not clear whether such forms of competition can predict the collapse of communities and associated shifts in ecosystem function in the face of environmental change. Here, we use phylogenetic and functional trait data to test whether communities of two ecologically important guilds of tropical birds (frugivores and insectivores) are structured by species interactions in a fragmented Amazonian forest landscape. In both guilds, we found that forest patch size, quality, and degree of isolation influence the phylogenetic and functional trait structure of communities, with small, degraded, or isolated forest patches having an increased signature of competition (i.e., phylogenetic and functional trait overdispersion in relation to null models). These results suggest that local extinctions in the context of fragmentation are nonrandom, with a consistent bias toward more densely occupied regions of niche space. We conclude that the loss of biodiversity in fragmented landscapes is mediated by niche‐based competitive interactions among species, with potentially far‐reaching implications for key ecosystem processes, including seed dispersal and plant damage by phytophagous insects.

Experimental characterization of the out-of-plane performance of regular stone masonry walls, including test setups and axial load influence - Tiago Miguel Ferreira; Alexandre A. Costa; António Arêde; Ana Gomes; Aníbal Costa (Bulletin of Earthquake Engineering, 2015)

How much do we know about the endangered Atlantic Forest? Reviewing nearly 70 years of information on tree community surveys - Renato A. F. de Lima; Danilo P. Mori; Gregory Pitta; Melina O. Melito; Carolina Bello; Luiz F. Magnago; Victor P. Zwiener; Daniel D. Saraiva; Márcia C. M. Marques; Alexandre A. de Oliveira; Paulo I. Prado (Biodiversity and Conservation, 2015)

Cannabidiol Exposure During Neuronal Differentiation Sensitizes Cells Against Redox-Active Neurotoxins - Patrícia Schönhofen; Liana M. de Medeiros; Ivi Juliana Bristot; Fernanda M. Lopes; Marco A. De Bastiani; Flávio Kapczinski; José Alexandre S. Crippa; Mauro Antônio A. Castro; Richard B. Parsons; Fábio Klamt (Molecular Neurobiology, 2015)

Conservation of Brosimum alicastrum, an underutilized crop and keystone forest tree species; a potential win–win for conservation and development in Latin America - Tonya A. Lander; Alexandre Monro (Biodiversity and Conservation, 2015)

Does extreme environmental severity promote plant facilitation? An experimental field test in a subtropical coastal dune - Camila T. Castanho; Alexandre A. Oliveira; Paulo Inácio K. L. Prado (Oecologia, 2015)

The anuran calling repertoire in the light of social context - Luís F. Toledo; Itamar A. Martins; Daniel P. Bruschi; Michel A. Passos; César Alexandre; Célio F. B. Haddad (acta ethologica, 2015)

3-Indol carboxaldehyde, an imidazole synthesized from naphthoquinone β-lapachone downregulates Candida albicans biofilm - José Alexandre da Rocha Curvelo; Anna Lea Silva Barreto; Camila A. dos Anjos; Rafaela S. Santana; Ariadne Nunes Alonso; Maria Teresa Vilela Romanos; Kelly C. G. de Moura; Paula Fernandes Carneiro; Maristela Barbosa Portela; Maria do Carmo F. R. Pinto; Rosangela Maria de Araújo Soares (Medicinal Chemistry Research, 2015)

Information Retention During Competitive Interactions: Siblings Need to Constantly Repeat Vocal Displays - Amélie N. Dreiss; Charlène A. Ruppli; Sévrine Antille; Alexandre Roulin (Evolutionary Biology, 2015)

Species richness and areas of endemism of oryzomyine rodents (Cricetidae, Sigmodontinae) in South America: an ndm / vndm approach - Joyce R. do Prado; Pamella G. G. Brennand; Leandro P. Godoy; Gustavo S. Libardi; Edson F. de Abreu‐Júnior; Paulo R. O. Roth; Elisandra A. Chiquito; Alexandre R. Percequillo (Journal of Biogeography, 2015)
Aim To infer areas of endemism for the tribe Oryzomyini in South America by employing a database of species richness and geographical distribution, and to compare these results with areas of endemism and species richness proposed in the literature for other taxa. Location We analysed specimens of the tribe Oryzomyini distributed throughout South and Central America, which are housed in European, North and South American museums and collections. Methods We analysed 2768 occurrence records for 102 species of the tribe Oryzomyini using the ndm / vndm algorithm and three different grid sizes to assess the possible effects of grid cell area on the results. Results Using the overlap of consensus areas in South America, we identified three generalized areas of endemism for the Oryzomyini: north‐western South America ( NWSA ), eastern South American ( ESA ), and northern South America ( NSA ); we also identified the Galápagos archipelago ( GA ) as an area of endemism. Main conclusions Areas of endemism detected in the continental portion of South America include its three main mountain chains: the Andes Cordillera, the Guyanan Shields, and an area east of the Brazilian Shield named Serra do Mar. Each of these regions encompasses many different types of vegetation, and the species richness and composition of the areas of endemism of the tribe are directly related to this environmental diversity. Different grid sizes affected the distributional heterogeneity of the consensus areas. The smallest grid cell size identified mainly Andean areas, which contain a higher number of more exclusive species in a small area along a steep elevational gradient. In contrast, the largest grid size identified areas of endemism along an environmental gradient that co‐varied with latitude and longitude. The identified areas of endemism are corroborated by previous studies on other taxa.

Energy acquisition and allocation to egg production in relation to fish reproductive strategies - Richard S McBride; Stylianos Somarakis; Gary R Fitzhugh; Anu Albert; Nathalia A Yaragina; Mark J Wuenschel; Alexandre Alonso‐Fernández; Gualtiero Basilone (Fish and Fisheries, 2015)
Oogenesis in fishes follows a universal plan; yet, due to differences in the synchrony and rate of egg development, spawning frequency varies from daily to once in a lifetime. Some species spawn and feed in separate areas, during different seasons, by storing energy and drawing on it later for reproduction (i.e. capital breeding). Other species spawn using energy acquired locally, throughout a prolonged spawning season, allocating energy directly to reproduction (i.e. income breeding). Capital breeders tend to ovulate all at once and are more likely to be distributed at boreal latitudes. Income breeding allows small fish to overcome allometric constraints on egg production. Income breeders can recover more quickly when good‐feeding conditions are re‐established, which is a benefit to adults regarding bet‐hedging spawning strategies. Many species exhibit mixed capital‐ and income‐breeding patterns. An individual's position along this capital–income continuum may shift with ontogeny or in relation to environmental conditions, so breeding patterns are a conditional reproductive strategy. Poor‐feeding environments can lead to delayed maturation, skipped spawning, fewer spawning events per season or fewer eggs produced per event. In a few cases, variations in feeding environments appear to affect recruitment variability. These flexible processes of energy acquisition and allocation allow females to prioritize their own condition over their propagules' condition at any given spawning opportunity, thereby investing energy cautiously to maximize lifetime reproductive value. These findings have implications for temporal and spatial sampling designs, for measurement and interpretation of fecundity, and for interpreting fishery and ecosystem assessments.

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Phylogeny and recombination analysis of Brazilian yellow passion fruit isolates of Cowpea aphid-borne mosaic virus: origin and relationship with hosts - Leilane K. Rodrigues; Leonardo A. Silva; Renata M. Garcêz; Alexandre L. R. Chaves; Ligia M. L. Duarte; José S. Giampani; Addolorata Colariccio; Ricardo Harakava; Marcelo Eiras (Australasian Plant Pathology, 2015)

Wolbachia do not live by reproductive manipulation alone: infection polymorphism in Drosophila suzukii and D. subpulchrella - Christopher A. Hamm; David J. Begun; Alexandre Vo; Chris C. R. Smith; Perot Saelao; Amanda O. Shaver; John Jaenike; Michael Turelli (Molecular Ecology, 2014)
Drosophila suzukii recently invaded North America and Europe. Populations in Hawaii, California, New York and Nova Scotia are polymorphic for Wolbachia , typically with Wolbachia in D. suzukii , denoted w S uz, is closely related to w R i, the variant prevalent in continental populations of D. simulans . w S uz is also nearly identical to Wolbachia found in D. subpulchrella , plausibly D. suzukii 's sister species. This suggests vertical Wolbachia transmission through cladogenesis (‘cladogenic transmission’). The widespread occurrence of 7–20% infection frequencies indicates a stable polymorphism. w S uz is imperfectly maternally transmitted, with wild infected females producing on average 5–10% uninfected progeny. As expected from its low frequency, w S uz produces no cytoplasmic incompatibility (CI), that is, no increased embryo mortality when infected males mate with uninfected females, and no appreciable sex‐ratio distortion. The persistence of w S uz despite imperfect maternal transmission suggests positive fitness effects. Assuming a balance between selection and imperfect transmission, we expect a fitness advantage on the order of 20%. Unexpectedly, Wolbachia ‐infected females produce fewer progeny than do uninfected females. We do not yet understand the maintenance of w S uz in D. suzukii . The absence of detectable CI in D. suzukii and D. subpulchrella makes it unlikely that CI‐based mechanisms could be used to control this species without transinfection using novel Wolbachia . Contrary to their reputation as horizontally transmitted reproductive parasites, many Wolbachia infections are acquired through introgression or cladogenesis and many cause no appreciable reproductive manipulation. Such infections, likely to be mutualistic, may be central to understanding the pervasiveness of Wolbachia among arthropods.

Two Hundred Years of Local Avian Extinctions in Eastern Amazonia - NÁRGILA G. MOURA; ALEXANDER C. LEES; ALEXANDRE ALEIXO; JOS BARLOW; SIDNEI M. DANTAS; JOICE FERREIRA; MARIA DE FÁTIMA C. LIMA; TOBY A. GARDNER (Conservation Biology, 2014)
Local, regional, and global extinctions caused by habitat loss, degradation, and fragmentation have been widely reported for the tropics. The patterns and drivers of this loss of species are now increasingly well known in Amazonia, but there remains a significant gap in understanding of long‐term trends in species persistence and extinction in anthropogenic landscapes. Such a historical perspective is critical for understanding the status and trends of extant biodiversity as well as for identifying priorities to halt further losses. Using extensive historical data sets of specimen records and results of contemporary surveys, we searched for evidence of local extinctions of a terra firma rainforest avifauna over 200 years in a 2500 km 2 eastern Amazonian region around the Brazilian city of Belém. This region has the longest history of ornithological fieldwork in the entire Amazon basin and lies in the highly threatened Belém Centre of Endemism. We also compared our historically inferred extinction events with extensive data on species occurrences in a sample of catchments in a nearby municipality (Paragominas) that encompass a gradient of past forest loss. We found evidence for the possible extinction of 47 species (14% of the regional species pool) that were unreported from 1980 to 2013 (80% last recorded between 1900 and 1980). Seventeen species appear on the International Union for Conservation of Nature Red List, and many of these are large‐bodied. The species lost from the region immediately around Belém are similar to those which are currently restricted to well‐forested catchments in Paragominas. Although we anticipate the future rediscovery or recolonization of some species inferred to be extinct by our calculations, we also expect that there are likely to be additional local extinctions, not reported here, given the ongoing loss and degradation of remaining areas of native vegetation across eastern Amazonia. Doscientos Años de Extinciones Locales de Aves en la Amazonia Oriental

Erratum to: Strontium ranelate changes the composition and crystal structure of the biological bone-like apatite produced in osteoblast cell cultures - William Querido; Andrea P. C. Campos; Erlon H. Martins Ferreira; Rosane A. S. San Gil; Alexandre M. Rossi; Marcos Farina (Cell and Tissue Research, 2014)

Strontium ranelate changes the composition and crystal structure of the biological bone-like apatite produced in osteoblast cell cultures - William Querido; Andrea P. C. Campos; Erlon H. Martins Ferreira; Rosane A. S. San Gil; Alexandre M. Rossi; Marcos Farina (Cell and Tissue Research, 2014)

Phytoplankton spatial distribution on the Continental Shelf off Rio de Janeiro, from Paraíba do Sul River to Cabo Frio - Gleyci A. O. Moser; Robson Alves Takanohashi; Mariana de Chagas Braz; Domênica Teixeira de Lima; Fabiana Vasconcelos Kirsten; Josefa Varela Guerra; Alexandre M. Fernandes; Ricardo César Gonçalves Pollery (Hydrobiologia, 2014)

Influence of tea tree oil (Melaleuca alternifolia) on the cattle tick Rhipicephalus microplus - Rafael Pazinato; Vanderlei Klauck; Andreia Volpato; Alexandre A. Tonin; Roberto C. Santos; Márcia E. de Souza; Rodrigo A. Vaucher; Renata Raffin; Patrícia Gomes; Candice C. Felippi; Lenita M. Stefani; Aleksandro S. Da Silva (Experimental and Applied Acarology, 2014)

Distinct Response of Lactating and Nonlactating Rats Exposed to Inorganic Mercury on Hepatic δ-Aminolevulinic Acid Dehydratase Activity - Cláudia S. Oliveira; Alexandre M. Favero; Carina Franciscato; Sônia C. A. da Luz; Maria Ester Pereira (Biological Trace Element Research, 2014)

Climatic niche at physiological and macroecological scales: the thermal tolerance–geographical range interface and niche dimensionality - Sidney F. Gouveia; Joaquín Hortal; Miguel Tejedo; Helder Duarte; Fernanda A. S. Cassemiro; Carlos A. Navas; José Alexandre F. Diniz‐Filho (Global Ecology and Biogeography, 2014)
Aim Under the H utchinsonian concept of the realized niche, biotic interactions and dispersal limitation may prevent species from fully occupying areas that they could tolerate physiologically. This can hamper the translation of physiological limits into climatically defined range limits and distorts inferences of evolutionary changes of the adaptive limits (i.e. niche conservatism). In contrast, heritable physiological limits should conform more closely to the position of the niche in the climatic hyperspace. Here, we hypothesize that a measure of niche position in the climatic hyperspace is more reliable than niche boundaries to capture the variability and evolutionary pattern of physiological tolerance. Location N eotropics and P alaeartic. Methods We used phylogenetic and non‐phylogenetic regressions to test the relationships between physiological requirements and macroecological niche features (i.e. based on known species distributions) among anurans. We use larval critical thermal maximum ( CT max ) as a measure of physiological response and maximum temperature ( T max ), temperature variability ( T var ) and the position and breadth of niche in climatic hyperspace as measures of the realized niche in geographical space. We also compare evolutionary rates among these parameters using the phylogenetic signal representation curve. Results CT max is better correlated with niche position ( r 2 = 0.414) than with T var , and CT max is unrelated to either T max or niche breadth. CT max and macroecological niche position also show similar and rapid evolutionary rates, i.e. faster than B rownian motion, whereas T max and T var evolve more slowly and niche breadth evolves at random. Main conclusions The transferability between thermal tolerance and realized climatic niche limits is weak. Only macroecological niche position in the multivariate climatic hyperspace correlates with physiological tolerance. It thus appears to be more suitable for describing the variability and evolutionary pattern of the species' adaptive limits. We link these results to ‘niche dimensionality’, in that multiple interacting factors outweigh single factors in demarcating the species' realized climatic niche, thereby determining the conserved upper thermal limits of the species.

Probing the carotenoid content of intact Cyclotella cells by resonance Raman spectroscopy - Maxime T. A. Alexandre; Kathi Gundermann; Andrew A. Pascal; Rienk van Grondelle; Claudia Büchel; Bruno Robert (Photosynthesis Research, 2014)

Phenotyping soybean plants transformed with rd29A:AtDREB1A for drought tolerance in the greenhouse and field - Amanda Alves de Paiva Rolla; Josirley de Fátima Corrêa Carvalho; Renata Fuganti-Pagliarini; Cibelle Engels; Alexandre do Rio; Silvana Regina Rockenbach Marin; Maria Cristina Neves de Oliveira; Magda A. Beneventi; Francismar Corrêa Marcelino-Guimarães; José Renato Bouças Farias; Norman Neumaier; Kazuo Nakashima; et al. (Transgenic Research, 2014)

The putative BH3 mimetic S1 sensitizes leukemia to ABT-737 by increasing reactive oxygen species, inducing endoplasmic reticulum stress, and upregulating the BH3-only protein NOXA - Ryan Soderquist; Alexandre A. Pletnev; Alexey V. Danilov; Alan Eastman (Apoptosis, 2014)

Community phylogenetics at the biogeographical scale: cold tolerance, niche conservatism and the structure of N orth A merican forests - Bradford A. Hawkins; Marta Rueda; Thiago F. Rangel; Richard Field; José Alexandre F. Diniz‐Filho (Journal of Biogeography, 2014)
Aim The fossil record has led to a historical explanation for forest diversity gradients within the cool parts of the Northern Hemisphere, founded on a limited ability of woody angiosperm clades to adapt to mid‐Tertiary cooling. We tested four predictions of how this should be manifested in the phylogenetic structure of 91,340 communities: (1) forests to the north should comprise species from younger clades (families) than forests to the south; (2) average cold tolerance at a local site should be associated with the mean family age (MFA) of species; (3) minimum temperature should account for MFA better than alternative environmental variables; and (4) traits associated with survival in cold climates should evolve under a niche conservatism constraint. Location The contiguous U nited S tates. Methods We extracted angiosperms from the US Forest Service's Forest Inventory and Analysis database. MFA was calculated by assigning age of the family to which each species belongs and averaging across the species in each community. We developed a phylogeny to identify phylogenetic signal in five traits: realized cold tolerance, seed size, seed dispersal mode, leaf phenology and height. Phylogenetic signal representation curves and phylogenetic generalized least squares were used to compare patterns of trait evolution against Brownian motion. Eleven predictors structured at broad or local scales were generated to explore relationships between environment and MFA using random forest and general linear models. Results Consistent with predictions, (1) southern communities comprise angiosperm species from older families than northern communities, (2) cold tolerance is the trait most strongly associated with local MFA, (3) minimum temperature in the coldest month is the environmental variable that best describes MFA, broad‐scale variables being much stronger correlates than local‐scale variables, and (4) the phylogenetic structures of cold tolerance and at least one other trait associated with survivorship in cold climates indicate niche conservatism. Main conclusions Tropical niche conservatism in the face of long‐term climate change, probably initiated in the Late Cretaceous associated with the rise of the Rocky Mountains, is a strong driver of the phylogenetic structure of the angiosperm component of forest communities across the USA . However, local deterministic and/or stochastic processes account for perhaps a quarter of the variation in the MFA of local communities.

Efficiency and Significance of Multiple Vocal Signals in Sibling Competition - Charlène A. Ruppli; Amélie N. Dreiss; Alexandre Roulin (Evolutionary Biology, 2013)

Poor fen succession over ombrotrophic peat related to late Holocene increased surface wetness in subarctic Quebec, Canada - SIMON VAN BELLEN; MICHELLE GARNEAU; ADAM A. ALI; ALEXANDRE LAMARRE; ÉLISABETH C. ROBERT; GABRIEL MAGNAN; HANS ASNONG; STEVE PRATTE (Journal of Quaternary Science, 2013)
Northern peatlands act as archives of environmental change through their sensitivity to water balance fluctuations, while being significant contributors to global greenhouse gas dynamics. Subarctic fens in north‐eastern Canada are characterized by a dominance of pools and flarks. We aimed to reconstruct the late Holocene hydrological conditions of these fens to establish the timing of the initiation of pool and flark formation and possible links with climate. Testate amoebae and plant macrofossils from five cores, sampled in three fens, were analysed to infer water tables with chronologies based on 14 C and 210 Pb dating. All sites showed the presence of relatively dry, ombrotrophic conditions with abundant Picea from 5000 cal a BP, followed by a first shift to wet, poor fen conditions with pool and flark development around 3000 cal a BP and a subsequent wet shift after ∼800 cal a BP. These trends coincide with previously observed Neoglacial and Little Ice Age cooler and wetter conditions and therefore climate may well have been a dominant factor in the initiation and development of pools and flarks over the late Holocene. The effect of anticipated climate change on subarctic peatlands remains unclear, although wetter conditions might enhance pool expansion to the detriment of terrestrial components.

Role of TRAV locus in low caries experience - Jessica Briseño-Ruiz; Takehiko Shimizu; Kathleen Deeley; Piper M. Dizak; Timothy D. Ruff; Italo M. Faraco; Fernando A. Poletta; João A. Brancher; Giovana D. Pecharki; Erika C. Küchler; Patricia N. Tannure; Andrea Lips; et al. (Human Genetics, 2013)

Effect of Stearic Acid on Enalapril Stability and Dissolution from Multiparticulate Solid Dosage Forms - Talita A. Cunha; Raphael C. Serpa; Ana Paula M. de Oliveira; Letícia N. Nasser; Luis Alexandre P. de Freitas; Stephania F. Taveira; Danielle G. A. Diniz; Eliana M. Lima; Ricardo N. Marreto (AAPS PharmSciTech, 2013)

The Lesion Simulating Disease (LSD) gene family as a variable in soybean response to Phakopsora pachyrhizi infection and dehydration - Caroline Cabreira; Alexandro Cagliari; Lauro Bücker-Neto; Beatriz Wiebke-Strohm; Loreta B. de Freitas; Francismar C. Marcelino-Guimarães; Alexandre L. Nepomuceno; Márcia M. A. N. Margis-Pinheiro; Maria H. Bodanese-Zanettini (Functional & Integrative Genomics, 2013)

How much land‐based greenhouse gas mitigation can be achieved without compromising food security and environmental goals? - Pete Smith; Helmut Haberl; Alexander Popp; Karl‐heinz Erb; Christian Lauk; Richard Harper; Francesco N. Tubiello; Alexandre de Siqueira Pinto; Mostafa Jafari; Saran Sohi; Omar Masera; Hannes Böttcher; et al. (Global Change Biology, 2013)
Feeding 9–10 billion people by 2050 and preventing dangerous climate change are two of the greatest challenges facing humanity. Both challenges must be met while reducing the impact of land management on ecosystem services that deliver vital goods and services, and support human health and well‐being. Few studies to date have considered the interactions between these challenges. In this study we briefly outline the challenges, review the supply‐ and demand‐side climate mitigation potential available in the Agriculture, Forestry and Other Land Use AFOLU sector and options for delivering food security. We briefly outline some of the synergies and trade‐offs afforded by mitigation practices, before presenting an assessment of the mitigation potential possible in the AFOLU sector under possible future scenarios in which demand‐side measures codeliver to aid food security. We conclude that while supply‐side mitigation measures, such as changes in land management, might either enhance or negatively impact food security, demand‐side mitigation measures, such as reduced waste or demand for livestock products, should benefit both food security and greenhouse gas ( GHG ) mitigation. Demand‐side measures offer a greater potential (1.5–15.6 Gt CO 2 ‐eq. yr −1 ) in meeting both challenges than do supply‐side measures (1.5–4.3 Gt CO 2 ‐eq. yr −1 at carbon prices between 20 and 100 US$ t CO 2 ‐eq. yr −1 ), but given the enormity of challenges, all options need to be considered. Supply‐side measures should be implemented immediately, focussing on those that allow the production of more agricultural product per unit of input. For demand‐side measures, given the difficulties in their implementation and lag in their effectiveness, policy should be introduced quickly, and should aim to codeliver to other policy agenda, such as improving environmental quality or improving dietary health. These problems facing humanity in the 21st Century are extremely challenging, and policy that addresses multiple objectives is required now more than ever.

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Nonparallelism in MHCII β diversity accompanies nonparallelism in pathogen infection of lake whitefish ( C oregonus clupeaformis ) species pairs as revealed by next‐generation sequencing - Scott A. Pavey; Maelle Sevellec; William Adam; Eric Normandeau; Fabien C. Lamaze; Pierre‐Alexandre Gagnaire; Marie Filteau; Francois Olivier Hebert; Halim Maaroufi; Louis Bernatchez (Molecular Ecology, 2013)
Major histocompatibility ( MHC ) immune system genes may evolve in response to pathogens in the environment. Because they also may affect mate choice, they are candidates for having great importance in ecological speciation. Here, we use next‐generation sequencing to test the general hypothesis of parallelism in patterns of MHCII β diversity and bacterial infections among five dwarf and normal whitefish sympatric pairs. A second objective was to assess the functional relationships between specific MHCII β alleles and pathogens in natural conditions. Each individual had between one and four alleles, indicating two paralogous loci. In C liff Lake, the dwarf ecotype was monomorphic for the most common allele. In W ebster Lake, the skew in the allelic distribution was towards the same allele but in the normal ecotype, underscoring the nonparallel divergence among lakes. Our signal of balancing selection matched putative peptide binding region residues in some cases, but not in others, supporting other recent findings of substantial functional differences in fish MHCII β compared with mammals. Individuals with fewer alleles were less likely to be infected; thus, we found no evidence for the heterozygote advantage hypothesis. MHCII β alleles and pathogenic bacteria formed distinct clusters in multivariate analyses, and clusters of certain alleles were associated with clusters of pathogens, or sometimes the absence of pathogens, indicating functional relationships at the individual level. Given that patterns of MHCII β and bacteria were nonparallel among dwarf and normal whitefish pairs, we conclude that pathogens driving MHCII β evolution did not play a direct role in their parallel phenotypic evolution.

Functional Consequences of Oculomotor Disorders in Hereditary Cerebellar Ataxias - M. F. Alexandre; S. Rivaud-Péchoux; G. Challe; A. Durr; B. Gaymard (The Cerebellum, 2013)

Mapping phenotypic, expression and transmission ratio distortion QTL using RAD markers in the Lake Whitefish (Coregonus clupeaformis) - Pierre‐Alexandre Gagnaire; Eric Normandeau; Scott A. Pavey; Louis Bernatchez (Molecular Ecology, 2013)
The evolution of reproductive isolation in an ecological context may involve multiple facets of species divergence on which divergent selection may operate. These include variation in quantitative phenotypic traits, regulation of gene expression, and differential transmission of particular allelic combinations. Thus, an integrative approach to the speciation process involves identifying the genetic basis of these traits, in order to understand how they are affected by divergent selection in nature and how they ultimately contribute to reproductive isolation. In the Lake Whitefish ( Coregonus clupeaformis ), dwarf and normal species pairs sympatrically occur in several North American postglacial lakes. The limnetic dwarf whitefish distinguishes from its normal benthic relative by numerous life history, behavioural, morphological and gene expression traits, in relation with the exploitation of distinct ecological niches. Here, we have applied the RAD‐Sequencing method to a hybrid backcross family to reconstruct a high‐density genetic linkage map and perform QTL mapping in the Lake Whitefish. The 3061 cM map encompassed 3438 segregating RAD markers distributed over 40 linkage groups, for an average resolution of 0.89 cM. We mapped phenotypic and expression QTL underlying ecologically important traits as well as transmission ratio distortion QTL, and identified genomic regions harbouring clusters of such QTL. A narrow genomic region strongly associated with sex determination was also evidenced. Positional and functional information revealed in this study will be useful in ongoing population genomic studies to illuminate our understanding of the genomic architecture of reproductive isolation between whitefish species pairs.

Anxiogenic-like profile of Wistar adult rats based on the pilocarpine model: an animal model for trait anxiety? - Filipe S. Duarte; Marcelo Duzzioni; Alexandre A. Hoeller; Nayana M. Silva; Andy L. Ern; Tetsade C. Piermartiri; Carla I. Tasca; Elaine C. Gavioli; Tadeu Lemos; Antonio P. Carobrez; Thereza C. M. De Lima (Psychopharmacology, 2013)

The SHARE European Earthquake Catalogue (SHEEC) 1000–1899 - M. Stucchi; A. Rovida; A. A. Gomez Capera; P. Alexandre; T. Camelbeeck; M. B. Demircioglu; P. Gasperini; V. Kouskouna; R. M. W. Musson; M. Radulian; K. Sesetyan; S. Vilanova; et al. (Journal of Seismology, 2013)

Exercise-induced endocannabinoid signaling is modulated by intensity - David A. Raichlen; Adam D. Foster; Alexandre Seillier; Andrea Giuffrida; Gregory L. Gerdeman (European Journal of Applied Physiology, 2013)

Investigation of the sampling performance of ensemble-based methods with a simple reservoir model - Alexandre A. Emerick; Albert C. Reynolds (Computational Geosciences, 2013)

Lamellar Liquid Crystalline Phases for Cutaneous Delivery of Paclitaxel: Impact of the Monoglyceride - Jaclyn M. Hosmer; Alexandre A. Steiner; Luciana B. Lopes (Pharmaceutical Research, 2013)

Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Andy Siegenthaler; Alexandre Buttler; Philippe Grosvernier; Jean-Michel Gobat; Mats B. Nilsson; Edward A. D. Mitchell (Oecologia, 2013)

Euglobal-like compounds from the genus Eugenia - Larissa G. Faqueti; Christiane Maes Petry; Christiane Meyre-Silva; Karima E. Machado; Alexandre Belle Cruz; Pablo A. Garcia; Valdir Cechinel-Filho; Arturo San Feliciano; Franco Delle Monache (Natural Product Research, 2013)

Anti-inflammatory and anti-arthritic activities of 3,4-dihydro-2,2-dimethyl-2H-naphthol[1,2-b]pyran-5,6-dione (β-lapachone) - Marília Maria Sitônio; Carlson H. R. de Carvalho Júnior; Ingrid de A. Campos; José Bruno Nunes Ferreira Silva; Maria do Carmo Alves de Lima; Alexandre J. S. Góes; Maria Bernadete Sousa Maia; Pedro J. Rolim Neto; Teresinha G. Silva (Inflammation Research, 2013)

Estimating greenhouse gas emissions from cattle raising in Brazil - Mercedes M. C. Bustamante; Carlos A. Nobre; Roberto Smeraldi; Ana P. D. Aguiar; Luis G. Barioni; Laerte G. Ferreira; Karla Longo; Peter May; Alexandre S. Pinto; Jean P. H. B. Ometto (Climatic Change, 2012)

Isolation of microsatellite loci in the Amazon sailfin catfish Pterygoplichlhys pardalis (Castelneau, 1855) (Teleostei: Loricariidae) - Rosalina P. Pereira; Carlos Henrique dos A. dos Santos; Priscila Roberta M. Nascimento; Gisele T. Clímaco; Adna Cristina B. Sousa; Tatiana Campos; Alexandre Manoel K. Vergueiro-Júnior; Maria N. Paula-Silva; Vera Maria F. Almeida-Val (Conservation Genetics Resources, 2012)

Epidemiological aspects of HCV infection in HIV-infected individuals in Piauí State, Northeast Brazil - Aldemir B. Oliveira-Filho; Evaldo H. Oliveira; Jairo A. A. Castro; Letiano V. Silva; Antonio C. R. Vallinoto; José Alexandre R. Lemos (Archives of Virology, 2012)

Evaluating Methane Oxidation Efficiencies in Experimental Landfill Biocovers by Mass Balance and Carbon Stable Isotopes - Marlon A. Capanema; Alexandre R. Cabral (Water, Air, & Soil Pollution, 2012)

Corticosterone Promotes Scramble Competition Over Sibling Negotiation in Barn Owl Nestlings (Tyto alba) - Charlène A. Ruppli; Bettina Almasi; Amélie N. Dreiss; Marine Battesti; Lukas Jenni; Alexandre Roulin (Evolutionary Biology, 2012)

The importance of mesofauna and decomposition environment on leaf decomposition in three forests in southeastern Brazil - Camila T. Castanho; Leda Lorenzo; Alexandre A. de Oliveira (Plant Ecology, 2012)

Central leptin replacement enhances chemorespiratory responses in leptin-deficient mice independent of changes in body weight - Mirian Bassi; Humberto Giusti; Cristiane Mota Leite; Janete A. Anselmo-Franci; Jussara M. do Carmo; Alexandre A. da Silva; John E. Hall; Eduardo Colombari; Mogens L. Glass (Pflügers Archiv - European Journal of Physiology, 2012)

Ecological determinism increases with organism size - Vinicius F. Farjalla; Diane S. Srivastava; Nicholas A. C. Marino; Fernanda D. Azevedo; Viviane Dib; Paloma M. Lopes; Alexandre S. Rosado; Reinaldo L. Bozelli; Francisco A. Esteves (Ecology, 2012)
After much debate, there is an emerging consensus that the composition of many ecological communities is determined both by species traits, as proposed by niche theory, as well as by chance events. A critical question for ecology is, therefore, which attributes of species predict the dominance of deterministic or stochastic processes. We outline two hypotheses by which organism size could determine which processes structure ecological communities, and we test these hypotheses by comparing the community structure in bromeliad phytotelmata of three groups of organisms (bacteria, zooplankton, and macroinvertebrates) that encompass a 10 000‐fold gradient in body size, but live in the same habitat. Bacteria had no habitat associations, as would be expected from trait‐neutral stochastic processes, but still showed exclusion among species pairs, as would be expected from niche‐based processes. Macroinvertebrates had strong habitat and species associations, indicating niche‐based processes. Zooplankton, with body size between bacteria and macroinvertebrates, showed intermediate habitat associations. We concluded that a key niche process, habitat filtering, strengthened with organism size, possibly because larger organisms are both less plastic in their fundamental niches and more able to be selective in dispersal. These results suggest that the relative importance of deterministic and stochastic processes may be predictable from organism size.

Comparative study of the interaction of fullerenol nanoparticles with eukaryotic and bacterial model membranes using solid-state NMR and FTIR spectroscopy - Patrick P. Brisebois; Alexandre A. Arnold; Yoann M. Chabre; René Roy; Isabelle Marcotte (European Biophysics Journal, 2012)

History matching time-lapse seismic data using the ensemble Kalman filter with multiple data assimilations - Alexandre A. Emerick; Albert C. Reynolds (Computational Geosciences, 2012)

Annexin A1 protein attenuates cyclosporine-induced renal hemodynamics changes and macrophage infiltration in rats - Leandro Pires Araujo; Renata Ramos Truzzi; Gloria Elisa Florido Mendes; Marcus Alexandre Mendes Luz; Emmanuel A. Burdmann; Sonia Maria Oliani (Inflammation Research, 2012)

Out-of-plane behaviour of existing stone masonry buildings: experimental evaluation - Alexandre A. Costa; António Arêde; Aníbal Costa; Carlos Sousa Oliveira (Bulletin of Earthquake Engineering, 2012)

Experimental testing, numerical modelling and seismic strengthening of traditional stone masonry: comprehensive study of a real Azorian pier - Alexandre A. Costa; António Arêde; Aníbal Costa; João Guedes; Bruno Silva (Bulletin of Earthquake Engineering, 2012)

Climatic history and dispersal ability explain the relative importance of turnover and nestedness components of beta diversity - Ricardo Dobrovolski; Adriano S. Melo; Fernanda A. S. Cassemiro; José Alexandre Felizola Diniz‐Filho (Global Ecology and Biogeography, 2012)
Aim We tested whether the geographic variation in the proportion of beta diversity attributed to nestedness or turnover components was explained by the effect of past glaciation events. Specifically, we tested the hypothesis that most of the beta diversity in regions retaining ice until recent periods was due to nestedness. Additionally, we tested whether the variation was influenced by thermal tolerance and the dispersal ability of species. Location This study analysed data from the New World. Methods We used presence/absence data for amphibians, birds and mammals of the New World. We calculated beta diversity among each 1°× 1° cell and the adjacent cells using the Sorensen dissimilarity index that expresses the total beta diversity. Furthermore, we partitioned it into turnover and nestedness components. The relative importance of the two latter components was expressed as the proportion of total beta diversity explained by nestedness (β ratio ). We calculated the correlation between β ratio and the time each cell was free of ice since the last glaciation (cell age). To control the effects of spatial autocorrelation, we calculated geographically effective degrees of freedom. Results The proportion of beta diversity attributed to nestedness was negatively correlated with cell age. Moreover, this effect was stronger for amphibians than mammals, and stronger for mammals than birds. Main conclusions Our results are in accordance with the hypothesis that the nestedness component of beta diversity is more important in areas affected by glaciations until recent time. The beta diversity in high latitudes is the result of past extinctions and recent recolonization, which result in higher levels of nestedness. This process is more evident for vertebrates with lower dispersal ability and lower temperature tolerance.

Climate links and recent extremes in antarctic sea ice, high-latitude cyclones, Southern Annular Mode and ENSO - Alexandre Bernardes Pezza; Harun A. Rashid; Ian Simmonds (Climate Dynamics, 2012)

Nest box design for the study of diurnal raptors and owls is still an overlooked point in ecological, evolutionary and conservation studies: a review - Marcel M. Lambrechts; Karen L. Wiebe; Peter Sunde; Tapio Solonen; Fabrizio Sergio; Alexandre Roulin; Anders Pape Møller; Bernat C. López; Juan A. Fargallo; Klaus-Michael Exo; Giacomo Dell’Omo; David Costantini; et al. (Journal of Ornithology, 2012)

Host and habitat specialization of avian malaria in Africa - CLAIRE LOISEAU; RYAN J. HARRIGAN; ALEXANDRE ROBERT; RAURI C. K. BOWIE; HENRI A. THOMASSEN; THOMAS B. SMITH; RAVINDER N. M. SEHGAL (Molecular Ecology, 2012)
Studies of both vertebrates and invertebrates have suggested that specialists, as compared to generalists, are likely to suffer more serious declines in response to environmental change. Less is known about the effects of environmental conditions on specialist versus generalist parasites. Here, we study the evolutionary strategies of malaria parasites ( Plasmodium spp.) among different bird host communities. We determined the parasite diversity and prevalence of avian malaria in three bird communities in the lowland forests in Cameroon, highland forests in East Africa and fynbos in South Africa. We calculated the host specificity index of parasites to examine the range of hosts parasitized as a function of the habitat and investigated the phylogenetic relationships of parasites. First, using phylogenetic and ancestral reconstruction analyses, we found an evolutionary tendency for generalist malaria parasites to become specialists. The transition rate at which generalists become specialists was nearly four times as great as the rate at which specialists become generalists. We also found more specialist parasites and greater parasite diversity in African lowland rainforests as compared to the more climatically variable habitats of the fynbos and the highland forests. Thus, with environmental changes, we anticipate a change in the distribution of both specialist and generalist parasites with potential impacts on bird communities.

Identification of defence-related genes expressed in coffee and citrus during infection by Xylella fastidiosa - Marcelo F. Carazzolle; Fernanda R. Rabello; Natália F. Martins; Alessandra A. de Souza; Alexandre M. do Amaral; Juliana Freitas-Astua; Gonçalo A. G. Pereira; Marcos A. Machado; Angela Mehta (European Journal of Plant Pathology, 2011)

Dosage-dependent shift in the spore community of arbuscular mycorrhizal fungi following application of tannery sludge - André S. Nakatani; Denise L. C. Mescolotti; Marco A. Nogueira; Alexandre M. Martines; Marina Y. H. Miyauchi; Sidney L. Stürmer; Elke J. B. N. Cardoso (Mycorrhiza, 2011)

Advances in understanding the Kombolgie Subgroup and unconformity-related uranium deposits in the Alligator Rivers Uranium Field and how to explore for them using lithogeochemical principles - P. A. Polito; T. K. Kyser; P. Alexandre; E. E. Hiatt; C. R. Stanley (Australian Journal of Earth Sciences, 2011)

Chilean Blue Whales as a Case Study to Illustrate Methods to Estimate Abundance and Evaluate Conservation Status of Rare Species - ROB WILLIAMS; SHARON L. HEDLEY; TREVOR A. BRANCH; MARK V. BRAVINGTON; ALEXANDRE N. ZERBINI; KEN P. FINDLAY (Conservation Biology, 2011)
Often abundance of rare species cannot be estimated with conventional design‐based methods, so we illustrate with a population of blue whales ( Balaenoptera musculus ) a spatial model‐based method to estimate abundance. We analyzed data from line‐transect surveys of blue whales off the coast of Chile, where the population was hunted to low levels. Field protocols allowed deviation from planned track lines to collect identification photographs and tissue samples for genetic analyses, which resulted in an ad hoc sampling design with increased effort in areas of higher densities. Thus, we used spatial modeling methods to estimate abundance. Spatial models are increasingly being used to analyze data from surveys of marine, aquatic, and terrestrial species, but estimation of uncertainty from such models is often problematic. We developed a new, broadly applicable variance estimator that showed there were likely 303 whales (95% CI 176–625) in the study area. The survey did not span the whales' entire range, so this is a minimum estimate. We estimated current minimum abundance relative to pre‐exploitation abundance (i.e., status) with a population dynamics model that incorporated our minimum abundance estimate, likely population growth rates from a meta‐analysis of rates of increase in large baleen whales, and two alternative assumptions about historic catches. From this model, we estimated that the population was at a minimum of 9.5% (95% CI 4.9–18.0%) of pre‐exploitation levels in 1998 under one catch assumption and 7.2% (CI 3.7–13.7%) of pre‐exploitation levels under the other. Thus, although Chilean blue whales are probably still at a small fraction of pre‐exploitation abundance, even these minimum abundance estimates demonstrate that their status is better than that of Antarctic blue whales, which are still

Linkage mapping of the Phg-1 and Co-1 4 genes for resistance to angular leaf spot and anthracnose in the common bean cultivar AND 277 - Maria Celeste Gonçalves-Vidigal; Anelise S. Cruz; Alexandre Garcia; J. Kami; Pedro S. Vidigal Filho; Lorenna L. Sousa; P. McClean; P. Gepts; M. A. Pastor-Corrales (Theoretical and Applied Genetics, 2011)

Transcriptional Profiles of Roots of Different Soybean Genotypes Subjected to Drought Stress - Renata Stolf-Moreira; Eliana G. M. Lemos; Lúcia Carareto-Alves; Jackson Marcondes; Selma S. Pereira; Amanda A. P. Rolla; Rodrigo M. Pereira; Norman Neumaier; Eliseu Binneck; Ricardo V. Abdelnoor; Maria C. N. de Oliveira; Francismar C. Marcelino; et al. (Plant Molecular Biology Reporter, 2011)

The response of the human circulatory system to an acute 200-μT, 60-Hz magnetic field exposure - David A. McNamee; Michael Corbacio; Julie K. Weller; Samantha Brown; Robert Z. Stodilka; Frank S. Prato; Yves Bureau; Alex W. Thomas; Alexandre G. Legros (International Archives of Occupational and Environmental Health, 2011)

Distribution of oxidizable organic C fractions in soils under cacao agroforestry systems in Southern Bahia, Brazil - Patrícia A. B. Barreto; Emanuela F. Gama-Rodrigues; A. C. Gama-Rodrigues; Alexandre G. Fontes; José C. Polidoro; Maria Kellen S. Moço; Regina C. R. Machado; V. C. Baligar (Agroforestry Systems, 2011)

Expression Analysis of PAC1-R and PACAP Genes in Zebrafish Embryos - David Alexandre; Jessy Alonzeau; Brent R. Bill; Stephen C. Ekker; James A. Waschek (Journal of Molecular Neuroscience, 2011)

Deviations from predictions of the metabolic theory of ecology can be explained by violations of assumptions - Fernanda A. S. Cassemiro; José Alexandre Felizola Diniz-Filho (Ecology, 2010)
The metabolic theory of ecology (MTE) is based on models derived from the first principles of thermodynamics and biochemical kinetics. The MTE predicts that the relationship between temperature and species richness of ectotherms should show a specific slope. Testing the validity of this model, however, depends on whether empirical data do not violate assumptions and are obtained within contour conditions. When dealing with richness gradients, the MTE must be empirically tested only for ectothermic organisms at high organization levels and when their body size as well as abundance does not vary with temperature gradients. Here we evaluate whether the magnitude of the deviations in slope expected from the MTE to empirical data for New World amphibians is due to the violations of model assumptions and to lack of generality due to restricting contour conditions. We found that the MTE correctly predicted biodiversity patterns only at higher levels of organization and when assumptions of the basic model were not violated. Approximately 60% of the deviations from the MTE‐predicted slope across amphibian families were due to violations of the model assumptions. The hypothesis that richness patterns are a function of environmental temperature is too restrictive and does not take complex environmental and ecological processes into account. However, our results suggest that it may be possible to obtain multiple derivations of the MTE equation if idiosyncrasies in spatial and biological/ecological issues that are essential to understanding biodiversity patterns are considered.

Effect of sodium bicarbonate as a pharmaceutical formulation excipient on the interaction of fluvastatin with membrane phospholipids - Germain Larocque; Alexandre A. Arnold; Étienne Chartrand; Yves Mouget; Isabelle Marcotte (European Biophysics Journal, 2010)

Quercetin restores plasma nitrite and nitroso species levels in renovascular hypertension - Marcelo F. Montenegro; Evandro M. Neto-Neves; Carlos A. Dias-Junior; Carla S. Ceron; Michele M. Castro; Valeria A. Gomes; Alexandre Kanashiro; Jose E. Tanus-Santos (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Understanding the effects of isolation on seed and pollen flow, spatial genetic structure and effective population size of the dioecious tropical tree species Myracrodruon urundeuva - Ana P. S. C. Gaino; Alexandre M. Silva; Marcela A. Moraes; Patrícia F. Alves; Mario L. T. Moraes; Miguel L. M. Freitas; Alexandre M. Sebbenn (Conservation Genetics, 2010)

Vision in click beetles (Coleoptera: Elateridae): pigments and spectral correspondence between visual sensitivity and species bioluminescence emission - Abner B. Lall; Thomas W. Cronin; Alexandre A. Carvalho; John M. de Souza; Marcelo P. Barros; Cassius V. Stevani; Etelvino J. H. Bechara; Dora F. Ventura; Vadim R. Viviani; Avionne A. Hill (Journal of Comparative Physiology A, 2010)

Species-specific effects of polyploidisation and plant traits of Centaurea maculosa and Senecio inaequidens on rhizosphere microorganisms - Aurélie Thébault; Beat Frey; Edward A. D. Mitchell; Alexandre Buttler (Oecologia, 2010)

Quantifying Microbial Methane Oxidation Efficiencies in Two Experimental Landfill Biocovers Using Stable Isotopes - Alexandre R. Cabral; Marlon A. Capanema; Julia Gebert; Joao F. Moreira; Louis B. Jugnia (Water, Air, & Soil Pollution, 2010)

Population structure and possible migratory links of common minke whales, Balaenoptera acutorostrata, in the Southern Hemisphere - Luis A. Pastene; Jorge Acevedo; Mutsuo Goto; Alexandre N. Zerbini; Paola Acuña; Anelio Aguayo-Lobo (Conservation Genetics, 2010)

The cardiovascular response to an acute 1800-μT, 60-Hz magnetic field exposure in humans - David A. McNamee; Michael Corbacio; Julie K. Weller; Samantha Brown; Frank S. Prato; Alex W. Thomas; Alexandre G. Legros (International Archives of Occupational and Environmental Health, 2010)

Erratum to: Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

Local and remote tissue injury upon intestinal ischemia and reperfusion depends on the TLR/MyD88 signaling pathway - Tatiana Victoni; Fernando Rodrigues Coelho; Alexandre Learth Soares; Andressa de Freitas; Thomas Secher; Rodrigo Guabiraba; François Erard; Ricardo Martins de Oliveira-Filho; B. Boris Vargaftig; Gregoire Lauvaux; Mamdouh A. Kamal; Bernhard Ryffel; et al. (Medical Microbiology and Immunology, 2010)

A device to improve the Schleger and Turner method for sweating rate measurements - Alfredo Manuel Franco Pereira; Alexandre Alves; Paulo Infante; Evaldo A. L. Titto; Flávio Baccari; J. A. Afonso Almeida (International Journal of Biometeorology, 2010)

The transcription factor GATA-2 does not associate with angiographic coronary artery disease in the Ottawa Heart Genomics and Cleveland Clinic GeneBank Studies - Sonny Dandona; Li Chen; Meng Fan; Md Afaque Alam; Olivia Assogba; Melanie Belanger; Kathryn Williams; George A. Wells; W. H. Wilson Tang; Stephen G. Ellis; Stanley L. Hazen; Ruth McPherson; et al. (Human Genetics, 2010)

Climate history, human impacts and global body size of Carnivora (Mammalia: Eutheria) at multiple evolutionary scales - José Alexandre Felizola Diniz‐Filho; Miguel Ángel Rodríguez; Luis Mauricio Bini; Miguel Ángel Olalla‐Tarraga; Marcel Cardillo; João Carlos Nabout; Joaquín Hortal; Bradford A. Hawkins (Journal of Biogeography, 2009)
Aim One of the longest recognized patterns in macroecology, Bergmann’s rule, describes the tendency for homeothermic animals to have larger body sizes in cooler climates than their phylogenetic relatives in warmer climates. Here we provide an integrative process‐based explanation for Bergmann’s rule at the global scale for the mammal order Carnivora. Location Global. Methods Our database comprises the body sizes of 209 species of extant terrestrial Carnivora, which were analysed using phylogenetic autocorrelation and phylogenetic eigenvector regression. The interspecific variation in body size was partitioned into phylogenetic (P) and specific (S) components, and mean P‐ and S‐components across species were correlated with environmental variables and human occupation both globally and for regions glaciated or not during the last Ice Age. Results Three‐quarters of the variation in body size can be explained by phylogenetic relationships among species, and the geographical pattern of mean values of the P‐component is the opposite of the pattern predicted by Bergmann’s rule. Partial regression revealed that at least 43% of global variation in the mean phylogenetic component is explained by current environmental factors. In contrast, the mean S‐component of body size shows large positive deviations from ancestors across the Holarctic, and negative deviations in southern South America, the Sahara Desert, and tropical Asia. There is a moderately strong relationship between the human footprint and body size in glaciated regions, explaining 19% of the variance of the mean P‐component. The relationship with the human footprint and the P‐component is much weaker in the rest of the world, and there is no relationship between human footprint and S‐component in any region. Main conclusions Bergmannian clines are stronger at higher latitudes in the Northern Hemisphere because of the continuous alternation of glacial–interglacial cycles throughout the late Pliocene and Pleistocene, which generated increased species turnover, differential colonization and more intense adaptive processes soon after glaciated areas became exposed. Our analyses provide a unified explanation for an adaptive Bergmann’s rule within species and for an interspecific trend towards larger body sizes in assemblages resulting from historical changes in climate and contemporary human impacts.

Frequency of BCoV detection by a semi-nested PCR assay in faeces of calves from Brazilian cattle herds - Danilo T. Stipp; Aline F. Barry; Alice F. Alfieri; Elisabete Takiuchi; Alexandre M. Amude; Amauri A. Alfieri (Tropical Animal Health and Production, 2009)

The diversity of juvenile salmonids does not affect their competitive impact on a native galaxiid - Kyle A. Young; Jessica Stephenson; Alexandre Terreau; Anne-Flore Thailly; Gonzalo Gajardo; Carlos Garcia de Leaniz (Biological Invasions, 2009)

Cloud condensation nuclei from biomass burning during the Amazonian dry-to-wet transition season - Jorge Alberto Martins; Fábio Luiz T. Gonçalves; Carlos A. Morales; Gilberto F. Fisch; Francisco Geraldo M. Pinheiro; João Bosco V. Leal Júnior; Carlos J. Oliveira; Emerson M. Silva; José Carlos P. Oliveira; Alexandre A. Costa; Maria Assunção F. Silva Dias (Meteorology and Atmospheric Physics, 2009)

Travelling and hunting in a changing Arctic: assessing Inuit vulnerability to sea ice change in Igloolik, Nunavut - Gita J. Laidler; James D. Ford; William A. Gough; Theo Ikummaq; Alexandre S. Gagnon; Slawomir Kowal; Kevin Qrunnut; Celina Irngaut (Climatic Change, 2009)

Distribution of common dolphins (Delphinus spp.) in the western Atlantic Ocean: a critical re-examination - Thomas A. Jefferson; Dagmar Fertl; Jaime Bolaños-Jiménez; Alexandre N. Zerbini (Marine Biology, 2009)

Analyses of associations with asthma in four asthma population samples from Canada and Australia - Denise Daley; Mathieu Lemire; Loubna Akhabir; Moira Chan-Yeung; Jian Qing He; Treena McDonald; Andrew Sandford; Dorota Stefanowicz; Ben Tripp; David Zamar; Yohan Bosse; Vincent Ferretti; et al. (Human Genetics, 2009)

Intratracheal Versus Intravenous Liposomal Delivery of siRNA, Antisense Oligonucleotides and Anticancer Drug - Olga B. Garbuzenko; Maha Saad; Seema Betigeri; Min Zhang; Alexandre A. Vetcher; Viatcheslav A. Soldatenkov; David C. Reimer; Vitaly P. Pozharov; Tamara Minko (Pharmaceutical Research, 2009)

Growth and carcass traits of Creole goats under different pre-weaning, fattening and slaughter conditions - L. Liméa; J. Gobardham; G. Gravillon; A. Nepos; G. Alexandre (Tropical Animal Health and Production, 2009)

Spatial species‐richness gradients across scales: a meta‐analysis - Richard Field; Bradford A. Hawkins; Howard V. Cornell; David J. Currie; J. Alexandre F. Diniz‐Filho; Jean‐François Guégan; Dawn M. Kaufman; Jeremy T. Kerr; Gary G. Mittelbach; Thierry Oberdorff; Eileen M. O’Brien; John R. G. Turner (Journal of Biogeography, 2009)
Aim We surveyed the empirical literature to determine how well six diversity hypotheses account for spatial patterns in species richness across varying scales of grain and extent. Location Worldwide. Methods We identified 393 analyses (‘cases’) in 297 publications meeting our criteria. These criteria included the requirement that more than one diversity hypothesis was tested for its relationship with species richness. We grouped variables representing the hypotheses into the following ‘correlate types’: climate/productivity, environmental heterogeneity, edaphics/nutrients, area, biotic interactions and dispersal/history (colonization limitation or other historical or evolutionary effect). For each case we determined the ‘primary’ variable: the one most strongly correlated with taxon richness. We defined ‘primacy’ as the proportion of cases in which each correlate type was represented by the primary variable, relative to the number of times it was studied. We tested for differences in both primacy and mean coefficient of determination of the primary variable between the hypotheses and between categories of five grouping variables: grain, extent, taxon (animal vs. plant), habitat medium (land vs. water) and insularity (insular vs. connected). Results Climate/productivity had the highest overall primacy, and environmental heterogeneity and dispersal/history had the lowest. Primacy of climate/productivity was much higher in large‐grain and large‐extent studies than at smaller scales. It was also higher on land than in water, and much higher in connected systems than in insular ones. For other hypotheses, differences were less pronounced. Throughout, studies on plants and animals showed similar patterns. Coefficients of determination of the primary variables differed little between hypotheses and across the grouping variables, the strongest effects being low means in the smallest grain class and for edaphics/nutrients variables, and a higher mean for water than for land in connected systems but vice versa in insular systems. We highlight areas of data deficiency. Main conclusions Our results support the notion that climate and productivity play an important role in determining species richness at large scales, particularly for non‐insular, terrestrial habitats. At smaller extents and grain sizes, the primacy of the different types of correlates appears to differ little from null expectation. In our analysis, dispersal/history is rarely the best correlate of species richness, but this may reflect the difficulty of incorporating historical factors into regression models, and the collinearity between past and current climates. Our findings are consistent with the view that climate determines the capacity for species richness. However, its influence is less evident at smaller spatial scales, probably because (1) studies small in extent tend to sample little climatic range, and (2) at large grains some other influences on richness tend to vary mainly within the sampling unit.

Purification and molecular cloning of a new galactose-specific lectin from Bauhinia variegata seeds - Luciano S. Pinto; Celso S. Nagano; Taianá M. Oliveira; Tales R. Moura; Alexandre H. Sampaio; Henri Debray; Vicente P. Pinto; Odir A. Dellagostin; Benildo S. Cavada (Journal of Biosciences, 2008)

Philosophical justifications for the extirpation of non-indigenous species: the case of the grasshopper Schistocerca nitens (Orthoptera) on the Island of Nihoa, Hawaii - Jeffrey A. Lockwood; Alexandre V. Latchininsky (Journal of Insect Conservation, 2008)

Senescence rates are determined by ranking on the fast–slow life‐history continuum - Owen R. Jones; Jean‐Michel Gaillard; Shripad Tuljapurkar; Jussi S. Alho; Kenneth B. Armitage; Peter H. Becker; Pierre Bize; Jon Brommer; Anne Charmantier; Marie Charpentier; Tim Clutton‐Brock; F. Stephen Dobson; et al. (Ecology Letters, 2008)
Comparative analyses of survival senescence by using life tables have identified generalizations including the observation that mammals senesce faster than similar‐sized birds. These generalizations have been challenged because of limitations of life‐table approaches and the growing appreciation that senescence is more than an increasing probability of death. Without using life tables, we examine senescence rates in annual individual fitness using 20 individual‐based data sets of terrestrial vertebrates with contrasting life histories and body size. We find that senescence is widespread in the wild and equally likely to occur in survival and reproduction. Additionally, mammals senesce faster than birds because they have a faster life history for a given body size. By allowing us to disentangle the effects of two major fitness components our methods allow an assessment of the robustness of the prevalent life‐table approach. Focusing on one aspect of life history – survival or recruitment – can provide reliable information on overall senescence.

Molecular mapping of two loci that confer resistance to Asian rust in soybean - Danielle C. G. Silva; Naoki Yamanaka; Rodrigo L. Brogin; Carlos A. A. Arias; Alexandre L. Nepomuceno; Antônio O. Di Mauro; Selma S. Pereira; Livia M. Nogueira; André L. L. Passianotto; Ricardo V. Abdelnoor (Theoretical and Applied Genetics, 2008)

The effects of sport fishing growth on behavior of commercial fishermen in Balbina reservoir, Amazon, Brazil - Carlos E. C. Freitas; Alexandre A. F. Rivas; Fabíola A. Nascimento; Flávia K. Siqueira-Souza; Ivanildo L. A. Santos (Environment, Development and Sustainability, 2008)

Growth and lipid composition of Atlantic cod (Gadus morhua) larvae in response to differently enriched Artemia franciscana - Alexandre Sachsida Garcia; Christopher C. Parrish; Joseph A. Brown (Fish Physiology and Biochemistry, 2008)

Cytoenzymatic investigation of intracellular digestion in the symbiont-bearing hydrothermal bivalve Bathymodiolus azoricus - Enikö Kádár; Sean A. Davis; Alexandre Lobo-da-Cunha (Marine Biology, 2008)

The cost‐effectiveness of biodiversity surveys in tropical forests - Toby A. Gardner; Jos Barlow; Ivanei S. Araujo; Teresa Cristina Ávila‐Pires; Alexandre B. Bonaldo; Joana E. Costa; Maria Cristina Esposito; Leandro V. Ferreira; Joseph Hawes; Malva I. M. Hernandez; Marinus S. Hoogmoed; Rafael N. Leite; et al. (Ecology Letters, 2008)
The identification of high‐performance indicator taxa that combine practical feasibility and ecological value requires an understanding of the costs and benefits of surveying different taxa. We present a generic and novel framework for identifying such taxa, and illustrate our approach using a large‐scale assessment of 14 different higher taxa across three forest types in the Brazilian Amazon, estimating both the standardized survey cost and the ecological and biodiversity indicator value for each taxon. Survey costs varied by three orders of magnitude, and dung beetles and birds were identified as especially suitable for evaluating and monitoring the ecological consequences of habitat change in our study region. However, an exclusive focus on such taxa occurs at the expense of understanding patterns of diversity in other groups. To improve the cost‐effectiveness of biodiversity research we encourage a combination of clearer research goals and the use of an objective evidence‐based approach to selecting study taxa.

Partitioning phylogenetic and adaptive components of the geographical body‐size pattern of New World birds - Lizabeth Ramirez; José Alexandre Felizola Diniz‐Filho; Bradford A. Hawkins (Global Ecology and Biogeography, 2008)
Aim To evaluate seasonal body‐size patterns for New World birds in geographical space, to develop environmental models to explain the gradients, and to estimate phylogenetic and adaptive contributions. Location The Western Hemisphere. Methods We used range maps to generate gridded geometric mean body masses. Summer and winter patterns were distinguished based on breeding and non‐breeding ranges. We first generated the geographical gradients, followed by phylogenetic eigenvector regression to generate body sizes predicted by the birds’ positions in a phylogenetic tree, which were used to generate the expected phylogenetic gradient. Subtracting the expected pattern from the observed pattern isolated the adaptive component. Ordinary least squares multiple‐regression models examined factors influencing the phylogenetic, adaptive and combined components of the seasonal body‐size patterns, and non‐spatial and spatial models were compared. Results Birds are larger in the temperate zones than in the tropics. The gradient is quantitatively stronger in winter than in summer. Regression models explained 66.6% of the variance in summer mass and 45.9% of the variance in winter mass. In summer, phylogenetic and adaptive responses of birds contribute equally to the gradient. In winter, the gradient in North America is much stronger than that expected by taxonomic turnover, and responses of species independent of their family membership drive the overall pattern. Main conclusions We confirm Bergmann's rule in New World birds and conclude that winter temperatures ultimately drive the pattern, exerting selection pressures on birds that overwhelm patterns expected by phylogenetic inertia at the family level. However, in summer, the movement of migratory species into the temperate zone weakens the gradient and generates a pattern more congruent with that expected from the taxonomic composition of the fauna. The analytical method we develop here represents a useful tool for partitioning the phylogenetic and non‐phylogenetic components of spatially explicit macroecological data.

Laboratory Bioassays of Vegetable Oils as Kairomonal Phagostimulants for Grasshoppers (Orthoptera: Acrididae) - Alexandre V. Latchininsky; Scott P. Schell; Jeffrey A. Lockwood (Journal of Chemical Ecology, 2007)

Southern hemisphere cyclones and anticyclones: recent trends and links with decadal variability in the Pacific Ocean - Alexandre Bernardes Pezza; Ian Simmonds; James A. Renwick (International Journal of Climatology, 2007)
The aim of this paper is to study the association between the extratropical Southern Hemisphere and the decadal variability in the Pacific Ocean (PO). We discuss a pattern of coherent large‐scale anomalies and trends in cyclone and anticyclone behaviour in light of the climate variability in the PO over the ERA40 reanalysis period (1957–2002). The two representative PO indices are the Pacific Decadal and Interdecadal Oscillations (PDO and IPO), and here the PDO is chosen owing to it being less associated with the southern oscillation index (SOI). Composites of the indicators of the density and intensity of cyclones/anticyclones given by an automatic tracking scheme were calculated for the years when the PDOI was more than one standard deviation above or below its mean. Although the ERA40 is not free from noise and assimilation changes, the results show a large‐scale feature, which seems to be robust and agrees with earlier studies using different data sets. The sea‐level pressure shows a strong annular structure related to the PDO, which is not seen for the SOI, with lower pressure around Antarctica during the positive phase and vice versa. More intense (and fewer) cyclones and anticyclones were observed during the positive PDO. This is less consistent for the SOI, particularly during the summer when a different PDO/SOI pattern arises at high latitudes. The trends project a pattern coincident with the positive PDO phase and seem to be linked with the main climate shift in the late seventies. Trends observed over the Tasman Sea are consistent with declining winter rainfall over southeastern Australia. Most patterns are statistically significant and seem robust, but random changes in ENSO may play a part, to a certain degree, in modulating the results, and a physical mechanism of causality has not been demonstrated. Although global warming and related changes in the Southern Annular Mode (SAM) may also help explain the observed behaviour, the large‐scale response presented here provides a new insight and would be of considerable interest for further modelling studies. Copyright © 2007 Royal Meteorological Society

Radiation and speciation of pelagic organisms during periods of global warming: the case of the common minke whale, Balaenoptera acutorostrata - LUIS A. PASTENE; MUTSUO GOTO; NAOHISA KANDA; ALEXANDRE N. ZERBINI; DAN KEREM; KAZUO WATANABE; YOSHITAKA BESSHO; MASAMI HASEGAWA; RASMUS NIELSEN; FINN LARSEN; PER J. PALSBØLL (Molecular Ecology, 2007)
How do populations of highly mobile species inhabiting open environments become reproductively isolated and evolve into new species? We test the hypothesis that elevated ocean‐surface temperatures can facilitate allopatry among pelagic populations and thus promote speciation. Oceanographic modelling has shown that increasing surface temperatures cause localization and reduction of upwelling, leading to fragmentation of feeding areas critical to pelagic species. We test our hypothesis by genetic analyses of populations of two closely related baleen whales, the Antarctic minke whale ( Balaenoptera bonaerensis ) and common minke whale ( Balaenoptera acutorostrata ) whose current distributions and migration patterns extent are largely determined by areas of consistent upwelling with high primary production. Phylogeographic and population genetic analyses of mitochondrial DNA control‐region nucleotide sequences collected from 467 whales sampled in four different ocean basins were employed to infer the evolutionary relationship among populations of B. acutorostrata by rooting an intraspecific phylogeny with a population of B. bonaerensis . Our findings suggest that the two species diverged in the Southern Hemisphere less than 5 million years ago (Ma). This estimate places the speciation event during a period of extended global warming in the Pliocene. We propose that elevated ocean temperatures in the period facilitated allopatric speciation by disrupting the continuous belt of upwelling maintained by the Antarctic Circumpolar Current. Our analyses revealed that the current populations of B. acutorostrata likely diverged after the Pliocene some 1.5 Ma when global temperatures had decreased and presumably coinciding with the re‐establishment of the polar–equatorial temperature gradient that ultimately drives upwelling. In most population samples, we detected genetic signatures of exponential population expansions, consistent with the notion of increasing carrying capacity after the Pliocene. Our hypothesis that prolonged periods of global warming facilitate speciation in pelagic marine species that depend on upwelling should be tested by comparative analyses in other pelagic species.

Vatairea macrocarpa (Leguminosae) lectin activates cultured macrophages to release chemotactic mediators - Nylane M. N. Alencar; Ana M. S. Assreuy; Alexandre Havt; Raquel G. Benevides; Tales R. de Moura; Romoaldo B. de Sousa; Ronaldo A. Ribeiro; Fernando Q. Cunha; Benildo S. Cavada (Naunyn-Schmiedeberg's Archives of Pharmacology, 2007)

Sex Attractant Pheromone from the Rice Stalk Stink Bug, Tibraca limbativentris Stal - Miguel Borges; Michael Birkett; Jeffrey R. Aldrich; James E. Oliver; Mitsuo Chiba; Yasuhiro Murata; Raul A. Laumann; José Alexandre Barrigossi; John A. Pickett; Maria C. B. Moraes (Journal of Chemical Ecology, 2006)

Limnological conditions in Subglacial Lake Vostok, Antarctica - Brent C. Christner; George Royston-Bishop; Christine M. Foreman; Brianna R. Arnold; Martyn Tranter; Kathleen A. Welch; W. Berry Lyons; Alexandre I. Tsapin; Michael Studinger; John C. Priscu (Limnology and Oceanography, 2006)
Subglacial Lake Vostok is located ~4 km beneath the surface of the East Antarctic Ice Sheet and has been isolated from the atmosphere for ≫15 million yr. Concerns for environmental protection have prevented direct sampling of the lake water thus far. However, an ice core has been retrieved from above the lake in which the bottom ,85 m represents lake water that has accreted (i.e., frozen) to the bottom of the ice sheet. We measured selected constituents within the accretion ice core to predict geomicrobiological conditions within the surface waters of the lake. Bacterial density is two‐ to sevenfold higher in accretion ice than the overlying glacial ice, implying that Lake Vostok is a source of bacterial carbon beneath the ice sheet. Phylogenetic analysis of amplified small subunit ribosomal ribonucleic acid (rRNA) gene sequences in accretion ice formed over a deep portion of the lake revealed phylotypes that classify within the β‐, γ‐, and Δ‐Proteobacteria. Cellular, major ion, and dissolved organic carbon levels all decreased with depth in the accretion ice (depth is a proxy for increasing distance from the shoreline), implying a greater potential for biological activity in the shallow shoreline waters of the lake. Although the exact nature of the biology within Lake Vostok awaits direct sampling of the lake water, our data from the accretion ice support the working hypothesis that a sustained microbial ecosystem is present in this subglacial lake environment, despite high pressure, constant cold, low nutrient input, potentially high oxygen concentrations, and an absence of sunlight.

Beyond Rapoport's rule: evaluating range size patterns of New World birds in a two-dimensional framework - Bradford A. Hawkins; José Alexandre Felizola Diniz-Filho (Global Ecology and Biogeography, 2006)

Beyond Rapoport's rule: evaluating range size patterns of New World birds in a two‐dimensional framework - Bradford A. Hawkins; José Alexandre Felizola Diniz‐Filho (Global Ecology and Biogeography, 2006)
Aim To evaluate Rapoport's rule for New World birds in two‐dimensional geographical space. We specifically test for a topography × climate interaction that predicts little difference in range sizes between lowlands and mountains in cold climates, whereas in the tropics, montane species have narrow ranges and lowland species have broad ranges. Location The western hemisphere. Methods We used digitized range maps of breeding birds to generate mean range sizes in grids of 27.5 × 27.5 km and 110 × 110 km across North and South America. We examined the geographical pattern with respect to range in elevation, mean temperature in the coldest month, their interaction, biome size and continental width, using model II analysis of variance, multiple regression and simple correlation. Results In northern latitudes species have broad ranges in both mountainous and flat areas. However, range sizes in the mountains and lowlands diverge southwards, with the most extreme differences in the tropics. Further, there are minimal differences in range sizes across latitudes in lowlands. The smallest mean ranges occur in the tropical Andes. Mean range sizes in north‐central Canada, Central America and Argentina/Chile are also small, reflecting the narrowing of the continents in these areas. The best regression model explained 51% of the variation in mean range size. Main conclusions The two‐dimensional range size pattern indicates that neither winter temperature nor annual variability in temperature strongly influences the distribution of range sizes directly; rather, climate influences bird range sizes indirectly via effects on habitat size. Also, macroclimate interacts with topographic relief across latitudes, generating sharp mesoscale habitat gradients in tropical mountains but not in high latitude mountains or in lowlands at any latitude. Birds respond to these habitat gradients, resulting in ‘latitudinal’ range size gradients in topographically complex landscapes but not in simple landscapes.

Defense Proteins from Vigna Unguiculata Seed Exudates: Characterization and Inhibitory Activity Against Fusarium Oxysporum - Tatiana L. Rose; Alexandre da Silva Conceição; Jose Xavier-Filho; Lev A. Okorokov; Kátia V. S. Fernandes; Francis Marty; Danièle Marty-Mazars; André O. Carvalho; Valdirene M. Gomes (Plant and Soil, 2006)

Ticks (Acari: Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Matias P. J. Szabó; Marcelo B. Labruna; Karina C. Castagnolli; Marcos V. Garcia; Adriano Pinter; Viviane A. Veronez; Geórgia M. Magalhães; Márcio B. Castro; Alexandre Vogliotti (Experimental and Applied Acarology, 2006)

MTHFR (C677T and A1298C) Polymorphisms and Risk of Sporadic Distal Colorectal Adenoma in the UK Flexible Sigmoidoscopy Screening Trial (United Kingdom) - Panagiota N. Mitrou; Mark A. Watson; Alexandre S. Loktionov; Christopher Cardwell; Marc J. Gunter; Wendy S. Atkin; Christopher P. Macklin; Tom Cecil; Timothy D. Bishop; John Primrose; Sheila A. Bingham (Cancer Causes & Control, 2006)

Post‐Eocene climate change, niche conservatism, and the latitudinal diversity gradient of New World birds - Bradford A. Hawkins; José Alexandre Felizola Diniz‐Filho; Carlos A. Jaramillo; Stephen A. Soeller (Journal of Biogeography, 2006)
Aim The aim of this study was to test a variant of the evolutionary time hypothesis for the bird latitudinal diversity gradient derived from the effects of niche conservatism in the face of global climate change over evolutionary time. Location The Western Hemisphere. Methods We used digitized range maps of breeding birds to estimate the species richness at two grain sizes, 756 and 12,100 km 2 . We then used molecular phylogenies resolved to family to quantify the root distance (RD) of each species as a measure of its level of evolutionary development. Birds were classified as ‘basal’ or ‘derived’ based on the RD of their family, and richness patterns were contrasted for the most basal and most derived 30% of species. We also generated temperature estimates for the Palaeogene across the Western Hemisphere to examine how spatial covariation between past and present climates might make it difficult to distinguish between ecological and evolutionary hypotheses for the current richness gradient. Results The warm, wet tropics support many species from basal bird clades, whereas the northern temperate zone and cool or dry tropics are dominated by species from more recent, evolutionarily derived clades. Furthermore, crucial to evaluating how niche conservatism among birds may drive the hemispherical richness gradient, the spatial structure of the richness gradient for basal groups is statistically indistinguishable from the overall gradient, whereas the richness gradient for derived groups is much shallower than the overall gradient. Finally, modern temperatures and the pattern of climate cooling since the Eocene are indistinguishable as predictors of bird species richness. Main conclusions Differences in the richness gradients of basal vs. derived clades suggest that the hemispherical gradient has been strongly influenced by the differential extirpation of species in older, warm‐adapted clades from parts of the world that have become cooler in the present. We propose that niche conservatism and global‐scale climate change over evolutionary time provide a parsimonious explanation for the contemporary bird latitudinal diversity gradient in the New World, although dispersal limitation of some highly derived clades probably plays a secondary role.

Identification of QTLs associated with citrus resistance toPhytophthora gummosis - Amauri Siviero; Mariângela Cristofani; Edson L. Furtado; Antonio A. F. Garcia; Alexandre S. G. Coelho; Marcos A. Machado (Journal of Applied Genetics, 2006)

Maturational differences in superficial and deep zone articular chondrocytes - Chisa Hidaka; Christina Cheng; Deborah Alexandre; Madhu Bhargava; Peter A. Torzilli (Cell and Tissue Research, 2006)

Genesis of itabirite-hosted Au–Pd–Pt-bearing hematite-(quartz) veins, Quadrilátero Ferrífero, Minas Gerais, Brazil: constraints from fluid inclusion infrared microthermometry, bulk crush-leach analysis and U–Pb systematics - Volker Lüders; Rolf L. Romer; Alexandre R. Cabral; Christian Schmidt; David A. Banks; Jens Schneider (Mineralium Deposita, 2005)

Evidence for a novel glaucoma locus at chromosome 3p21-22 - Paul N. Baird; Simon J. Foote; David A. Mackey; Jamie Craig; Terence P. Speed; Alexandre Bureau (Human Genetics, 2005)

Water links the historical and contemporary components of the Australian bird diversity gradient - Bradford A. Hawkins; José Alexandre Felizola Diniz‐Filho; Stephen A. Soeller (Journal of Biogeography, 2005)
Aim To document the geographical structure of the historical signal in the continental species richness gradient of birds and evaluate the influences of contemporary and historical climatic conditions on the generation and maintenance of the richness pattern. Location Australia. Methods We used range maps of breeding birds to generate the spatial pattern of species richness at four grain sizes, and two molecular phylogenies to measure the level of evolutionary development of avifaunas at each grain size. We then used simple correlation and path analysis to generate a statistical model of species richness using environmental predictor variables and compared the spatial patterns of richness and mean evolutionary development to identify possible environmental links between richness and net diversification rates across the continent. Results The contemporary richness pattern is well explained statistically by actual evapotranspiration (a measure of water–energy balance), operating both directly and indirectly through plant production, and this is robust to the spatial resolution of the analysis. Further, species richness and the mean level of evolutionary development of faunas show a strong spatial correspondence, such that dry areas support both fewer species and species from more highly derived families, whereas wet areas support more species of both basal and derived families. The evolutionary pattern conforms to a similar pattern known for plants and is probably explained by the increase in aridity in western and central Australia arising in the Miocene. Main conclusion The contemporary bird richness gradient contains a historical signal and reflects the effects of both current levels of water availability as well as changes in rainfall patterns extending over evolutionary time. The historical signal persists even in the absence of obvious hard barriers to dispersal.

Climate Change Scenarios for the Hudson Bay Region: An Intermodel Comparison - Alexandre S. Gagnon; William A. Gough (Climatic Change, 2005)

Preweaning Productivity of Suckling Goats and Sheep in Guadeloupe (FWI) under Intensive Reproductive Rate and Grazing Management - E. Ortega-Jimenez; G. Alexandre; R. Arquet; M. Mahieu; A. Xandé (Tropical Animal Health and Production, 2005)

An atypical form of erythrokeratodermia variabilis maps to chromosome 7q22 - Thomas G. Saba; Alexandre Montpetit; Andrei Verner; Pierre Rioux; Thomas J. Hudson; Rgen Drouin; Christian A. Drouin (Human Genetics, 2005)

Macroecological explanations for differences in species richness gradients: a canonical analysis of South American birds - Luis Mauricio Bini; José Alexandre Felizola Diniz‐Filho; Bradford A. Hawkins (Journal of Biogeography, 2004)
Aim To evaluate how spatial variation of species richness in different bird orders responds to environmental gradients and determine which order level trait best predicts these relationships. Location South America. Methods A canonical correlation analysis was performed between the species richness in each of 17 bird orders and eight environmental variables in 374, 220 × 220 km cells. Loadings associated with the first two canonical variables were regressed against six order‐level predictors, including diversification level (number of species in each order), body size, median geographical range size and characteristics included in the model to control Type I error rates (the phylogenetic relationship among orders and levels of local‐scale spatial autocorrelation). Results Richness patterns of 14 bird orders were highly correlated with the first canonical axis, indicating that most orders respond similarly to energy‐water gradients (primarily actual evapotranspiration, minimum temperature and potential evapotranspiration). In contrast, species richness within Trochiliformes, Apodiformes and Galliformes were also correlated with the second canonical variable, representing measures of mesoscale climatic variation (range in elevation within cells, minimum temperature, and the interaction term between them) and landcover (habitat diversity). We also found that total diversification within orders was the best predictor of the loadings associated with the first canonical axis, whereas body size of each order best predicted loadings on the second axis. Conclusion Our results broadly support climatic‐related hypotheses as explanations for spatial variation in species richness of different orders. However, both historical (order‐specific variation in speciation rates) and ecological (dispersal of species that evolved by independent processes into areas amenable to birds) processes can explain the relationship between order level traits, such as body size and diversification level, and magnitude of response to current environment, furnishing then guidelines for a further and deeper understanding of broad‐scale diversity gradients.

A test of multiple hypotheses for the species richness gradient of South American owls - José Alexandre Felizola Diniz-Filho; Thiago F. L. V. B. Rangel; Bradford A. Hawkins (Oecologia, 2004)

High rates of net ecosystem carbon assimilation by Brachiara pasture in the Brazilian Cerrado - Alexandre J.B. Santos; Carlos A. Quesada; Gabriela T. Da Silva; Jair F. Maia; Heloisa S. Miranda; Antonio Carlos Miranda; Jon Lloyd (Global Change Biology, 2004)
To investigate the consequences of land use on carbon and energy exchanges between the ecosystem and atmosphere, we measured CO 2 and water vapour fluxes over an introduced Brachiara brizantha pasture located in the Cerrado region of Central Brazil. Measurements using eddy covariance technique were carried out in field campaigns during the wet and dry seasons. Midday CO 2 net ecosystem exchange rates during the wet season were −40 μmol m −2 s −1 , which is more than twice the rate found in the dry season (−15 μmol m −2 s −1 ). This was observed despite similar magnitudes of irradiance, air and soil temperatures. During the wet season, inferred rates of canopy photosynthesis did not show any tendency to saturate at high solar radiation levels, with rates of around 50 μmol m −2 s −1 being observed at the maximum incoming photon flux densities of 2200 μmol m −2 s −1 . This contrasted strongly to the dry period when light saturation occurred with 1500 μmol m −2 s −1 and with maximum canopy photosynthetic rates of only 20 μmol m −2 s −1 . Both canopy photosynthetic rates and night‐time ecosystem CO 2 efflux rates were much greater than has been observed for cerrado native vegetation in both the wet and dry seasons. Indeed, observed CO 2 exchange rates were also much greater than has previously been reported for C 4 pastures in the tropics. The high rates in the wet season may have been attributable, at least in part, to the pasture not being grazed. Higher than expected net rates of carbon acquisition during the dry season may also have been attributable to some early rain events. Nevertheless, the present study demonstrates that well‐managed, productive tropical pastures can attain ecosystem gas exchange rates equivalent to fertilized C 4 crops growing in the temperate zone.

Reproduction and metabolism at − 10°C of bacteria isolated from Siberian permafrost - Corien Bakermans; Alexandre I. Tsapin; Virginia Souza‐Egipsy; David A. Gilichinsky; Kenneth H. Nealson (Environmental Microbiology, 2003)
Summary We report the isolation and properties of several species of bacteria from Siberian permafrost. Half of the isolates were spore‐forming bacteria unable to grow or metabolize at subzero temperatures. Other Gram‐positive isolates metabolized, but never exhibited any growth at − 10°C. One Gram‐negative isolate metabolized and grew at − 10°C, with a measured doubling time of 39 days. Metabolic studies of several isolates suggested that as temperature decreased below + 4°C, the partitioning of energy changes with much more energy being used for cell maintenance as the temperature decreases. In addition, cells grown at − 10°C exhibited major morphological changes at the ultrastructural level.

Spatial autocorrelation and red herrings in geographical ecology - José Alexandre Felizola Diniz‐Filho; Luis Mauricio Bini; Bradford A. Hawkins (Global Ecology and Biogeography, 2003)
Aim Spatial autocorrelation in ecological data can inflate Type I errors in statistical analyses. There has also been a recent claim that spatial autocorrelation generates ‘red herrings’, such that virtually all past analyses are flawed. We consider the origins of this phenomenon, the implications of spatial autocorrelation for macro‐scale patterns of species diversity and set out a clarification of the statistical problems generated by its presence. Location To illustrate the issues involved, we analyse the species richness of the birds of western/central Europe, north Africa and the Middle East. Methods Spatial correlograms for richness and five environmental variables were generated using Moran's I coefficients. Multiple regression, using both ordinary least‐squares (OLS) and generalized least squares (GLS) assuming a spatial structure in the residuals, were used to identify the strongest predictors of richness. Autocorrelation analyses of the residuals obtained after stepwise OLS regression were undertaken, and the ranks of variables in the full OLS and GLS models were compared. Results Bird richness is characterized by a quadratic north–south gradient. Spatial correlograms usually had positive autocorrelation up to c . 1600 km. Including the environmental variables successively in the OLS model reduced spatial autocorrelation in the residuals to non‐detectable levels, indicating that the variables explained all spatial structure in the data. In principle, if residuals are not autocorrelated then OLS is a special case of GLS. However, our comparison between OLS and GLS models including all environmental variables revealed that GLS de‐emphasized predictors with strong autocorrelation and long‐distance clinal structures, giving more importance to variables acting at smaller geographical scales. Conclusion Although spatial autocorrelation should always be investigated, it does not necessarily generate bias. Rather, it can be a useful tool to investigate mechanisms operating on richness at different spatial scales. Claims that analyses that do not take into account spatial autocorrelation are flawed are without foundation.

The mid‐domain effect cannot explain the diversity gradient of Nearctic birds - Bradford A. Hawkins; José Alexandre Felizola Diniz‐Filho (Global Ecology and Biogeography, 2002)
A recent explanation for diversity gradients proposes a ‘null model’ based on how species ranges are constrained by the geometry of bounded domains. We conduct a test of this hypothesis by comparing patterns predicted by two two‐dimensional geometric models against observed diversity patterns for terrestrially feeding Nearctic birds. Consistent with previous tests in two‐dimensional space, we find empirical support for the hypothesis to be very weak. We also point out a fundamental conceptual flaw in the hypothesis with respect to the key assumption that ranges can exist independently of the environment in which they are embedded that undermines its theoretical basis as well. We conclude that the mid‐domain effect has little empirical support and no theoretical support for its existence, and recommend that it be eliminated as a potential explanation for diversity gradients.

Genotypic and Phenotypic Evidence of Different Drug-Resistance Mutation Patterns between B and Non-B Subtype Isolates of Human Immunodeficiency Virus Type 1 found in Brazilian Patients Failing HAART - Elena Caride; Kurt Hertogs; Brendan Larder; Pascale Dehertogh; Rodrigo Brindeiro; Elizabeth Machado; Carlos A.M. De Sá; Walter A. Eyer-Silva; Fernando Samuel Sion; Luiz F.C. Passioni; Jaqueline A. Menezes; Alexandre R. Calazans; et al. (Virus Genes, 2001)

Platelet-Activating Factor Modulates a Secreted Phosphatase Activity of the Trypanosomatid Parasite Herpetomonas muscarum muscarum - Patricia M.L. Dutra; Felipe A. Dias; Claudia O. Rodrigues; Alexandre Romeiro; Marcia Attias; Wanderley De Souza; Angela H.C.S. Lopes; José Roberto Meyer-Fernandes (Current Microbiology, 2001)

UN ECE ICP Materials: Dose-Response Functions on Dry and Wet Acid Deposition Effects After 8 Years of Exposure - Johan Tidblad; Vladimir Kucera; Alexandre A. Mikhailov; Jan Henriksen; Katerina Kreislova; Tim Yates; Bruno Stöckle; Manfred Schreiner (Water, Air, & Soil Pollution, 2001)

Raised atmospheric CO 2 levels and increased N deposition cause shifts in plant species composition and production in Sphagnum bogs - Frank Berendse; Nico Van Breemen; HÅkan Rydin; Alexandre Buttler; Monique Heijmans; Marcel R. Hoosbeek; John A. Lee; Edward Mitchell; Timo Saarinen; Harri Vasander; Bo Wallén (Global Change Biology, 2001)
Part of the missing sink in the global CO 2 budget has been attributed to the positive effects of CO 2 fertilization and N deposition on carbon sequestration in Northern Hemisphere terrestrial ecosystems. The genus Sphagnum is one of the most important groups of plant species sequestrating carbon in temperate and northern bog ecosystems, because of the low decomposability of the dead material it produces. The effects of raised CO 2 and increased atmospheric N deposition on growth of Sphagnum and other plants were studied in bogs at four sites across Western Europe. Contrary to expectations, elevated CO 2 did not significantly affect Sphagnum biomass growth. Increased N deposition reduced Sphagnum mass growth, because it increased the cover of vascular plants and the tall moss Polytrichum strictum . Such changes in plant species composition may decrease carbon sequestration in Sphagnum ‐dominated bog ecosystems.

Tumor necrosis factor-α promoter polymorphism TNF2 is associated with a stronger delayed-type hypersensivity reaction in the skin of borderline tuberculoid leprosy patients - Milton O. Moraes; Nádia C. Duppre; Philip N. Suffys; Adalberto R. Santos; Alexandre S. Almeida; José A. C. Nery; Elizabeth P. Sampaio; Euzenir N. Sarno (Immunogenetics, 2001)

Amazonian Tree Mortality during the 1997 El Niño Drought - G. Bruce Williamson; William F. Laurance; Alexandre A. Oliveira; Patricia Delamônica; Claude Gascon; Thomas E. Lovejoy; Luciano Pohl (Conservation Biology, 2000)
In 1997, the Amazon Basin experienced an exceptionally severe El Niño drought. We assessed effects of this rare event on mortality rates of trees in intact rain forest based on data from permanent plots. Long‐term (5‐ to 13‐year) mortality rates averaged only 1.12% per year prior to the drought. During the drought year, annual mortality jumped to 1.91% but abruptly fell back to 1.23% in the year following El Niño. Trees dying during the drought did not differ significantly in size or species composition from those that died previously, and there was no detectable effect of soil texture on mortality rates. These results suggest that intact Amazonian rainforests are relatively resistant to severe El Niño events.

3D micro-computed tomography of trabecular and cortical bone architecture with application to a rat model of immobilisation osteoporosis - A. Laib; O. Barou; L. Vico; M. H. Lafage-Proust; C. Alexandre; P. Rügsegger (Medical & Biological Engineering & Computing, 2000)

Geographic distribution of tree species occurring in the region of Manaus, Brazil: implications for regional diversity and conservation - Alexandre A. De Oliveira; Douglas C. Daly (Biodiversity and Conservation, 1999)

A central Amazonian terra firme forest. I. High tree species richness on poor soils - Alexandre A. De Oliveira; Scott A. Mori (Biodiversity and Conservation, 1999)

Genetic Organization and DNA Sequence of Early Region 4 of Bovine Adenovirus Type 3 - Joong B. Lee; Mohit K. Baxi; Neeraja Idamakanti; P. Seshidhar Reddy; Alexandre N. Zakhartchouk; C. Pyne; Lorne A. Babiuk; Suresh K. Tikoo (Virus Genes, 1998)

Characterization of Bovine Adenovirus Type 3 Early Region 2B - Mohit K. Baxi; P. Seshidhar Reddy; Alexandre N. Zakhartchouk; Neeraja Idamakanti; Caron Pyne; Lorne A. Babiuk; Suresh K. Tikoo (Virus Genes, 1998)

Induction and inhibition of human lymphocyte transformation by the lectin from the red marine alga Amansia multifida - Hermenio C. Lima; Francisco H. F. Costa; Alexandre H. Sampaio; Samya A. Neves; Norma M. B. Benevides; Darlio I. A. Teixeira; David J. Rogers; Ana Lúcia P. Freitas (Journal of Applied Phycology, 1998)

Fumarolic activity of Avachinsky and Koryaksky volcanoes, Kamchatka, from 1993 to 1994 - Yuri A. Taran; Charles B. Connor; Vyacheslav N. Shapar; Alexandre A. Ovsyannikov; Arthur A. Bilichenko (Bulletin of Volcanology, 1997)

Homologous oxypiperidines as inhibitors of protein synthesis in vitro and ex vivo - Dmitrij A. Kuznetsov; Nikolay V. Zavijalov; Gennadij J. Kelman; Alexandre V. Govorkov (Archives of Toxicology, 1987)